A comprehensive overview of evolutionary relationships and geographic distributions of cownose rays: more valid taxa needing protective measures - Yasmim Trindade C. Cunha; Renata Daldin Leite; Lucas Gabriel Pereira da Silva; Vanessa Paes Cruz; Jorge Luiz S. Nunes; Matheus Marcos Rotundo; Paola Palacios-Barreto; Píndaro Diaz-Jaimes; Ana P. Barbosa Martins; M. Aaron Macneil; Chris G. Mull; José Augusto Pires Bitencourt; et al. (Reviews in Fish Biology and Fisheries, 2026)
Rays of the family Rhinopteridae Jordan & Evermann, 1896 are highly migratory and widely distributed in warm tropical and temperate waters. Along the Brazilian coast, the presence of two species has been recorded: Rhinoptera bonasus Mitchill, 1815 and Rhinoptera brasiliensis Müller, 1836. These stingrays are commonly caught as bycatch in trawl fisheries, however, the two species lack distinctive external morphological features that allow for reliable differentiation—species identification is primarily based on the shape and arrangement of teeth in the buccal plates. This study aimed to investigate the evolutionary history of the genus Rhinoptera and to explore which evolutionary drivers, such as biogeographic events or behavioral traits, have influenced its diversification. To achieve this, we analyzed both mitochondrial and nuclear genetic markers, focusing on the species occurring along the Brazilian coast. Specimens of both species were collected across various locations in Brazil, and additional sequences from other Rhinoptera species were obtained from GenBank. Our results reveal the presence of multiple cryptic species within Rhinoptera , particularly within R. bonasus , and likely in Rhinoptera steindachneri Evermann & Jenkins, 1891 and Rhinoptera javanica Müller & Henle, 1841. Notably, R. bonasus does not occur in Brazilian waters nor in parts of the Caribbean where a distinct cryptic sister lineage was identified. Based on our findings, we propose the resurrection of Rhinoptera lalandii Müller & Henle, 1841 as the species representing the lineage found along the Brazilian coast and the Eastern Atlantic Ocean. We suggest that philopatric behavior may represent one of several factors potentially influencing diversification within Rhinopteridae, although this hypothesis requires direct behavioral and population level validation. These findings highlight the urgent need for a comprehensive taxonomic revision of the family, as well as a reassessment of current conservation strategies to better reflect the hidden diversity within this group of species. Graphical abstract

Characterization of a novel panel of polymorphic microsatellite loci and the mitogenome for the Neotropical marsupial Gracilinanus agilis (Didelphimorphia: Didelphidae) - Marcela Reis Duarte da Silva; Cássia Alves Lima-Rezende; Priscilla Lóra Zangrandi; André Faria Mendonça; Renato Caparroz; Emerson Monteiro Vieira; Fernando Pacheco Rodrigues (Molecular Biology Reports, 2026)
Background Microsatellite and mitochondrial markers are important tools for investigating natural populations, enabling the assessment of their diversity, genetic structure, kinship, parentage, and reproductive biology. Although the importance of such markers is widely recognized, their use in Neotropical mammals, especially marsupials, is still limited by the scarcity of species-specific loci characterized for extant species. Methods and results In this study, we describe and characterize 15 polymorphic microsatellite loci and recover part of the mitochondrial genome for the Neotropical marsupial Gracilinanus agilis using massive parallel sequencing with the Illumina platform. DNA sequencing yielded a dataset comprising 2,331,566 paired reads, of which 1,434 were mapped to a previously published mitogenome of the species, resulting in a partial mitogenome of 16,098 base pairs. The microsatellite search identified a total of 4,199 loci, of which 26 pairs were tested on 30 individuals. Of these, 15 loci were successfully amplified and exhibited high levels of genetic variation, with an average of 7.73 alleles per locus, a mean observed heterozygosity of 0.63, and a mean expected heterozygosity of 0.72. Furthermore, these loci collectively provide a high paternity exclusion probability and a low identity probability. Conclusions Our results suggest that the described marker set could be very useful for population genetic studies, evaluation of reproductive strategies (such as semelparity), and analysis of the population dynamics of this species.

Correction: Staphylococcus aureus in commercial laying hens from Pernambuco, Brazil: detection of efflux pumps and β-lactam resistance genes - Órion Pedro da Silva; Denny Parente de Sá Barreto Maia Leite; Valdir Vieira da Silva; Iago Carvalho Barbosa; Samuel Fernando dos Santos; Mércia Rodrigues Barros; Rinaldo Aparecido Mota (Brazilian Journal of Microbiology, 2026)

Staphylococcus aureus in commercial laying hens from Pernambuco, Brazil: detection of efflux pumps and β-lactam resistance genes - Órion Pedro da Silva; Denny Parente de Sá Barreto Maia Leite; Valdir Vieira da Silva; Iago Carvalho Barbosa; Samuel Fernando dos Santos; Mércia Rodrigues Barros; Rinaldo Aparecido Mota (Brazilian Journal of Microbiology, 2026)

Integrated crop-livestock systems in semiarid regions improve sheep performance compared to traditional use of natural rangelands: Nutrient digestibility, biochemical parameters, microbial protein and carcass traits - Claudenilde de Jesus Pinheiro Costa; Jheiny Rafaela Carvalho Lima; Rodrigo Barbosa de Medeiros; Maria Luana Medeiros; Arthur Lucas Julio Silva; Anderson da Silva Sales Torres; Thaysa Rodrigues Torres; Francisco Fernando Ramos de Carvalho; Márcio Vieira da Cunha; Mércia Virginia Ferreira dos Santos; José Carlos Batista Dubeux; Evaristo Jorge Oliveira de Souza (Small Ruminant Research, 2026)

Effects of quercetin supplementation in cooling extender on sperm quality of stallions - Luis Fernando Mercês Chaves Silva; Frederico Ozanam Papa; Iara Macêdo Petelinkar; Camila de Paula Freitas-Dell’Aqua; Sidnei Nunes de Oliveira; Endrigo Adonis Braga de Araujo; Luiz Roberto Pena Andrade Junior; Lucas Troncarelli Rodrigues; Gabriel Augusto Monteiro (Journal of Equine Veterinary Science, 2026)

Recreational ketamine exposure disrupts redox and inflammatory homeostasis in salivary glands and plasma leading to salivary dysfunction - Emanuelly Camilly Soares Lima-da-Silva; Cristian Kallahan Silva Chagas; Wallacy Watson Pereira Melo; Ana Paula de Andrade Silva; Sabrina Carvalho Cartágenes; Nair Correia de Freitas Castro; Fernando Bezerra; Rommel Rodrigues Burbano; Antonio Hernandes Chaves-Neto; Renata Duarte Souza-Rodrigues; Cristiane do Socorro Ferraz Maia; Rafael Rodrigues Lima (Food and Chemical Toxicology, 2026)

In Silico discovery and preliminary serological evaluation of an NcSRS2-derived synthetic peptide for the diagnosis of Neospora caninum in dogs and cattle - Maria Lorenza Leal Motta; Diogo Fonseca Soares Pereira; Juliana Rodrigues Moraes; Rodrigo Moreira Verly; Luís Fernando Pita Gondim; Clelton Aparecido dos Santos; Alexsandro Sobreira Galdino; Walderez Ornelas Dutra; Olindo Assis Martins-Filho; Lis Ribeiro do Valle Antonelli; Renato Andreotti; Ronaldo Alves Pinto Nagem; et al. (Veterinary Parasitology, 2026)

Metabolic response to anthelmintic treatment in beef cattle with subclinical gastrointestinal nematode infection - Mateus Lotério Coelho; Bianca Thais Baumann; Arthur Souza Galvão; Márcia Rocha Vicente; Murilo Damasceno Brunet De Freitas; Breno Braga Barros; Daniel de Castro Rodrigues; Siddartha Torres Rico; Eduardo Dos Santos; Nara Cônsolo; Luiz Colnago; Fernanda Ocampos; et al. (Veterinary Parasitology, 2026)

Surface electromyography and joint angle kinematics of horses at walk and trot on a treadmill - Matheus Crawford Tomaini; Daiane Patricia Oldiges Heck; Beatriz Cavalcante Moreira; Leonardo Rodrigues de Lima; Runer Augusto Marson; Fernando Queiroz de Almeida (Research in Veterinary Science, 2026)

Localized citizen science programs complement traditional research in macrofungal inventory, monitoring, and conservation in montane ecosystems of Southern Brazil - Mahatma Titton; Thiago Kossmann; Genivaldo Alves-Silva; Emerson Luiz Gumboski; Sidney José Damiani; Michel Tadeu Rodrigues Nolasco de Omena; Ana Luiza Castelo Branco Figueiredo; Fernando Vidal; Paulo Ricardo Pezzuto; Fernanda Karstedt; Diogo Henrique Costa-Rezende; Nelson Menolli; et al. (Fungal Ecology, 2026)

Listeria monocytogenes dry surface biofilms: a comparative study of mono- and coculture with Enterococcus faecium - Raul Fernando Pereira; Joana Rodrigues Cerqueira Zioli Fernandes; Thais Helena de Camargo; Jéssica Aragão F.F. Finger; Maristela S. Nascimento (Food Research International, 2026)

Early silicification of continental carbonates: Processes, settings, and implications for the South Atlantic pre-salt - Elias Cembrani; Amanda Goulart Rodrigues; Luiz Fernando De Ros (Earth-Science Reviews, 2026)

Topography- and depth-driven variability of β-glucosidase activity in Amazonian Forest soils (Brazil): A machine learning and structural equation modeling approach - Gizachew Ayalew Tiruneh; Ciro Abbud Righi; Jefferson Lordello Polizel; Vinicius Gonçalves; Carlos Rodrigues Pereira; Fernando Dini Andreote; Rafael Lima Oliveira; Jean Jesus Macedo Novais; Marcelo Henrique Procópio Pelegrino; Jose Alexandre Melo Dematte; Marcelino Carneiro Guedes; Ranjith P. Udawatta (CATENA, 2026)

High prevalence of Giardia spp. in cats without diarrhea and agreement between diagnostic techniques in the municipality of Londrina, Paraná, Brazil - Luiz Roberto Santos Aoki; Fernando de Souza Rodrigues; Giovanna Cristina Justino Santos Aoki; Lethicia Mendes Nino; Mateus Siqueira Pyles; Michel dos Santos Pinto; Michelle Santos Sabioni; João Alfredo Biagi Camargo Neto; Alex Akira Nakamura; Katia Denise Saraiva Bresciani; Gustavo Felippelli; Marcos Franke Pinto (Veterinary Research Communications, 2026)
In this study, we conducted an epidemiological investigation and analyzed the agreement between the Faust technique and the immunochromatographic assay in the diagnosis of Giardia spp. in 272 cats in the municipality of Londrina, Paraná state, Brazil. We identified an overall prevalence of 74.63% (203/272 [95% CI: 69.14–79.44%]) of Giardia spp. in cats, being significantly higher in adult and non-domiciled animals, which presented, respectively, 5.3 and 8.6 times more chances of infection when compared to kittens and domiciled animals. However, all the animals investigated that tested positive did not present with diarrhea. Regarding diagnostic methods, using coproparasitological examination, Giardia spp. cysts were observed in the feces of 193 cats, and through the immunochromatographic assay, coproantigens of this protozoan were detected in 203 samples, demonstrating almost perfect agreement ( Kappa Cohen: 0.907). Thus, according to the authors’ knowledge, this is the highest prevalence of Giardia spp. ever identified in cats in Brazil, and with regard to diagnostic methods, we observed a high concordance between the coproparasitological examination and the immunochromatographic assay in the detection of the aforementioned protozoan.

Aging impact on canine extracellular vesicles production, size, and miRNA content - Clara Luna Marina; Alexandra Mazer Greuel; Lucas de O. Las-Casas; Evilly Lopes-Gomes; Sabrina Simplício de Araújo Romero Ferrari; Marcio Lourenço Rodrigues; Flavia C. G. dos Reis; Anamélia Lorenzetti Bocca; Simoneide Souza Titze-de-Almeida; Fernando Francisco Borges Resende; Fabiano José Ferreira de Sant’Ana; Ricardo Titze-de-Almeida (Veterinary Research Communications, 2026)
Increasing life expectancy has been accompanied by a higher prevalence of age-associated conditions, underscoring the need to better understand biological mechanisms of aging and to identify accessible biomarkers. Extracellular vesicles (EVs) are lipid-bilayer vesicles that mediate intercellular communication by transporting proteins, lipids, and regulatory RNAs, including microRNAs (miRNAs). Here, we investigated whether the abundance, morphology, and molecular cargo of plasma-derived EVs differ between young and senior dogs. Blood samples were obtained from 24 clinically healthy dogs in Gama (Federal District, Brazil), and plasma EVs were isolated by sequential centrifugation, filtration through a 0.22 μm filter, and ultracentrifugation. EVs concentration and size distribution were assessed by nanoparticle tracking analysis (NTA), morphology by transmission electron microscopy (TEM), and cargo by quantification of total protein and sterols using commercial assays. In addition, we quantified miR-19b, miR-29c, miR-7, miR-155, and miR-21 by Real Time Quantitative Polymerase Chain Reaction (RT-qPCR). Senior dogs exhibited a lower plasma EV yield and greater size heterogeneity, with a higher proportion of larger EVs. Total protein and sterol content per starting plasma volume were reduced in the senior group; however, sterol normalized per EV was increased, consistent with compositional remodeling of circulating vesicles with age. Finally, EV-associated miRNA levels were reduced in senior dogs, particularly miR-19b and miR-29c. Collectively, these findings indicate that canine aging is associated with marked changes in plasma EV abundance, morphology, and cargo, indicating that EVs could represent a promising tool for investigating age-related disorders in dogs.

Soil physical quality and organic carbon dynamics in low-input perennial rubber plantations across a chronosequence in the Brazilian Cerrado - Luís Felipe Leite Sabino de Oliveira; Lucas Eduardo de Oliveira; Taísa Cristina Tinoco; Fernando Antônio de Souza; Hamilton César de Oliveira Charlo; Leonardo Carneiro Morgado; Arcângelo Loss; Dinamar Márcia da Silva Vieira; José Luiz Rodrigues Torres (Agroforestry Systems, 2026)

Pelleted high-concentrate diets containing different fiber sources for finisher lambs of distinct genotypes - Veridiana Basoni Silva; Lucas Santiago Gomes Brasileiro; Hemilly Cristina Menezes de Sá; Gilberto de Lima Macedo Júnior; Fernando Antônio de Souza; Matheus Rodrigues de Almeida Santos; Marivânia de Fátima Neri Campos; Sabrina Ludmila da Costa; Luciano Soares de Lima; Iran Borges (Small Ruminant Research, 2026)

Fatty acid composition and gene expression involved in lipid metabolism from Nelore and Rubia Gallega x Nelore cattle - Adrielle M. Ferrinho; Fabio Luis Henrique; Gabriella Vespe de Moura; Taiane da Silva Martins; Julian Muñoz; Lenise F. Mueller; Pollyana Leite Matioli; Tamyres Rodrigues de Amorim; Alessandra Bridi; Mirele D. Poleti; Juliano Coelho da Silveira; João Negrão; et al. (Livestock Science, 2026)

Deformational architecture and kinematic reconstruction of a large-scale mass-transport deposit from the integration of digital outcrop models and field-based structural analysis, La Peña Canyon, Paganzo Basin - Leonardo Mairink Barão; Barbara Trzaskos; Fernando Farias Vesely; Victoria Valdez Buso; Mérolyn Camila Naves de Lima Rodrigues; Deise Marli da Silveira; Guillan Diedrichs Fayad; Luis Gustavo de Castro; Dorval Carvalho Dias Filho; Juan Pablo Milana (Journal of Structural Geology, 2026)

Droplet class and spray volume influence on spray characteristics and herbicide performance in a maize-Brachiaria grass intercropping system - Arthur Duarte Rodrigues Neto; Thais Regina Ramos Alves; Leandro Tropaldi; Daniel Nicodemo; Fernando Shintate Galindo; Paulo Humberto Pagliari; Ronaldo Cintra Lima; Vagner do Nascimento; Marina Funichello; Evandro Pereira Prado (Phytoparasitica, 2026)
Optimizing maize–Brachiaria intercropping requires effective weed management with selective maize herbicides. This study evaluated the spray performance and efficacy of atrazine + nicosulfuron for weed management in maize–Brachiaria intercropping, focusing on how droplet classes and spray volumes affect maize growth and yield. The deposition experiment was conducted in a greenhouse in a completely randomized design with six replications. Field experiments were conducted during two seasons [2021 early season—ES (rainy season) and 2022 late season—LS (dry season) in a randomized block design and a 4 × 2 factorial (fine, medium, coarse, and very coarse droplet classes × spray volumes of 77 and 144 L ha −1 ) plus four controls treatments: Maize + Brachiaria without weed control, Maize + Brachiaria manually weeding, Brachiaria manually weeding, and Maize manually weeding. The study revealed that droplet class and spray volume significantly influence droplet deposition. Treatments spraying fine droplets at 144 L ha −1 exhibited higher coverage and droplet density levels. Intercropping maize with Brachiaria grass can be achieved without significant yield losses in the ES. However, the intercropping system reduced maize yield by approximately 17% in the LS. Applying the herbicides atrazine + nicosulfuron at 144 L ha −1 improved weed control and positively impacted maize yield during the LS.

Integrin inhibition differentially remodels vascular networks in lung metastases driven by vessel co-option or angiogenesis - Laura Marcos-Zazo; Iván Carrera-Aguado; Jesús Gómez-Escudero; Patricia Berlana-Galán; Irene Torre-Cea; Elena Guerra-Paes; Celia Redondo-Gonzalez; Juan Sánchez-Mateos; Daniel Cáceres-Calle; Óscar Maiques; Miguel Pericacho; Susana Fraile; et al. (Angiogenesis, 2026)
Tumor progression depends on an adequate blood supply to sustain oxygen and nutrients delivery. While tumor angiogenesis involves the formation of new blood vessels from pre-existing ones, vessel co-option represents a non-angiogenic vascularization strategy whereby tumor cells utilize pre-existing host vessels. Co-opted vessels have been considered refractory to anti-angiogenic therapies, and pharmacological modulation of co-opted vessels remains limited. In this study, we investigate the effects of low-dose cilengitide on tumor vascular remodeling in vessel co-option and angiogenic metastatic models. Our results reveal that cilengitide exerts distinct vascular effects depending on the mode of tumor vascularization. In vessel co-option-driven tumors, cilengitide treatment is associated with the remodeling of the co-opted vasculature into a more organized normalized vascular network, characterized by an increased number of functional blood vessels and enhanced vascular barrier integrity. In contrast, in angiogenic-driven tumors, cilengitide treatment promotes an expansion of the vascular network consistent with augmented, but structurally immature angiogenesis. Importantly, vascular remodeling in vessel co-option metastases is accompanied by enhanced blood vessel perfusion and reduced hypoxia, which correlates with enhanced responsiveness to chemotherapy. Conversely, in angiogenic metastases, the vascular network induced by low-dose cilengitide fails to support immunocompetent microenvironmental features and is associated with increased chemotherapy resistance. This study provides the first evidence that co-opted vasculature can be therapeutically targeted via integrin inhibition, suggesting vascular normalization remodeling as a potential strategy to overcome resistance in tumors undergoing vessel co-option.

Beyond mortality: Fipronil-induced disorientation and impaired survival in the social wasp Polybia paulista - Vinicius Edson Soares de Oliveira; Nathan Rodrigues Batista; William Fernando Antonialli-Junior (Chemosphere, 2026)

Urban aerosols and the intensification of maximum air temperature in a tropical Amazonian city - Rafael Palácios; Marco A. Franco; Fernando G. Morais; Maurício Moura; Francisco de Souza Oliveira; Glauber Cirino; Breno Imbiriba; Leone F.A. Curado; João Basso; Thiago R. Rodrigues; Amaury de Souza; Julia Cohen; et al. (Urban Climate, 2026)

Co-inoculation of PGPB and AMF: Impacts on common bean yield, nutrition, and selective root taxon co-occurrence - Fernando de Souza Buzo; Lucas Martins Garé; Nayara Fernanda Siviero Garcia; Juliana Trindade Martins; João Paulo Furlan Rodrigues; Barbara Nairim Ceriani de Luna; Vinicius Tamboreli Rodrigues; Lucas Amoroso de Carvalho; Daniel Guariz Pinheiro; Amaia Nogales; Everlon Cid Rigobelo; Orivaldo Arf (Journal of Cleaner Production, 2026)

Giant paraovarian cyst causing abdominal distention in a Swiss mouse (Mus musculus) - Daniel F. Barrantes Murillo; Luis J. Alfaro Quillas; Regina C. Rodrigues da Paz; Fernando H. Furlan Gouvêa; Caroline Argenta Pescador; Marcos de Almeida Souza (Journal of Comparative Pathology, 2026)

Revisiting two-stage models of chemically-induced cirrhosis-associated hepatocarcinogenesis in rodents: methodological and histopathological approaches - Antonio Rodrigues Bueno da Fonseca; Paulo Franco Cordeiro de Magalhães Junior; Luis Fernando Barbisan (Journal of Molecular Histology, 2026)
Repeated exposure to hepatotoxins such as carbon tetrachloride (CCl 4 ), thioacetamide (TAA), or diethylnitrosamine (DEN) has been frequently used to induce fibrosis/cirrhosis in rodents. In this narrative review, we compared two-stage medium-term protocols using different CCl 4 or TAA regimens in DEN-initiated rats and mice. In addition, we revisited our previous two-stage DEN/CCl 4 or DEN/TAA rat models to compare fibrosis grade, the mean number, and the percentage of liver area occupied by hepatocellular lesions positive for placental glutathione S-transferase (GST-P). Thus, we evaluated two groups of male Wistar rats that received DEN (a single dose), as an initiator agent for liver carcinogenesis, followed by CCl 4 or TAA regimens (multiple doses) until week 25. Both male Wistar groups presented lower body weight gain and higher liver weight, serum alanine aminotransferase (ALT) levels, hepatocyte proliferation, and a frank development of fibrosis/cirrhosis, GST-P-positive preneoplastic lesions, and liver tumors. However, DEN/TAA protocol in male Wistar rats was more effective as a fibrosis/cirrhosis-associated hepatocarcinogenesis model since TAA effectively accelerates liver disease progression and carcinogenesis. In addition, these chemical regimens have been prospectively studied as a suitable and effective protocol that resembles the corresponding human disease with various molecular and morphological outcomes. In conclusion, two-stage DEN/CCl 4 or DEN/TAA rodent models are effective in mimicking the progression of fibrosis-associated hepatocarcinogenesis and are suitable for prophylactic or therapeutic investigations.

Climatotherapy in marine and dead sea environments for musculoskeletal and rheumatologic conditions: a systematic review of effectiveness and safety - Tatiana Leite Müller; Fernando Hellmann; Daniel Maurício de Oliveira Rodrigues; María Lorena Vela; Francisco Maraver (International Journal of Biometeorology, 2026)
Climatotherapy (including thalassotherapy, sun exposure, and marine mud therapy) has long been used as a complementary intervention for musculoskeletal and rheumatologic disorders (MSRDs), yet its evidence base remains fragmented and methodologically heterogeneous. To synthesize the effectiveness and safety of climatotherapy in marine or Dead Sea environments for MSRDs, focusing on pain, physical function, and health-related quality of life. Following Joanna Briggs Institute methodology and PRISMA 2020, PubMed, PEDro, and the Cochrane Library were searched (May 2024; updated September 2025) for randomized and non-randomized trials of climatotherapy in marine or Dead Sea settings. Methodological quality was assessed with the PEDro scale. A structured narrative synthesis was complemented by a limited meta-analysis of pain; given the few trials and substantial heterogeneity, pooled estimates are exploratory. Ten articles representing nine studies (n = 465) were included. Interventions consistently produced short-term improvements in pain, physical function, and quality of life. Pooling was feasible only for pain (k = 2) and was statistically inconclusive, but condition-specific analysis showed a large, significant effect in osteoarthritis and a smaller, non-significant effect in fibromyalgia. Single-study estimates indicated benefits for tender point count and physical quality of life. No serious adverse events were reported, though safety was inconsistently assessed. Climatotherapy shows consistent short-term benefits, particularly for pain and physical function in osteoarthritis. Methodological limitations preclude firm pooled conclusions; rigorous multicenter trials with standardized outcomes and safety reporting are needed. Trial RegistrationPROSPERO CRD42024534694 (registered May 2024).

Abundant Development of Agaricales Fungi on Livingston Island, Antarctica: Potential Connections to Climate Change - Fernando Augusto Bertazzo-Silva; Flavia Helena Aires Sousa; Kamille Rodrigues Ferraz; Jorge Renato Pinheiro Velloso; Evelise Leis Carvalho; Marcos André Pinheiro Velloso; Vanessa dos Anjos Baptista; Adriano Luis Schünemann; Carlos Ernesto Gonçalves Reynaud Schaefer; Jair Putzke (Current Microbiology, 2026)
Rapid warming across Antarctica is reshaping terrestrial ecosystems, yet the dynamics of macroscopic fungi in this region remain largely undocumented. Here, we present the first ecological and statistical assessment of Agaricales fungi on Byers Peninsula, Livingston Island (South Shetland Islands, Antarctica), based on surveys conducted in February 2023. Across 20 sites, we recorded 2,566 basidiomes representing eight morphospecies in three genera ( Arrhenia, Galerina, and Omphalina ). Community diversity was moderate (Shannon–Wiener H′ = 1.97; Simpson’s D = 0.85), with assemblages dominated by Omphalina (68.4% of basidiomes), while Arrhenia sp. 1 displayed the broadest spatial distribution (65% of sites). Spatial analyses revealed significant variation in Agaricales abundance among sites (ANOVA, p = 0.016), while multivariate ordination (NMDS based on Bray–Curtis dissimilarity) showed substantial overlap in morphospecies composition across dominant vegetation types, with no significant differences detected by PERMANOVA (p = 0.527). The emergence of diverse basidiome assemblages in such an extreme environment underscores the ecological relevance of fungi in polar ecosystems and highlights their potential as sensitive bioindicators of climate-driven change. This quantitative baseline provides a critical reference for long-term monitoring and advances understanding of fungal contributions to biogeochemical processes in a rapidly changing Antarctic landscape.

Bile Acids as Functional Additives in Plant-Based Tilapia Diets: A Dose-Response Study on Growth, Lipid Metabolism, and Hepatoprotection - Cleber Fernando Menegasso Mansano; Daniely Alves Rodrigues; Mayra Lizett González-Félix; Kifayat Ullah Khan; Thiago Matias Torres do Nascimento; Andressa Tellechea Rodrigues; Luan Souza do Nascimento; Beatrice Ingrid Macente; Wilson Massamitu Furuya (Fishes, 2026)
The replacement of fishmeal with plant-based ingredients in aquafeeds, while economically and environmentally advantageous, can impair lipid metabolism and liver function in fish due to the lack of specific bioactive compounds such as bile acids (BAs). BAs are amphipathic steroid molecules that facilitate lipid digestion and act as signaling hormones, yet their optimal inclusion levels in conventional, balanced diets for Nile tilapia (Oreochromis niloticus) remain undefined. This study evaluated the effects of dietary BA inclusion on growth performance, feed efficiency, body composition, and serum biochemical parameters of juvenile Nile tilapia (GIFT strain, initial weight 18.04 ± 3.67 g) and estimated the optimal inclusion level. Six isoproteic (320 g kg−1) and isoenergetic (3300 kcal kg−1) plant-based diets were formulated with increasing BAs levels (0, 50, 100, 200, 400, and 600 mg kg−1) and fed to quadruplicate groups for 45 days. Only the Linear Response Plateau (LRP) model converged for weight gain data, estimating the optimal BA level at 479.70 mg kg−1, with a plateau weight gain of 76.60 g. Inclusion of the 50–600 mg kg−1 BAs significantly improved specific growth rate (up to 4.53%), crude protein retention efficiency (up to 81.11%), and whole-body crude protein content (up to 50.52%) compared to the control (p

Clinical efficacy and safety of a spray formulation containing carvacrol and eugenol against Rhipicephalus linnaei and Ctenocephalides felis felis in artificially infested dogs - Fernando Rocha Miranda; Isabelle Vilela Bonfim; Anna Julia Bessa Fernandes; Ingrid Lins Raquel de Jesus; Taynara Monsores e Silva; Matheus Eduardo Costa da Silva; Mathias Pittizer da Silva; Gabrielle de Lima Monzato; Clara Rodrigues Dutra; Ygor Henrique da Silva; Brena Gava Guimarães; Diefrey Ribeiro Campos; et al. (Veterinary Parasitology, 2026)

Grape marc as a novel dietary strategy to reduce methane emission in sheep - Rodrigo Chaves Barcellos Grazziotin; Mauricio Cardozo Machado; Jean Victor Savian; Lucas Jackson De Souza; Rogério Folha Bermudes; Cássio Cassal Brauner; Marcio Nunes Corrêa; Fernanda Medeiros Gonçalves; Isabela Seffrin Rodrigues; Yasmin Alencastro Da Rosa; Fernando Amarilho-Silveira (Small Ruminant Research, 2026)

Paleoecological patterns and Panthalassic paleobiogeographic affinity of Pennsylvanian conodont faunas from the Chibcha Terrane (Colombia) - Andrés Felipe Rojas Mantilla; Ana Karina Scomazzon; Afonso César Rodrigues Nogueira; Fernando Erthal; Luis Antonio Obregón Cubillos; Paulo A. Souza; Sara Nascimento; Jordana Maria Viccari (Marine Micropaleontology, 2026)

Evaluation of ceramic and polymeric membranes for crossflow microfiltration of coconut water: Filtration performance and composition of the clarified coconut water - José Diogo da Rocha Viana; Elenilson de Godoy Alves Filho; Lorena Mara Alexandre e Silva; Paulo Riceli Vasconcelos Ribeiro; Carlos Alberto Kenji Taniguchi; Arthur Claudio Rodrigues de Souza; Fernando Antônio Pinto de Abreu; José Carlos Cunha Petrus; Kirley Marques Canuto (Journal of Food Engineering, 2026)

Defatting irradiated cricket flour to improve its functional properties and develop innovative hybrid beef patties - Guilherme Fernando Cavalcante Bruno Amaral Gama; Fernanda Beatriz Jacquiminouth Lopes; Marise Aparecida Rodrigues Pollonio; Tiago Bueno de Moraes; Carmen Josefina Contreras Castillo; Camila de Souza Paglarini (Food Chemistry, 2026)

Preliminary Physicochemical Assessment of Aquaculture Effluents for Irrigation Reuse in the Brazilian Semi-Arid - Tereza Amelia Lopes Cizenando Guede Rocha; Rafael Oliveira Batista; Silvanete Severino da Silva; Stefeson Bezerra de Melo; Phâmella Kalliny Pereira Farias; Palloma Vitória Carlos de Oliveira; Francisco Éder Rodrigues de Oliveira; Daniela da Costa Leite Coelho; Luiz Fernando de Sousa Antunes; Antônio Gustavo de Luna Souto; Laio Ariel Leite de Paiva; Fagner Nogueira Ferreira (Water, Air, & Soil Pollution, 2026)
Aquaculture effluents are increasingly recognized as a strategic resource for agricultural water reuse, especially in semi-arid regions, where water scarcity and fertilizer costs intensify pressure on production systems. Within a circular economy framework, these effluents may simultaneously supply water and nutrients; however, their physicochemical composition must be carefully assessed, since excessive salt loading may impair soil quality and threaten long-term agricultural sustainability. This study performed a preliminary physicochemical assessment of raw and diluted aquaculture effluents to determine their potential for irrigation reuse in the Brazilian semi-arid, with emphasis on salinity, sodicity, ionic composition, nutrient-related parameters, and trace elements. The experiment was conducted at the Federal Rural University of the Semi-Arid (UFERSA), Mossoró, northeastern Brazil, from October 2022 to December 2023. Five treatments were evaluated: T1 (100% freshwater), T2 (75% freshwater + 25% effluent), T3 (50% freshwater + 50% effluent), T4 (25% freshwater + 75% effluent), and T5 (100% effluent). Samples were analyzed for pH, electrical conductivity (EC), major ions, nutrients, and trace elements, while sodium adsorption ratio, magnesium hazard, residual sodium carbonate, and hardness were also determined. Dilution with freshwater partially improved irrigation suitability but increasing effluent proportion intensified hydrochemical restrictions. Although effluents supplied relevant amounts of Ca 2+ , Mg 2+ , N, and P, reuse potential was mainly limited by salinity, particularly EC and Cl − , whereas sodicity remained secondary. Multivariate analysis identified EC, Ca 2+ , Mg 2+ , Cl⁻, HCO₃ − , P, SAR, Mn, Zn 2+ , and N as the main drivers of water quality variation, supporting irrigation reuse under controlled dilution, drainage, and continuous monitoring protocols. Graphical Abstract

Canopy structure, dry matter intake and performance of Holstein × Gyr cows (Bos taurus taurus L. × Bos taurus indicus L.) under rotational stocking in Urochloa spp. pastures - Natalia Avila Soares; Carlos Augusto de Miranda Gomide; Patrícia do Rosário Rodrigues; Domingos Sávio Campos Paciullo; Mirton José Frota Morenz; Angelo Herbet Moreira Arcanjo; Fernando Antônio de Souza; Fernanda de Kássia Gomes; Pedro Drummond Rodrigues; Ângela Maria Quintão Lana (Tropical Animal Health and Production, 2026)
Pasture-based dairy systems require well-adapted forage cultivars and appropriate grazing management to sustain milk production while maintaining favorable sward structure. The objective of this study was to evaluate the performance of Holstein × Gyr crossbred cows and the productive and structural characteristics of Paiaguás grass pasture ( Urochloa brizantha cv. BRS Paiaguás) and Ipyporã grass pasture ( Urochloa brizantha × Urochloa ruziziensis cv. BRS Ipyporã), under rotational stocking during two rainy season. For the agronomic variables, a completely randomized design was adopted in a split-plot design: two grasses and three experimental phases, with twelve paddocks evaluated per phase. The arrangement for milk yield and milk composition was the complete switchback trial, and for dry matter intake, it was the cross-over. Paiaguás grass showed greater herbage mass, accumulation and herbage accumulation rate. Ipyporã grass showed a greater leaf: stem ratio (1.54 vs. 1.02) and greater volumetric density (127.45 vs. 108.15 kg DM cm ha − 1 ). Milk yield did not differ between cultivars or experimental phases with an average value of 107.65 L ha − 1 day − 1 ). Stocking rate was higher in Paiaguás grass pasture compared with Ipyporã grass (7.71 vs. 6.90 AU ha − 1 ). Dry matter intake differed between cultivars only in phase 2, when it was higher for Ipyporã grass compared with Paiaguás grass (2.21 vs. 1.97% of body weight, respectively). Both cultivars supported a great milk yield when managed with 41 cm pre-grazing height for cv. BRS Ipyporã and 63 cm for cv. BRS Paiaguás, and 50% defoliation.

Ecotoxicity assessment of dairy wastewater: environmental risks and regulatory needs - Magno Lange Albuquerque; Fernando Rodrigues-Silva; Alyson Rogério Ribeiro; Carollina M. Chávez; Gilcinéa de Cássia Santana; Alessandra da S. Martins; Camila C. Amorim; Maria Clara V. M. Starling (Ecotoxicology, 2026)

Climate Predicts Tree Dispersal Strategies Across Brazil's Ecosystems - Fernanda C. Souza; Vinícius Andrade Maia; Renata Françoso; Matheus Coutinho Freitas de Oliveira; Ana Beatriz Ligo; Bruno X. Pinho; Jesús Aguirre‐Gutiérrez; Martin Sullivan; Larissa Rocha‐Santos; Laura de Brito Évora; Leonardo de Sousa Miranda; María Natalia Umaña; et al. (Global Ecology and Biogeography, 2026)
Aim We investigate the distribution of dispersal modes — endozoochory (via animal ingestion), synzoochory (via animal seed accumulation) and anemochory (via wind)—and seed mass of woody plants across Brazilian ecosystems, testing whether their relative abundance in local plant communities could be predicted by climate, edaphic factors and dispersal agents (e.g., the main vectors moving seeds). We expected climate to be the main predictor of dispersal strategy abundance. Location Brazilian ecosystems (Amazon, Atlantic Forest, Cerrado and Caatinga). Time Period 2004–2020. Major Taxa Studied Woody angiosperms, trees and shrubs. Methods We assigned seed mass to 1984 species and dispersal mode to 2203 species within 300 old‐growth and non‐flooded plots. We employed Random Forest regressions to assess the influence of water availability, temperature seasonality, soil fertility, wind and frugivorous primates on the community‐weighted means of seed mass and dispersal modes. We mapped predictions and estimated the area of applicability to identify regions where predictions were reliable. Results Climate was the main factor predicting tree dispersal strategies, followed by dispersal agents or soil properties. Endozoochory was prevalent in wetter regions with high water availability and greater diurnal temperature range. Anemochory was more common in drier regions with low water availability, stronger winds and greater diurnal temperature range, whereas synzoochory was more abundant in areas with low temperature seasonality. Heavier seeds were more prevalent in regions with less seasonal temperatures, smaller diurnal temperature ranges and weaker winds. Main Conclusions Climate is a key predictor of the distribution and prevalence of plants with contrasting dispersal modes and seed masses. We thus expect functional responses to environmental change associated with shifts in the relative abundance of dispersal strategies, with implications for ecosystem services. Our results also highlight the critical role of plot‐based datasets in improving our understanding of how environmental factors influence seed dispersal strategies across tropical ecosystems.

Too close for comfort? Mesozooplankton dynamics in Marine Protected Areas adjacent to mining tailings on the southeastern Brazilian shelf - Bianca Salvador; Laura Rodrigues da Conceição; Renato David Ghisolfi; Mônica Souza Mendes; Tayná Rosa Martins Paiva; Valéria da Silva Quaresma; Daniel Rigo; Gustavo Martins Rocha; Paulo Sergio Salomon; Gabriel Harley Costa Santos; Priscila Teixeira-Amaral; Márcio Murilo Barboza Tenório; et al. (Marine Environmental Research, 2026)

Morphometric characterization and decision tree–based prediction of phenotypic traits in Pantaneiro sheep - Agda Costa Valério; Tatiane Fernandes; Adrielly Lais Alves da Silva; Renata Alves Chagas; Ariadne Patrícia Leonardo; Marcio Rodrigues de Souza; Núbia Michelle Vieira da Silva; Fernando Miranda de Vargas Junior (Tropical Animal Health and Production, 2026)
The Pantaneiro sheep is a locally adapted genetic resource shaped by the seasonal flooding, thermal stress, and heterogeneous forage availability of the Brazilian Pantanal. Characterizing its morphological structure using objective and field-applicable traits is essential for standardized phenotyping and conservation-oriented breeding strategies. This study evaluated 211 Pantaneiro ewes raised under semi-extensive management to identify morphometric patterns and identify simple predictors of qualitative phenotypic traits. Twenty-three quantitative and ten qualitative traits were measured and analyzed using multivariate techniques, including factor analysis and hierarchical clustering, to describe morphological structure. Decision tree models were then developed to predict key phenotypic traits from morphometric variables. Four main morphological dimensions explained 64.6% of total variance, reflecting body capacity, limb robustness, and cranial morphology. Among the ten decision tree models generated, three achieved predictive accuracies above 80% head profile (86.3%), muzzle type (84.8%), and wool color (82.5%), indicating that metatarsus and tarsus circumferences are reliable non-invasive predictors of cranial and tegumentary traits. The integration of multivariate morphometry and machine learning proved effective for identifying simple predictors applicable to field management. Overall, these findings reinforce the adaptive potential of Pantaneiro ewe and their importance for sustainable and resilient livestock production in tropical floodplain ecosystems.

Correction to: Parasitofauna of Atlantic Yellow-nosed Albatross, Thalassarche chlororhynchos (Procellariiformes: Diomedeidae), stranded on the northeastern coast of Brazil - André Mota Alves; Larissa Mello Figueiredo; Rayanne Beatriz de França Oliveira; Órion Pedro da Silva; Sarah Raquel Jesus Santos Simões; Tamiris dos Santos Rodrigues; Marina Maria Verissimo de Oliveira; Emanuelle Ferreira dos Santos; Bruna Gomes de Oliveira; Iara Gama de Medeiros; Elaine Knupp de Brito; Claudia Carvalho do Nascimento; et al. (Thalassas: An International Journal of Marine Sciences, 2026)

Parasitofauna of Atlantic Yellow-Nosed Albatross, Thalassarche chlororhynchos (Procellariiformes: Diomedeidae), stranded on the northeastern coast of Brazil - André Mota Alves; Larissa Mello Figueiredo; Rayanne Beatriz de França Oliveira; Órion Pedro da Silva; Sarah Raquel Jesus Santos Simões; Tamiris dos Santos Rodrigues; Marina Maria Verissimo de Oliveira; Emanuelle Ferreira dos Santos; Bruna Gomes de Oliveira; Iara Gama de Medeiros; Elaine Knupp de Brito; Claudia Carvalho do Nascimento; et al. (Thalassas: An International Journal of Marine Sciences, 2026)

Organic Carbon Compartments and Chemical Attributes of Sandy Soil in Response to Crop Succession Under Conventional Management and Fallow Long-term in the Semi-arid Region - Andler Milton de Paiva Oliveira; Luiz Fernando de Sousa Antunes; José Francismar de Medeiros; Stefeson Bezerra de Melo; Jeane Cruz Portela; Antônio Gustavo de Luna Souto; Rafael Oliveira Batista; Rômulo Simões Cezar Menezes; Frederico Ribeiro do Carmo; Daniel Valadão Silva; Francisco Éder Rodrigues de Oliveira; João Luiz Lima; et al. (Journal of Soil Science and Plant Nutrition, 2026)

Clarified açaí (Euterpe oleracea Martius) exerts protective effects against methylmercury toxicity in salivary glands and total saliva - Vinicius Ruan Neves dos Santos; Leonardo Oliveira Bittencourt; Hadassa Helez Neves Ferreira; Daiane Claydes Baia-da-Silva; Paulo Fernando Santos Mendes; Luis Eduardo de Oliveira Teixeira; Antonio Hernandes Chaves-Neto; Bruno Santana Carneiro; Diomar Cavalcante Oliveira; Iracina Maura de Jesus; Renata Duarte de Souza-Rodrigues; Herve Rogez; et al. (BioMetals, 2026)
Methylmercury (MeHg) contamination can cause damage to the salivary glands, which is associated with oxidative stress and glandular dysfunction. Açaí ( Euterpe oleracea Martius), a fruit rich in antioxidants, emerges as a natural alternative to mitigate the toxic effects of MeHg. This study aimed to evaluate whether clarified açaí juice exerts a protective effect on the major salivary glands of rats intoxicated with MeHg. Wistar rats were allocated into four groups: control, MeHg-exposed (0.04 mg/kg/day), açaí-supplemented (0.01 L/kg/day), and MeHg-exposed with açaí supplementation. The compounds were administered by orogastric gavage for 60 days. Subsequently, total saliva was collected to determine antioxidant capacity, lipid peroxidation, and amylase activity, while submandibular and parotid glands were analyzed to total mercury (Hg) levels, antioxidant capacity, and lipid peroxidation. Our results showed that açaí supplementation did not reduce Hg accumulation in the salivary glands. However, MeHg exposure significantly decreased antioxidant capacity in both glands, whereas açaí supplementation mitigated this reduction, maintaining values comparable to the control group. Lipid peroxidation was elevated in the MeHg group in both glands, but this alteration was attenuated by açaí. In saliva, MeHg exposure lowered antioxidant capacity and elevated lipid peroxidation levels, both of which were attenuated by açaí supplementation. Moreover, MeHg altered salivary protein concentration and reduced amylase activity, while açaí supplementation counteracted these effects. These results demonstrate that açaí’s antioxidant constituents confer protective effects against MeHg-induced oxidative damage and functional impairment in salivary glands and saliva, underscoring its potential as a natural protective agent against Hg toxicity.

Evolution and emergence of the integrase inhibitor 231 insertion resistance mutation in an HIV-2 strain isolated in central Portugal - João Pereira-Vaz; Anália Carmo; Alexandra Mendes; Célia Morais; Ana Alves; Fernando Rodrigues; Vítor Duque (Virus Genes, 2026)

Kinetics and experimental parameters of oral Toxoplasma gondii infection in Syrian hamsters - Talita Rodrigues dos Santos; Jorge Lucas Nascimento Souza; Luis Fernando Viana Furtado; Maira do Santos Carneiro Lacerda; Letícia Pereira Lopes; Mike dos Santos; Roselene Ecco; Érica dos Santos Martins-Duarte; Élida Mara Leite Rabelo (Veterinary Parasitology, 2026)

A framework for assessing the environmental safety of wastewater treated by advanced oxidation processes based on species sensitivity distribution - Fernando Rodrigues-Silva; Carla S. Santos; Ana I. Gomes; Vítor J.P. Vilar; Maria Clara V.M. Starling; Camila C. Amorim (Science of The Total Environment, 2026)

Techno-economic assessment of anti-elastase and antioxidant peptide production from buffalo cheese whey via ultrasound-assisted hydrolysis - Eduardo Steiger Kaufmann; Caroline Schmitz; Marcy Heli Paiva Rodrigues; William Jacobs; Daniel Neutzling Lehn; Luís Fernando Saraiva Macedo Timmers; Claucia Fernanda Volken de Souza (Food and Bioproducts Processing, 2026)

Limonene and carvacrol combined with drugs that inhibit ergosterol synthesis are potent against Leishmania major - Rita de Cássia Viana de Carvalho; Karla Germana dos Reis Bacelar; Eduardo Lima Pereira; Bianca Soriano dos Anjos; Evellyn Caroline Silva Melo; Francisco das Chagas de Souza Cunha; Paulo Sérgio de Araujo Sousa; Jefferson Almeida Rocha; Leiz Maria Costa Véras; Klinger Antônio da Franca Rodrigues; Maria das Graças de Freire Medeiros; Daniel Dias Rufino Arcanjo; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)
Leishmaniases are neglected diseases widely distributed in tropical and subtropical countries, caused by parasites of the Leishmania genus. Current therapy includes pentavalent antimonial and amphotericin B, but adverse effects persist. The development of a new, more selective, and less toxic combination therapy is therefore a rational and promising approach. In this study, we report the effects of combinations of the monoterpenes limonene (Lim) and carvacrol (Car) with drugs targeting ergosterol biosynthesis, namely nystatin (Nys), tioconazole (Tio), and rosuvastatin (Ros), on Leishmania major , their cytotoxicity on macrophages, and we evaluate their synergism and mechanisms of action. The combinations inhibited the growth of L. major promastigotes, with Lim-Car combined with nystatin (3:2) exhibiting the highest activity, showing an IC 50 of 2.02 µg/mL. Furthermore, this combination demonstrated greater action against amastigotes (IC 50 of 0.53 µg/mL) and a high selectivity index (33.60). Low cytotoxicity was observed in murine macrophages (CC 50 17.81 µg/mL), as well as a low hemolytic potential (CH 50 of > 100 µg/mL). The Lim-Car and nystatin (3:2) combination presented a synergistic effect, with a fractional inhibitory concentration index of 0.4. Changes in parasite membrane integrity were also observed, which may be linked to the interaction of nystatin with the enzyme 14-alpha demethylase, along with an increase in TNF-α expression and a reduction in IL-10 and IL-6 levels. These results suggest that the combination of Lim-Car with Nys (3:2) may exert a summative effect through multiple biochemical pathways and warrants further investigation as a potential combined therapy with antileishmanial activity.

Image-based phenotyping of castor bean seeds for morphological traits, seed weight prediction, and assessment of genetic diversity - Diego Andrade Santos; Diego Fernando Marmolejo Cortes; Mylena Almeida dos Santos; Myriam El Adas; Bismarck Ferreira de Morais; Denise Barreto dos Santos; Tairone da Silva de Almeida; Christian Adalberto Santos de Queiroz; Gabriel da Paixão Fernandes; Ailan Santos de Jesus; Rafaella da Silva Rodrigues; Daniel Santos Alves; et al. (Euphytica, 2026)
Digital seed phenotyping offers an efficient and objective alternative to conventional, labor-intensive methods for morphological characterization in plant breeding programs. In castor bean, rapid and reliable tools are essential to support genetic improvement. This study evaluated the potential of digital phenotyping for seed characterization and its application in breeding. Seeds from 65 accessions (2023) and 51 accessions (2024) were photographed with an RGB camera and processed in ImageJ® for extraction of morphological traits. Agreement between digital and manual measurements was assessed by correlation and Bland–Altman analysis, while machine learning models were trained to predict hundred-seed weight (HSW). Genetic diversity was explored using principal component analysis (PCA) and clustering, and variance components and heritability were estimated with mixed linear models. Digital phenotyping showed strong agreement with manual measurements (r = 0.95–0.97) and enabled accurate HSW prediction, with Ridge Regression achieving the best performance (R 2 = 0.88; RMSE = 3.83; MAE = 3.19). PCA explained 85.7% of the variance and revealed three phenotypic clusters. Traits such as seed length (H 2 = 0.88) and aspect ratio (H 2 = 0.87) exhibited high heritability, while roundness (H 2 = 0.79), perimeter (H 2 = 0.72), and area (H 2 = 0.67) were moderate. These findings demonstrate that digital phenotyping is a reliable and high-throughput method for castor bean seed characterization, supporting genotype selection and the integration of machine learning approaches into breeding programs for greater precision and efficiency.

Diversity of Endophytic Fungi in Theobroma grandiflorum and their Potential for Biological Control of Witches’ Broom Disease and Promotion of Cupuaçu Seedling Growth in the Amazon - Jusley Souza Santos; Nárcya Trindade de Souza; Thalya da Silva Rodrigues; Fernando José Fernandes Martins; Laryssa dos Santos Prado; Fernanda Viana Diniz; Erlangela Rocha Viga; Berenice Kussumoto de Alcântara da Silva; Clarice Maia Carvalho; Leila Priscila Peters (Current Microbiology, 2026)
Endophytic fungi can play a crucial role in protecting plants against pathogens. Cupuaçu tree ( Theobroma grandiflorum ) is a commercially valuable crop significantly affected by witches’ broom, a disease caused by the pathogen Moniliophthora perniciosa . In the current study, we report the first investigation on the cultivable fungal endophytic community associated with the leaves and stems of T. grandiflorum in the Western Amazonia. We also selected 14 endophytic fungi to analyze hydrolytic enzymes and screen their antagonistic activity against M. perniciosa under laboratory and greenhouse conditions. Our findings revealed that the diversity and composition of the endophytic communities did not differ significantly between the sampled leaf and stem tissues. Most of the endophytic fungi exhibited amylolytic activity (93%), while 71% showed cellulolytic activity and 43% displayed proteolytic activity. Additionally, antagonism assays with M. perniciosa revealed that Trichoderma orientale showed the highest growth inhibition (69.4%), followed by Cunninghamella blakesleeana (64.2%) and T. tawa (63.6%). In greenhouse experiments, T. tawa and C. blakesleeana significantly reduced infection by M. perniciosa by 50% and 70%, respectively. Plants co-inoculated with C. blakesleeana and the pathogen showed a significant increase in height, shoot dry biomass, and photosynthetic pigment content compared to plants infected only with M. perniciosa . Furthermore, the application of T. tawa and C. blakesleeana increased the levels of chlorophylls and carotenoids in healthy plants, indicating a beneficial interaction with the plant’s physiology. Thus, these fungi stand out as promising candidates for the development of bioinputs aimed at the sustainable management of diseases in cupuaçu cultivation in the Amazon.

Ruminally unprotected guanidinoacetic acid supply in sheep diets is effective in improving oocyte quality through mitochondrial function and by modulating regulatory gene markers that encode follicular growth, estrogen synthesis, and antiapoptotic activity - Jhennyfe Nobre de Sena; Camila Muniz Cavalcanti; Alfredo José Herrera Conde; Bruna Vitória de Freitas Alves; Larissa Fernandes Baia Cesar; Marta da Costa Sousa; Yohana Huicho Miguel; Louhanna Pinheiro Rodrigues Teixeira; Fernando Felipe da Silva Pereira; Gildas Mbemya Tetaping; Juliana Paula Martins Alves; César Carneiro Linhares Fernandes; et al. (Animal Reproduction Science, 2026)

Ag(I) complexes with natural products and triphenylphosphine: activity against tumor cell lines and mycobacterium tuberculosis - Jocely Lucena Dutra; João Honorato de Araujo-Neto; Rafael Wendel Rodrigues Santana; Rone Aparecido De Grandis; Giulia Polinário; Fernando Rogério Pavan; Javier Ellena; Alzir Azevedo Batista (JBIC Journal of Biological Inorganic Chemistry, 2026)

Modeling Future Climate Impacts on Brazil’s Operational Wind and Solar Energy Capacity - Felipe Husadel Poyer; Francisco Lopes Lima; Rodrigo Santos Costa; André Rodrigues Gonçalves; Fernando R. Martins; André F. P. Lucena; Enio Bueno Pereira (Environmental Modeling & Assessment, 2026)
Over the past decade, the Brazilian electricity sector has undergone a profound transformation, driven by the large-scale deployment of wind and solar photovoltaic power plants, a trend that is expected to continue in the years ahead. Although the transition to these variable renewable energy resources helps to reduce greenhouse gas emissions and mitigate the climate crisis, they are vulnerable to the very climate changes they help to avert. This study uses projections from CMIP6 global climate models under two future scenarios (SSP2-4.5 and SSP5-8.5) to assess potential impacts on power generation in the existing centralized wind and solar power facilities in Brazil. The study innovates by assessing the effects of climate change on the future performance of the power plants using measured historical capacity factors as a proxy, thereby eliminating the need for climate bias correction and standardized manufacturer power curves. Projections indicate a nationwide increase in wind potential between 6% and 15% by the end of the century, contributing to an extended wind season in the northeastern region and a stronger seasonality in the southern region. In contrast, the photovoltaic potential reveals modest change; the positive effects of increasing surface radiation are counterbalanced by the negative effects of warmer air temperatures across the assessed scenarios. These findings offer valuable insights for strengthening Brazil’s energy security under future climate conditions.

Polysaccharide-mediated stabilization of bacterial nanocellulose dispersions: Experimental and molecular dynamics study - Ricardo Silva-Carvalho; Daniela Martins; Tarsila G. Castro; Ana Cristina Rodrigues; Bruna Costa; Paula Parreira; Artur Cavaco-Paulo; Fernando Dourado; M. Cristina L. Martins; Miguel Gama (Food Hydrocolloids, 2026)

Phylogenetic diversity recovery along Atlantic Forest succession: The potential for conserving evolutionary history - Alex Josélio Pires Coelho; Carlos Mário Galván-Cisneros; Pedro Manuel Villa; Heitor Mancini Teixeira; Fabio Antônio Ribeiro Matos; Alice Cristina Rodrigues; Nayara Mesquita Mota; Fernando da Costa Britod Lacerda; Fábia Maria dos Santos Souza; Nathália Vieira Hissa Safar; Nathália Silva; Fabiana Bonani; et al. (Biological Conservation, 2026)

A survey of vector-borne bacteria in bat-associated mites (Mesostigmata: Macronyssidae and Spinturnicidae) from Brazil reveals the presence of Ehrlichia spp. - Luís Fernando da Cruz; Victor de Souza Mello-Oliveira; Maria Eduarda Moraes das Chagas; Gabriella Soares; Ana Cláudia Calchi; Ana Carolina Castro-Santiago; Leormando Fortunato Dornelas-Júnior; Érica Munhoz de Mello; Igor Massahiro de Souza Suguiura; Elizabete Captivo Lourenço; João Carlos Marocco; Letícia Dorigoni; et al. (Veterinary Research Communications, 2026)

Effect of increasing prickly pear cactus (Nopalea cochenillifera) levels in diets of Holstein × Zebu dairy cows on nutrients intake and digestibility, ingestive behavior, and milk fatty acids profile - Fernando Rossa; Adriane Pereira da Silva dos Santos; Fábio Andrade Teixeira; Claudenor de Jesus Santos; Robério Rodrigues Silva; José Esler de Freitas Júnior; Lara Maria Santos Brant; Fabiano Ferreira da Silva (Tropical Animal Health and Production, 2026)
This study evaluated the effects of including different levels of prickly pear cactus ( Nopalea cochenillifera ) in the diets of crossbred dairy cows (Holstein × Zebu) on nutrient intake and digestibility, nitrogen balance, microbial protein synthesis, milk yield and composition, and feeding behavior. Eight multiparous cows (15.9 ± 1.8 kg/day of milk; 100 ± 11 days in milk, mean ± SD) were assigned to a double 4 × 4 Latin square design with 21-day periods, consisting of 16 days of dietary adaptation followed by 5 days of data collection. The experimental diets were: (1) CON, without prickly pear cactus (PPC); (2) PPC16, containing 16% PPC in dry matter (DM); (3) PPC32, with 32% PPC in DM; and (4) PPC48, with 48% PPC in DM. The inclusion of PPC reduced NDF intake, both in absolute terms ( P = 0.037) and relative to body weight ( P = 0.021), and decreased water intake compared with the control diet ( P < 0.001), showing a quadratic response to inclusion levels ( P < 0.001). For digestibility, quadratic effects were observed for crude protein ( P = 0.007) and ether extract ( P < 0.001). Milk yield and principal components (protein, fat, and lactose) were not affected ( P > 0.05). However, PPC reduced milk cholesterol concentration ( P = 0.013) and altered the fatty acid profile, specifically decreasing CLA c9t11 ( P = 0.025) and n-3 fatty acids ( P = 0.033), while also increasing the proportion of saturated fatty acids ( P = 0.027). It was concluded that intermediate levels of prickly pear cactus inclusion (32–35% of DM) optimized nutrient utilization while maintaining milk production, representing the most suitable supplementation strategy for crossbred dairy cows under tropical conditions.

The parasitic fauna of Cory’s shearwater or bobo-grande (Procellariiformes: Calonectris borealis) stranded on the northeastern coast of Brazil - André Mota Alves; Larissa Mello Figueiredo; Rayanne Beatriz de França Oliveira; Tamiris dos Santos Rodrigues; Sarah Raquel Jesus Santos Simões; Iara Gama de Medeiros; Elaine Knupp de Brito; Jociery Einhardt Vergara Parente; Marcillo Altoé Boldrini; Victor Fernando Santana Lima; João Carlos Gomes Borges (Ornithology Research, 2026)

Hyperdominant Trees Reveal Savanna Vulnerability Under Climate Change - Facundo Alvarez; Ben Hur Marimon‐Junior; Beatriz Schwantes Marimon; Wesley Jonatar Alves da Cruz; Norberto Gomes Ribeiro Júnior; Raiane Gonçalves Béu; Polyanna da Conceição Bispo; Aldair de Souza Medeiros; Glécio Machado Siqueira; Marcelo Leandro Bueno; Fabiana de Gois Aquino; Frederico Augusto Guimarães Guilherme; et al. (Global Change Biology, 2026)
The Cerrado biome, spanning ~2 million km 2 , is one of the most extensive and biodiverse tropical savannas, yet it is paradoxically dominated by only 30 hyperdominant tree species (~2% of all species, > 50% of all stems). However, their vulnerability to climate change and the effectiveness of current conservation efforts remain uncertain. By combining (i) species distribution models calibrated with edaphic‐climatic predictors and occurrence data for hyperdominant Cerrado trees with (ii) functional‐trait analyses related to ecological strategies (leaf economics, bark investment, ecophysiology, drought tolerance, regeneration, and dispersal), we identified the biomass production and reproductive traits that best predict species persistence under high‐emission scenarios (RCP8.5). Currently, only 427,980 km 2 (~17.4%) of the modeled potential environmental suitability falls within protected areas; under future climate scenarios, this protected suitable area is projected to decline by ~45.9% to 231,377 km 2 (~18.1%). This loss, resulting from land conversion with the expansion of agricultural frontiers and fire events, highlights a mismatch in current regional conservation priorities, overlooking the needs of the Cerrado and its associated biodiversity. Given ongoing land‐use change and that 58% of remaining native vegetation occurs on private lands, this mismatch highlights the urgent need to align conservation and agricultural policy. Functional trait analyses revealed a clear gradient from acquisitive “fast” to conservative “slow” strategies, reflecting trade‐offs in water‐use efficiency and biomass allocation, with leaf structural and reproductive traits best predicting species resilience to climate change. Our results indicate that a small subset of hyperdominant species not only forms current community structure but also signals the biome's resilience/vulnerability to climate change. Conservation planning should prioritize identified climate refuges and be based on functional traits to buffer the loss of functional and structural integrity in one of the world's richest and most threatened savanna ecosystems.

Forest residue removal undermines soil health and micronutrient transfer to trees, compromising sustainable productivity of Eucalyptus plantations - Antonio L. Florentino; Nariane de Andrade; Nikolas S. Mateus; Bruna E. Schiebelbein; Adam C. Rodrigues; Liamara S. Masullo; Alexandre V. Ferraz; Eduardo Mariano; Fernando D. Andreote; Carlos E.P. Cerri; Maurício R. Cherubin; Timothy R. Filley; et al. (Soil and Tillage Research, 2026)

Effects of concentrate levels with or without protected fat on intake, digestibility, microbial protein synthesis, and performance in feedlot lambs - Cláudia Loianny Souza Lima; Douglas dos Santos Pina; Henry Daniel Ruiz Alba; Maria Leonor Garcia Melo Lopes de Araújo; Susiane de Carvalho Matos; Luis Fernando Batista Pinto; José Esler de Freitas Júnior; Manuela Silva Libânio Tosto; José Augusto Gomes Azevedo; Stefanie Alvarenga Santos; Carlindo Santos Rodrigues; Gleidson Giordano Pinto de Carvalho (Small Ruminant Research, 2026)

Determinants of L-band backscatter in dry tropical ecosystems: Implications for biomass mapping - João M.B. Carreiras; Thomas Higginbottom; John L. Godlee; Sam Harrison; Lorena Benitez; Penelope J. Mograbi; Aurora Levesley; Karina Melgaço; David Milodowski; Georgia Pickavance; Geoff Wells; Edmar Almeida de Oliveira; et al. (Remote Sensing of Environment, 2026)

Origin, viability, and cell cycle status of seminal somatic cells for potential application in cattle cloning via nuclear transfer - Higor da Silva Ferreira; Gabriella Borba de Oliveira; Eduardo de Oliveira Sanguinet; Ana Laura da Silva Feijó; César Augusto Pinzón-Osorio; Verônica Rafaela Benvenutti; Louise Fontoura Köhler; Marianna Bertolini; Fernando Almeida-Souza; Felipe de Jesus Moraes Junior; David Driemeier; Ana Lúcia Abreu-Silva; et al. (Reproductive Biology, 2026)

Risk-based inspection framework for outer hull of floating units based on the integration of inspection programs - Edilson Gabriel Veruz; Renan Favarão da Silva; Gilberto Francisco Martha de Souza; Fernando Andrade Rodrigues (Ocean Engineering, 2026)

Performance analysis and geometric evaluation of galvanized T- and Y-Shapes for earth-air heat exchangers using constructal design - Ana M.B. Domingues; Andre L. Razera; Jairo V.A. Ramalho; Michel K. Rodrigues; Honório J. Fernando; Liércio A. Isoldi; Elizaldo D. dos Santos (Geothermics, 2026)

Alcohol exposure during pregnancy and its impact on fetal neurodevelopment: a bibliometric and scientific mapping analysis - Paulo Fernando Santos Mendes; Julia Karine Miranda Rodrigues; Pedro Anibal Cardoso Barros; Wallacy Watson Pereira Melo; Thaís Pereira Torrres-Magno; Rafael Rodrigues Lima; Luanna Melo Pereira Fernandes (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Evaluation of the stability of concentrate feed stored in metallic silos under farm conditions in Brazil - Tiago Bordin; Elisangela Vilas Boas; Pedro Henrique Ferreira da Silva; Luciane Maria Colla; Fernando Pilotto; Laura Beatriz Rodrigues (Journal of Consumer Protection and Food Safety, 2026)
Maintaining the nutritional quality of stored concentrates is crucial for the health and productivity of dairy herds, particularly in tropical climates where high temperatures can accelerate feed degradation. This study aimed to monitor the effects of temperature and humidity variations on the quality of pelleted concentrate feed in steel silos under real-world Brazilian farm conditions during 28-day storage. Three 4-ton steel silos containing concentrate feed for lactating cows were evaluated on a dairy farm in southern Brazil. Internal and external temperature and humidity were recorded continuously. Samples were collected weekly (D0-D28). They underwent bromatological, physicochemical, and microbiological analyses (vitamins A and D3, fatty acids, total aerobic count, and mold/yeast counts). Despite extreme conditions (50 °C, 90% relative humidity) in the steel silos, microbial counts remained stable. However, vitamins A and D3 decreased significantly (233 ± 12 to 132 ± 13.08 µg/100 g dry matter (DM) and 1,577 ± 74 to 929 ± 295 IU/kg DM, respectively; 15–20% loss), while other nutrients remained stable. While metallic silos effectively preserve the quality of bulk feed in the short term, significant thermosensitive nutrient losses occur under tropical conditions. Farmers should align storage durations with seasonal climate patterns and consider protective technologies for vitamins. The findings highlight the need for comparative studies of storage methods and practical solutions tailored to tropical dairy systems, where nutrient preservation directly impacts milk production economics.

Successional agroforestry systems as land use that promote the restoration and conservation of ant assemblages in the Amazon - Dhâmyla Bruna de Souza Dutra; João Pedro Gomes Chaves; Kauã Magalhães; Gabriel Pedrosa; Luane Karoline Fontenele; Camila Braga da Conceição; Icaro Wilker; Carla Rodrigues Ribas; Rodrigo Machado Feitosa; Vitória Brunetta; Cristaianny Nogueira de Oliveira; Fernando Augusto Schmidt (Biodiversity and Conservation, 2026)
Land-use changes, driven by the expansion of agriculture and livestock farming, are one of the main drivers of biodiversity loss in the Amazon region. In this context, Succesional Agroforestry Systems - SAFs, emerge as a potential alternative to reconcile agricultural production with biodiversity conservation and restoration. This study assessed the impact of different land-use types on ant diversity and the composition of habitat-use guilds in areas of primary forest, pastures, shifting cultivation, and SAFs at different ages. The results indicate that primary forests consistently exhibited the highest alpha, beta, and gamma diversity. The community composition also shifted along the land-use gradient, with disturbed areas showing a higher relative representation of generalist and open-area species, while forest specialists were proportionally more represented in primary forests. Old SAFs displayed diversity values and guild composition that were intermediate between primary forests and more intensively managed systems whereas young SAFs more closely resembled pastures and shifting cultivation areas. These findings highlight the importance of SAF age in shaping biodiversity recovery trajectories, suggesting that mature agroforestry systems have the potential to promote the recovery of biodiversity in human-modified landscapes. This study underscores the importance of long-term agroforestry management strategies to promote conservation and ecological restoration, especially in regions of high biodiversity value, such as the Amazon.

Connectivity and Age of Restored Atlantic Forest Fragments Drives Composition and Functionality of the Fungal Community in the Leaf Litter Layer - Guilherme Lucio Martins; Dina in 't Zandt; Luis Fernando Merloti; Wanderlei Bieluczyk; Gabriel Silvestre Rocha; Robert Timmers; Ricardo Ribeiro Rodrigues; Siu Mui Tsai; Wim H. van der Putten (Molecular Ecology, 2026)
The restoration of biodiversity and functional tropical forests is critical to mitigating global biodiversity losses. Aboveground, increasing the connectivity of regenerating forest fragments facilitates the recolonization of tropical forest biodiversity. However, restoring functional ecosystems also requires the recovery of decomposition processes as these are essential in shaping aboveground biodiversity. Therefore, we investigate the role of forest connectivity in restoring the composition and functioning of fungal communities in the leaf litter layer during a chronosequence of forest restoration. In the Brazilian Atlantic Forest, we studied secondary forests regrown between 18 and 55 years after deforestation and different levels of forest connectivity and compared their litter to recently abandoned pastures and undisturbed primary forests. We quantified how forest age and connectivity between fragments influenced the litter fungi composition in relation to tree diversity, litter chemistry and litter isotopes. We show that fungal composition was highly heterogeneous in forest litter, whereas pasture litter exhibited a more homogeneous community. Moreover, forest connectivity had stronger effects on litter fungal composition compared to forest age. Connectivity promoted wood saprotrophs and endophytes, while suppressing soil saprotrophs, with its effects being more evident during later stages of restoration. Fungal guilds such as endophytes and saprophytes were primarily influenced by tree diversity and leaf litter chemistry. We conclude that forest connectivity promotes the re‐establishment of saprophytic fungi capable of decomposing recalcitrant litter substrates, driven mainly by enhancing tree diversity and litter quality. Practical implications of increasing connectivity may relate to forest resilience in front of future climate change scenarios.

Digestible lysine requirement in diets for tambaquis (Colossoma macropomum) in growth phase from 100 g to 500 g - Andressa Tellechea Rodrigues; Magdiel Santos Oliveira; Denis William Johansem de Campos; Jesaias Ismael da Costa; Cleber Fernando Menegasso Mansano; Dalton José Carneiro (Aquaculture, 2026)

In Silico, in vitro, and in vivo studies of a 2-substituted quinazolin-4(3H)-one in T-cell acute lymphoblastic leukemia - Giorgio Antoniolli; Gilberto Carlos Franchi Junior; Keli Lima; Rayssa de Mello Lopes; Euzebio Guimarães Barbosa; João Agostinho Machado-Neto; Carmen Silvia Passos Lima; Tiago Rodrigues; Fernando Coelho (Toxicology and Applied Pharmacology, 2026)

Chemical characterization, toxicity and involvement of calmodulin in the antithrombotic activity of Rosmarinus officinalis L. essential oil - Kalynca Kayla Viana Aragão; Railson Pereira Souza; Silvia Letícia Maciel Barbosa; Enedina Rodrigues da Silva Neta; Lorranya Éveli Pereira Feitosa Araújo; Alyne Pereira Lopes; Heron Silva Soares; Emerson Portela Sena; Pedro Simão da Silva Azevedo; Benedito Pereira de Sousa Neto; Daniel Fernando Pereira Vasconcelos; Maria José dos Santos Soares; et al. (South African Journal of Botany, 2026)

Advancing eutrophication mitigation through nature-based and hybrid solutions: A systematic review - Rafaela R. Morelato; Fernando Rodrigues-Silva; Guenther Carlos C. Viana; Camila C. Amorim (Journal of Environmental Chemical Engineering, 2026)

Suboptimal responses to E2/P4-based timed AI protocols compromise pregnancy outcomes in fertile beef cattle: Roles of ovulation timing and semen viability - César Augusto Pinzón-Osorio; Thomaz Kranen Cunha; German Holguin-Sanabria; Marco Alves Machado; Favorino José de Freitas Collares; Luís Henrique de Aguiar; Paula Rodriguez-Villamil; Felipe Ledur Ongaratto; Eduardo Pradebom da Silva; Eduardo de Oliveira Sanguinet; Carolina Silveira da Silva; Daiane Mentz; et al. (Animal Reproduction Science, 2026)

Correction: Amphotericin B-Loaded Bigel: Characterization and in vivo Antileishmanial Evaluation in BALB/c Mice Infected with Leishmania amazonensis - Rosilene Ribeiro de Sousa; Matheus Oliveira do Nascimento; Leandro Josuel da Costa Santos; Francisco Gesley de Sousa Abreu; André Luiz Pinheiro de Moura; Daniele Costa Lopes; Karla Germana dos Reis Bacelar; Rita de Cássia Vianna de Carvalho; Paulline Paiva Mendes de Souza Leal; Charllyton Luis Sena da Costa; Vitória de Cássia Coelho Rodrigues; Fernando Aécio de Amorim Carvalho; et al. (AAPS PharmSciTech, 2026)

Amphotericin B-Loaded Bigel: Characterization and in vivo Antileishmanial Evaluation in BALB/c Mice Infected with Leishmania amazonensis - Rosilene Ribeiro de Sousa; Matheus Oliveira do Nascimento; Leandro Josuel da Costa Santos; Francisco Gesley de Sousa Abreu; André Luiz Pinheiro de Moura; Daniele Costa Lopes; Karla Germana dos Reis Bacelar; Rita de Cássia Vianna de Carvalho; Paulline Paiva Mendes de Souza Leal; Charllyton Luis Sena da Costa; Vitória de Cássia Coelho Rodrigues; Fernando Aécio de Amorim Carvalho; et al. (AAPS PharmSciTech, 2026)

In vitro and in silico evaluation of the anti-leishmania activity of synthetic chalcones - Fernando Ferreira Leite; Luis Cezar Rodrigues; Bruno Hanrry Melo de Oliveira; Gabrielly Diniz Duarte; Maria Denise Leite Ferreira; Natália Ferreira de Sousa; Shayenne Eduarda Ramos Vanderley; Leonardo Lima Cardoso; Tatjana Souza Lima Keesen; Rodrigo Santos Aquino de Araújo; Luciana Scotti; Marcus Tullius Scotti; et al. (Natural Product Research, 2026)

High-intensity ethanol binge drinking pattern in adolescence induces long-lasting impairment in the salivary glands and saliva quality of rats - José Mário Matos-Sousa; Wallacy Watson Pereira Melo; Vinicius Ruan Neves dos Santos; Cristian dos Santos Pereira; Paulo Fernando Santos Mendes; Flávia Letícia Magalhães Lemos; João de Jesus Viana Pinheiro; Luanna de Melo Pereira Fernandes; Cristiane do Socorro Ferraz Maia; Antônio Hernandes Chaves-Neto; Rafael Rodrigues Lima (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Toward Ocean Model-Driven Robotic Exploration - Renato Mendes; Ana Duarte; Leonardo Azevedo; Lucrezia Bernacchi; João Borges de Sousa; João Pereira; Bernardo Gabriel; João Bogas; Marina Cunha; Clara Rodrigues; Ajit Subramaniam; Fernando Esteves; et al. (Oceanography, 2026)
This interdisciplinary work demonstrates the viability of coupling ocean models with in situ robotic sampling in a dynamic coastal region as a means to increase model skill and prediction. Model-driven exploration closes the sample-assimilate-​predict-direct loop within a virtuous cycle to refine prediction for a range of applications in a region characterized by harsh conditions, high variability, and diverse physical forcings, including bathymetry and coastal topography. By exploring the feasibility of coupling high-resolution autonomous underwater vehicle (AUV) sampling and data assimilation with a geostatistical model in a continuous loop, we aim to provide a new approach to understanding coastal dynamics and processes, while using modest computational resources. The novelty of this effort is threefold: the demonstration of coupling models with AUV sampling, the importance of targeted sampling, and the impact of loop closure toward model prediction.

Human impact on the frozen continent: Anthropogenic debris in a coastal Antarctic ecosystem - Fernando Augusto Bertazzo-Silva; Flavia Helena Aires Sousa; Jorge Renato Pinheiro Velloso; Kamille Rodrigues Ferraz; Alice Lemos Costa; Carlos Ernesto Gonçalves Reynaud Schaefer; Jair Putzke (Regional Studies in Marine Science, 2025)

Limited role of urban parks in frog diversity conservation - Débora Damianus Antunes Dal Fabbro; Fernando Rodrigues da Silva (Journal for Nature Conservation, 2025)

Enhancing “Campos” grassland productivity by improving soil fertility and overseeding: A meta-analysis - João Pedro Moro Flores; Dionata Filippi; Lucas Aquino Alves; Gustavo Pesini; Leandro Bittencourt de Oliveira; Geraldo José Rodrigues; Carlos Nabinger; Fernando Luiz Ferreira De Quadros; Tales Tiecher (Geoderma Regional, 2025)

Beet leaves after in vitro human gastrointestinal digestion present antioxidant capacity and protective effects in colorectal cancer cells - Luis Gustavo Saboia Ponte; Beatriz Terui Milanezi; Izabella Batista Barbosa; Isadora Carolina Betim Pavan; Ana Paula Morelli; Mariana Camargo Silva Mancini; Luiz Guilherme Salvino da Silva; Jessica Freire Feitor; Aline Teixeira do Brasil Morais; Daniel Rodrigues Cardoso; Maria Teresa Bertoldo Pacheco; Adriane Elisabete Costa Antunes; et al. (Food Research International, 2025)

Consumer profile and quality monitoring of the honey and honey like products commercialized in the mesoregion of Western Santa Catarina - Patrícia Paula Resmini; Débora Laís Haupenthal; Kaliane Eduarda Kronbauer; Maíra Amélia Mafessoni Herpich; Maria Victoria Martins Rodrigues; Fernando Zuchello; Rúbia Mores (Food and Humanity, 2025)

Catastrophic wildfires in the Pantanal wetlands as catalysts for transformative change - Alexandre de Matos Martins Pereira; Geraldo Alves Damasceno-Junior; Renata Libonati; Liana O. Anderson; Allan Henrique de Almeida Souza; Bruno Henrique dos Santos Ferreira; Andre Valle Nunes; André Luiz Siqueira; Angelica Guerra; Angelo Cipriano Pacelli Rabelo; Arnaud L.J. Desbiez; Arthur Henrique Leite Falcette; et al. (Environmental Science & Policy, 2025)

Ashes of governance: Brazil’s 2024 wildfire crisis and its implications - Ronan Adler Tavella; Fernando Rafael de Moura; Flavio Manoel Rodrigues da Silva Júnior (Regional Environmental Change, 2025)

Multiomic insights into sucrose accumulation in sugarcane - Alexandre Hild Aono; Ricardo José Gonzaga Pimenta; Jéssica Faversani Diniz; Marishani Marin Carrasco; Guilherme Kenichi Hosaka; Fernando Henrique Correr; Ana Letycia Basso Garcia; Estela Araujo Costa; Alisson Esdras Coutinho; Luciana Rossini Pinto; Marcos Guimarães de Andrade Landell; Mauro Alexandre Xavier; et al. (Plant Molecular Biology, 2025)

Subtle morphological and behavioral differentiation in workers of a ponerine ant, Odontomachus chelifer (Hymenoptera: Formicidae) - Ingrid de Carvalho Guimarães; Márlon César Pereira; Poliana Galvão dos Santos; Candida Anitta Pereira Rodrigues; Sidnei Eduardo Lima-Junior; William Fernando Antonialli-Junior (Journal of Insect Behavior, 2025)

Annexin A1 is crucial during Toxoplasma gondii infection promoting the modulation of inflammation and intestinal and central nervous system barrier functions - Rayane Aparecida Nonato Rabelo; Rafaela das Dores Pereira; Natalia Fernanda de Melo Oliveira; Samuel Luiz Teixeira Porto; César Luís Nascimento Barbosa; Livia Fernanda Dias Santana; Fernando Bento Rodrigues Oliveira; Mayra Fernanda Ricci; Celso Martins Queiroz-Junior; Cínthia Firmo Teixeira; Vivian Barbosa Santos Alvarenga; Luiza Pinheiro Silva; et al. (Inflammation Research, 2025)

Diversity of grass-associated Nitrospirillum and proposal of six novel species - Jerri Edson Zilli; Stefan Schwab; Natália dos Santos Ferreira; Veronica Massena Reis; Alberto Fernandes de Oliveira Junior; Jean Luiz Simões-Araujo; Luis Henrique de Barros Soares; Fernanda dos Santos Dourado; Evelise Bach; Luiz Fernando Wurdig Roesch; Carolina Nachi Rossi; Karinne Motta de Oliveira Lima de Souza; et al. (Brazilian Journal of Microbiology, 2025)

Mangaba ( hancornia speciosa ): exploring potent antifungal and antioxidant properties in lyophilised fruit pulp extract through in vitro analysis - Victor Hugo Nosella Sá Barreto; Camila Medeiros da Silva Mazzeti; Bruna Magusso Rodrigues; Hellika Simões de Souza; Arianne Dias Correa; Milena de Almeida Mello; Caio Fernando Ramalho de Oliveira; Janaina de Cássia Orlandi Sardi; Claudia Andrea Lima Cardoso; Fabiane La Flor Ziegler Sanches; Maria Ligia Rodrigues Macedo; Elisvânia Freitas dos Santos; et al. (Natural Product Research, 2025)

Letter to the Editor Regarding the Article “Open Air Quality Data Platforms for Environmental Health Research and Action” - Fernando Rafael de Moura; Dayane Florentino Ferreira de Moura; Ronan Adler Tavella; Flavio Manoel Rodrigues da Silva Júnior (Current Environmental Health Reports, 2025)

White lab coat syndrome in dogs: Owners’ perception - Anna Julia Bessa Fernandes; Debora Azevedo Borges; Isabelle Vilela Bonfim; Fernando Rocha Miranda; Fernanda da Silva Freitas Campos; Clara Rodrigues Dutra; Ingrid Lins Raquel De Jesus; Taynara Monsores Silva; Yara Peluso Cid (Journal of Veterinary Behavior, 2025)

Climate change will boost the invasion of the harmful cyanobacterium Raphidiopsis raciborskii in South America - Felipe Morais Zanon; Bruno Henrique Mioto Stabile; Beatriz Melissa Campos; Érica Oliveira de Lima; Matheus Juan Alarcon Sampaio; Yasmin Rodrigues de Souza; Leonardo Rodrigues Tolardo; Mayra Koma Gomes; Luddy Searom Carias de Moraes; Gabriela Sponchiado Hein; Jaqueline Dantas da Silva; Larissa da Silva Pinha; et al. (Harmful Algae, 2025)

Sustainable aqueous extraction of Brazilian varieties avocado oil: Effects on yield, physical and chemical properties, fatty acids and Triacylglycerols - Diego Fernando García-Ramón; Joanna Cios; Maria Eduarda Machado Soares; João Pedro Fernandes de Sant'Ana; Juliane Viganó; Christianne Elisabete da Costa Rodrigues; Caroline West; Alessandra Lopes de Oliveira (Food Chemistry, 2025)

Skeletal muscle fibers, carcass yield and feed efficiency in native Pantaneiros lambs: a biotype characterization study - Agda Costa Valério; Tatiane Fernandes; Adrielly Lais Alves da Silva; Renata Alves Chagas; Ariadne Patrícia Leonardo; Marcio Rodrigues de Souza; Núbia Michelle Vieira da Silva; Fernando Miranda de Vargas Junior (Tropical Animal Health and Production, 2025)

Substituting grass hay and ground corn with forage cactus genotypes on mineral status of lambs - Luiz Carlos Leal Torres; Tomás Guilherme Pereira da Silva; Ricardo Alexandre Silva Pessoa; Roberto Germano Costa; Daurivane Rodrigues Sousa; Ângela Maria Vieira Batista; Diana Valadares Pessoa; Ihasmyn dos Santos Nunes; Ana Paula Silveira Paim; Dorgival Morais de Lima Júnior; Pierre Castro Soares; Francisco Fernando Ramos de Carvalho (Tropical Animal Health and Production, 2025)

Salinity-driven habitat use of marine-estuarine batoids on the Amazon Coast - Ana Rita Onodera Palmeira-Nunes; Ricardo de Souza Rosa; Jorge Luiz Silva Nunes; Nivaldo Magalhães Piorski; João Braullio de Luna Sales; Jamerson Aguiar Santos; Ana Paula Barbosa Martins; Rachel Ann Hauser-Davis; Getulio Rincon; Keyton Kylson Fonseca Coelho; Luís Fernando Rodrigues-Filho; Natascha Wosnick (Environmental Biology of Fishes, 2025)

Myiasis-causing flies in anurans: new interactions, geographic distribution, and an updated list of records in the Neotropics - Franciele Cristina de Souza; Victor Morais Ghirotto; Alexandre Polletini Neto; Camila Saraiva dos Anjos; André Luís F. da Silva; Rodrigo Lingnau; Emeline da S. Ceccon; Cátia Antunes de Melo-Patiu †; Mirco Solé; Silionamã P. Dantas; Claudio Borteiro; Domingos de J. Rodrigues; et al. (Biologia, 2025)

Environmental factors influence in vitro embryo production of Gir cattle - Lethissia Amorim da Silva Coelho; Rondineli Pavezzi Barbero; Marco Roberto Bourg de Mello; Jaime Araujo Cobuci; Fernanda Santos Silva Raidan; Luiz Fernando Rodrigues Feres; Elisandra Lurdes Kern (Theriogenology, 2025)

Coal facies of the Olmos Formation in the Sabinas Basin, Northeastern Mexico - Genaro de la Rosa-Rodríguez; Juan Josué Enciso-Cárdenas; Cristina Fernanda Alves Rodrigues; Manuel João Lemos de Sousa; Luis Fernando Camacho Ortegón; Eduardo González-Partida; Yuriko Yarel Bueno Yamamoto (Journal of South American Earth Sciences, 2025)

Effects of floating macrophytes on open-water evaporation in a Brazilian tropical reservoir - Italo Sampaio Rodrigues; Carlos Alexandre Gomes Costa; Adunias dos Santos Teixeira; Iran Eduardo Lima Neto; Fernando Bezerra Lopes; José Carlos de Araújo (Journal of South American Earth Sciences, 2025)

Plant community and fine-root growth under preserved and passively restored Cerrado sites in southeast Brazil - Lucas de Camargo Reis; Marisa de Cássia Piccolo; George Rodrigues Lambais; Guilherme Furlan; Fernando Guerra; Plínio Barbosa de Camargo; Wanderlei Bieluczyk (Journal of Environmental Management, 2025)

Whey protein and probiotic supplementation ameliorates DSS-induced colitis in mice - Amanda Ascanio; Jaqueline Cristina Galiardo; Eliane Vale da Silva; José Antônio Sampaio Zuanon; Luis Carlos Spolidorio; Letícia de Aquino Penteado; Priscila Marques Firmiano Dalle Piagge; José Fernando Rinaldi de Alvarenga; Alexandra Ivo de Medeiros; Daniel Rodrigues Cardoso; Daniela Cardoso Umbelino Cavallini (International Dairy Journal, 2025)

Recovery of below-ground associations in restored Brazilian Atlantic Forest - Luis Fernando Merloti; Raúl Ochoa-Hueso; Dina in 't Zandt; G.F. (Ciska) Veen; Wanderlei Bieluczyk; Ricardo Ribeiro Rodrigues; Lucas William Mendes; Siu Mui Tsai; Wim H. van der Putten (Applied Soil Ecology, 2025)

Correction: Distributional projections of an Amazonian fish in native and non-native watersheds of South America in response to climate change - Vitor Gois Ferreira; Eliezer de Oliveira da Conceição; Tatiane Mantovano; Rejane Guimarães Melo; Jonathan Rosa; Ana Paula dos Santos Bertoncin; Leidiane Pereira Diniz; Leonardo Antunes Pessoa; Marcelo Henrique Schmitz; Rafaela Giacomel Rauber; Rosana Müller Padilha Feitosa; Vanessa Ernandes de Amo; et al. (Biological Invasions, 2025)

Description and Patterns of Hyperostosis in Plata Pompano, Trachinotus marginatus Cuvier, 1832 - Alice Miranda Cardoso de Sá; Márcia Carolina Salomão; Helena Passeri Lavrado; Wilson Thadeu Valle Machado; Ana Paula de Castro Rodrigues; Fernando Augusto Pereira Tuna (Journal of Fish Diseases, 2025)
This study describes the occurrence of hyperostosis, to the best of our knowledge, for the first time in Trachinotus marginatus Cuvier 1832 and examines its patterns in 21 specimens from Rio de Janeiro, Brazil. Radiographic images revealed the presence of the condition in 76.2% of the individuals, affecting five distinct bone regions: supraoccipital (76.2%), dorsal‐fin pterygiophore (52.3%), anal‐fin pterygiophore (9.5%), rib (4.8%) and hemal spine (4.8%). Hyperostosis was consistently observed in the first dorsal pterygiophore and was not found in the other dorsal pterygiophores. A directional linearity was noted in the growth of the supraoccipital crest in the cranial region as the sexual maturation of individuals progressed, demonstrating a tendency for bone expansion. Although hyperostosis is a species‐specific condition, the studied species did not exhibit a clear relationship between specific bone region patterns and the total length of the individual, suggesting no progression in the same affected regions as the animal grows. Longitudinal histological sections of the supraoccipital and ribs revealed high bone porosity caused by hyperostosis, with the presence of several vascular channels. This study represents the first report of the condition of this species, which is an important resource for artisanal fishing in southern Brazilian waters.

Removal of toxic metals in contaminated water by adsorption using filters with a combination of nanomaterial and biomass - Luma Rodrigues Blanc; Luiz Fernando Oliveira Maia; Cristiano Agenor Oliveira de Araújo; Camila Neves Lange; Bruno Lemos Batista; Jairo Lisboa Rodrigues (Environmental Monitoring and Assessment, 2025)

Acid-modified titanate nanotubes for enhanced photocatalytic removal of contaminants of emerging concern in water - Guenther Carlos C. Viana; Djalma L.S. Maia; Daniel A.S. Rodrigues; Lara Fabian S. Ribeiro; Italo O. Mazali; Fernando Rodrigues-Silva; Maria Clara V.M. Starling; Thiago A. Neves; Camila C. Amorim (Journal of Water Process Engineering, 2025)

Microstructures and deformation mechanisms of mass transport-related, soft-sediment folds - Clara Costa Polanski; Barbara Trzaskos; Mérolyn Camila Naves de Lima Rodrigues; Fernando Farias Vesely (Journal of Structural Geology, 2025)

In vitro effects of the new antifungal compound manogepix (APX001) against the three most clinically relevant species of Sporothrix - Fernando Almeida-Silva; Fernanda Praça Nogueira Marques; Pedro Henrique Tenório-Alvarenga; Vanice Rodrigues Poester; Melissa Orzechowski Xavier; Rosely Maria Zancopé-Oliveira; Rodrigo Almeida-Paes (Brazilian Journal of Microbiology, 2025)

Fertilization with fermented composts improves agroeconomic performance and sustainability in organic lettuce and forage sorghum cropping systems in Northwestern Minas Gerais, Brazil - Ana Amélia dos Santos Cordeiro; Luiz Fernando de Sousa Antunes; Giulia da Costa Rodrigues dos Santos; José Guilherme Marinho Guerra; Ricardo Luiz Louro Berbara; Ednaldo da Silva Araújo; José Antonio Azevedo Espindola (Organic Agriculture, 2025)

Distributional projections of an Amazonian fish in native and non-native watersheds of South America in response to climate change - Vitor Gois Ferreira; Eliezer de Oliveira da Conceição; Tatiane Mantovano; Rejane Guimarães Melo; Jonathan Rosa; Ana Paula dos Santos Bertoncin; Leidiane Pereira Diniz; Leonardo Antunes Pessoa; Marcelo Henrique Schmitz; Rafaela Giacomel Rauber; Rosana Müller Padilha Feitosa; Vanessa Ernandes de Amo; et al. (Biological Invasions, 2025)

Critical analysis of sewage sludge-based organomineral fertilizers through a bibliometric perspective - Mayra Maniero Rodrigues; Douglas Gomes Viana; Rafael Santana Mendonça; Gian Franco Capra; Fernando Carvalho Oliveira; Luis Fernando Vieira da Silva; Thiago Assis Rodrigues Nogueira; Jussara Borges Regitano (Environment, Development and Sustainability, 2025)

Efficacy of Platelet and Leukocyte Rich Fibrin (L-PRF) in the healing process and bone repair in maxillary sinus lift surgeries: a systematic review - Élio Hitoshi Shinohara; Ilan Hudson Gomes de Santana; Mayara Rebeca Martins Viana; Edmundo Junio Rodrigues de Almeida; Anderson Jara Ferreira; José Marcos Pereira Júnior; Arthur Felipe de Brito Andrade; Fernando Kendi Horikawa; Eduardo Dias Ribeiro (Cell and Tissue Banking, 2025)

Three new quinones from Senna pluribracteata (Fabaceae) and investigation of their bioactivity in BV-2 microglial cells - Ranna Beatris de Lima Souza; Ana Rita Rodrigues de Almeida Silva Brilhante; Marianna Vieira Sobral; Paulo Bruno Araujo Loureiro; Geraldo Moisés Wanderley Amorim; Maria de Fátima Agra; Ana Carolina Ferreira de Albuquerque; Fernando Martins dos Santos Junior; Marcelo Sobral da Silva; Raimundo Braz-Filho; Josean F. Tavares (Natural Product Research, 2025)

Basalt rock dust as a soil remineralizer in upland rice grown in tropical soils: residual effects on soil fertility, Si availability, and leaf anatomy - Mariana de Carvalho Ribeiro; Aline Redondo Martins; Rodrigo Silva Alves; Luís Gustavo Frediani Lessa; Hamilton Seron Pereira; Fernando Shintate Galindo; Marcelo Carvalho Minhoto Teixeira Filho; Cassio Hamilton Abreu–Junior; Arun Dilipkumar Jani; Gian Franco Capra; Antonio Ganga; Thiago Assis Rodrigues Nogueira (Journal of Cleaner Production, 2025)

A novel zooplankton-based environmental monitoring tool for coastal impacted areas: The case of the Doce River dam rupture - Gustavo Martins Rocha; Bianca Salvador; Gabriel Harley Costa Santos; Laura Rodrigues da Conceição; Priscila Teixeira-Amaral; Maikon Di Domenico; Diego de Arruda Xavier; Eduardo Schettini Costa; Renata Caiado Cagnin; Cesar Alexandro da Silva; Mayara Bandeira; Mônica de Souza Mendes; et al. (Estuarine, Coastal and Shelf Science, 2025)

Typologies for ecosystem accounting for the Brazilian Pantanal - Fernando Rodrigues Teixeira Dias; Catia Urbanetz; Pedro R. Andrade (Wetlands Ecology and Management, 2025)

Accuracy of inspection surveillance in detecting bovine tuberculosis during slaughter in Rio Grande do Sul - Jerônimo Miguel Vicenzi; Cristine Cerva; Fernando Sérgio Castilhos Karam; Lucas Brunelli de Moraes; Rogério Oliveira Rodrigues; Priscilla Lucas Oliveira; Angélica Cavalheiro Bertagnolli; Fabiana Quoos Mayer (Veterinary Research Communications, 2025)

Determinants of Cyanobacteria and Algae Diversity in Natural Freshwater Micro‐Ecosystems - Yasmin Rodrigues de Souza; Beatriz Melissa Campos; Fernando Miranda Lansac‐toha; Annika Busse; Jana S. Petermann; Gustavo Quevedo Romero; Pablo Augusto Poleto Antiqueira; Luzia Cleide Rodrigues (Environmental Microbiology, 2025)
In this context, estimating the contributions of single sites to overall beta diversity (LCBD—Local Contribution to Beta Diversity, i.e., indicator of site's ecological uniqueness) or partitioning overall beta diversity into contributions of individual species (SCBD—Species Contribution to Beta Diversity, i.e., degree of variation of individual species across the study area) has proven to be a good approach to improve the knowledge of drivers of beta diversity. The number of studies on beta diversity in hyperdiverse environments, such as the Neotropics, is still scarce. We explored the contributions of each site and species to the overall cyanobacteria and algae beta diversity of 77 natural freshwater micro‐ecosystems (i.e., tank bromeliads) of a neotropical ecosystem. We observed that LCBD was negatively related to Shannon diversity, turbidity and luminosity (% canopy cover). The negative relationship between LCBD and Shannon diversity indicates that micro ecosystems with less diversity reflect unique characteristics, and LCBD values can predict these environments. In our study, high LCBD values indicated environments in need of restoration, that is, poor in species richness and with greater turbidity and luminosity, showing that most bromeliad tanks presented high species diversity and low turbidity and luminosity.

Yellow mealworm beetle (Tenebrio molitor) larvae as an alternative model for antileishmanial drug evaluation - Michel Muálem de Moraes Alves; Victoria Hannah Araújo de Almeida Passos; Paulline Paiva Mendes de Souza Leal; Pastora Pereira Lima Neta; Bianca Soriano dos Anjos; Boris Timah Acha; Jose Moreira Tavares Neto; José Otávio Carvalho Sena de Almeida; Leonardo da Rocha Sousa; Daniel Dias Rufino Arcanjo; Klinger Antonio da Franca Rodrigues; Fernando Aécio de Amorim Carvalho; et al. (Veterinary Parasitology, 2025)

Droughts, livestock expansion, and Forest degradation: A 37-year assessment of landscape change in a semiarid municipality of Brazil - Francisco Éder Rodrigues de Oliveira; Eveline de Almeida Ferreira; Rodrigo Fernandes; Victor Neudo Santos Tavares; Yara de Almeida Araújo; João Luiz Lima; Luiz Fernando de Sousa Antunes; Noely Raiana da Costa Chagas; Pedro Lucas Nogueira de Freitas; Cirley Tavares Lemos; Ayslan do Nascimento Fernandes; Eulene Francisco da Silva (Science of The Total Environment, 2025)

Evaluation and calibration of MERRA-2 and CAMS reanalysis for PM2.5 in a semi-urbanized area in the south of the Amazon - Danielle Nassarden; Jorge Menezes; Carlos Barbosa Pessoa; Anderson Carneiro; Luiz O. F. dos Santos; Glauber Cirino; Breno Imbiriba; Fernando Sallo; Leone F. A. Curado; Thiago R. Rodrigues; João Basso; Marco A. Franco; et al. (Air Quality, Atmosphere & Health, 2025)

Comparisons of Hyperostotic Bones in Two Species of the Genus Oligoplites Gill, 1863 in the Southern Brazilian Coast - Fernando A. P. Tuna; Ana Paula C. de Rodrigues; Gustavo P Filgueira; Rebeca s da Bianca; Wilson T. V. Machado; Márcia C. Salomão; Helena P. Lavrado (Journal of Fish Diseases, 2025)
The description of skeletal disorders is commonly reported in fish species raised through aquaculture; however, wild marine fish may also exhibit high frequencies of anomalies, particularly the development of hyperostosis, a condition that causes thickening of the bones. Specimens of Oligoplites saliens ( n = 15) and Oligoplites palometa ( n = 14) were radiographed to verify hyperostotic bone occurrences. Hyperostosis was detected in all individuals (> 400 mm TL) analysed for both species, occurring in six distinct regions of the skeleton (supraoccipital bone, cleithrum, dorsal pterygiophores, anal pterygiophore, haemal spines, and neural spines), regardless of the sex of the individuals. No hyperostosis was found in the neural and haemal spines of O. palometa and in the anal pterygiophore of O. saliens . Histological sections of the supraoccipital bone of O. saliens were conducted, revealing high porosity characterised by the presence of vascular channels in bones with hyperostosis. The species exhibited species‐specific patterns for the condition, demonstrating differences even among species of the same genus occurring in the same geographic area. This is the first record of hyperostosis for both species in Brazilian waters.

Dynamic ion-releasing biomaterials actively shape the microenvironment to enhance healing - Willian Fernando Zambuzzi; Marcel Rodrigues Ferreira (Journal of Trace Elements in Medicine and Biology, 2025)

Novel insights into the association between Leptogium puberulum (Ascomycota) and Deschampsia antarctica (Poaceae): implications for plant–lichen dynamics in Antarctica - Fernando Augusto Bertazzo-Silva; Jair Putzke; Antonio Batista Pereira; Cassiane Furlan-Lopes; Alice Lemos Costa; Kamille Rodrigues Ferraz; Ana Luiza Klotz-Neves; Carlos Ernesto Gonçalves Reynaud Schaefer (Polar Biology, 2025)

Genetic insights into non-additive effects in tetraploid potato breeding - Luciana Aparecida Miguel; Rafaela Pereira Carvalho; Roberto Henrique de Lima Ribeiro; Mayra Alejandra Rincón Rueda; Ivan David Briceño-Pinzón; Lucimara Cruz de Souza; Vinicius Samuel Martins; Leticia Novais Padua; José Airton Rodrigues Nunes; Pedro Crescêncio de Souza Carneiro; Mário Henrique Murad Leite Andrade; Márcio Fernando Ribeiro Resende; et al. (Euphytica, 2025)

Amazon’s climate crossroads: analyzing air pollution and health impacts under machine learning-based temperature increase scenarios in Northern Mato Grosso, Brazil - Fernando Rafael de Moura; Romina Buffarini; Edison Luis Devos Barlem; Willian Cézar Nadaleti; Helotonio Carvalho; Flávio Manoel Rodrigues da Silva Júnior (Environmental Geochemistry and Health, 2025)

Development of a computational deep learning model for detecting people in aerial images and videos degraded by compression artifacts - Fernando Rodrigues Trindade Ferreira; Loena Marins do Couto (Earth Science Informatics, 2025)

Mass spectrometry-based identification reveals the polymicrobial nature of canine urinary tract infections - Natália Rodrigues Paschoal; Fábio Vinícius Ramos Portilho; Beatriz Oliveira de Almeida; Marcelo Fagali Arabe Filho; Carolina Aparecida Rodrigues; Thaís Spessotto Bello; Patrik Júnior de Lima Paz; Fernando José Paganini Listoni; Márcio Garcia Ribeiro (Brazilian Journal of Microbiology, 2025)

Modeling the adsorption of ciprofloxacin on magnetic biochar: A comparative study of traditional and advanced approaches - Ana Carolina Ferreira Piazzi Fuhr; Daniel Lucas Costa Rodrigues; Júlia Amaral Guido; Cristiane Ferraz de Azevedo; Nicholas Fernandes de Souza; Guilherme Luiz Dotto; Eder Claudio Lima; Fernando Machado Machado (Journal of Water Process Engineering, 2025)

Exploring plant functional traits and their relationship to biomass dynamics in secondary forests in Eastern Amazonia - Luane Botelho; Fernando Elias; Beatriz V. Barbosa; Karoline C. Silva; Vanessa Negrão-Rodrigues; Euciney E.S. Barbosa; Jucelino S. Coutinho; Joice Ferreira; Jos Barlow; Grazielle Sales Teodoro (Flora, 2025)

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

Optimizing bacterial nanocellulose production from eucalyptus bark: A circular approach to wastewater management and resource recovery - Ana Cristina Rodrigues; Daniela Martins; M. Salomé Duarte; Ricardo Silva-Carvalho; Susana Marques; Ana Júlia Cavaleiro; Miguel Gama; Fernando Dourado (Journal of Environmental Chemical Engineering, 2025)

Two-dimensional estimation of service load limit in CLT plates - Guilherme dos Santos Silva; Elvys Dias Reis; Edson Fernando Castanheira Rodrigues; Herisson Ferreira dos Santos; André Luis Christoforo (Engineering Structures, 2025)

Ursolic acid derivatives improved clinical signs of experimental autoimmune encephalomyelitis by modulating central nervous system inflammation - Elaine Carlos Scherrer; Karla Antunes Ramos; Ydia Mariele Valadares; Igor Gabriel Machado Soares; Alessandra Paula Carli; Fernando Sá Silva; Jeferson Gomes Silva; Daniel Gomes Alvarenga; Alessa Sin Singer Brugiolo; Rodrigo Moreira Verly; Maiara Rodrigues Salvador; Angelo Marcio Leite Denadai; et al. (Metabolic Brain Disease, 2025)

Dragonflies (Odonata) as bioindicators of the sustainability of agroforestry systems in the Atlantic Forest - Cíntia Ribeiro; Fernando Geraldo de Carvalho; Fábio de Oliveira Roque; John P. Simaika; Ulisses Gaspar Neiss; Laís Rodrigues Santos; Francisco Maciel Barbosa-Santos; Karolina Teixeira Silva; Marciel Elio Rodrigues (Aquatic Sciences, 2025)

Effects of deforestation on multitaxa community similarity in the Brazilian Atlantic Forest - Daniel Maurenza; Renato Crouzeilles; Jayme Augusto Prevedello; Mauricio Almeida‐Gomes; Marina Schmoeler; Renata Pardini; Cristina Banks‐Leite; Marcus Vinicius Vieira; Jean Paul Metzger; Carlos Roberto Fonseca; Marina Zanin; Alex Fernando Mendes; et al. (Conservation Biology, 2025)
Habitat loss can lead to biotic homogenization (decrease in β diversity) or differentiation (increase in β diversity) of biological communities. However, it is unclear which of these ecological processes predominates in human‐modified landscapes. We used data on vertebrates, invertebrates, and plants to quantify β diversity based on species occurrence and abundance among communities in 1367 landscapes with varying amounts of habitat ( 60% of forest cover) throughout the Brazilian Atlantic Forest. Decreases in habitat amount below 30% led to increased compositional similarity of vertebrate and invertebrate communities, which may indicate a process of biotic homogenization throughout the Brazilian Atlantic Forest. No pattern was detected in plant communities. We found that habitat loss was associated with a deterministic increase in faunal community similarity, which is consistent with a selected subset of species being capable of thriving in human‐modified landscapes. The lack of pattern found in plants was consistent with known variation between taxa in community responses to habitat amount. Brazilian legislation requiring the preservation of 20% of Atlantic Forest native vegetation may be insufficient to prevent the biotic homogenization of faunal communities. Our results highlight the importance of preserving large amounts of habitat, providing source areas for the recolonization of deforested landscapes, and avoiding large‐scale impacts of homogenization of the Brazilian Atlantic Forest.

Assessment of water and sediment quality in intermittent streams across different land uses in the Brazilian semiarid region: implications for sustainable irrigation and resource management - Yara de Almeida Araújo; Eveline de Almeida Ferreira; Rodrigo Fernandes; Gustavo Gonzaga Henry-Silva; Francisco Éder Rodrigues de Oliveira; Victor Neudo Santos Tavares; Jeane Cruz Portela; Marx Lima da Cunha; Noely Raiana da Costa Chagas; Luiz Fernando de Sousa Antunes; Antônio Gustavo de Luna Souto; Eulene Francisco da Silva (Environmental Science and Pollution Research, 2025)

Visual soil assessment as an early indicator of soil quality in the caatinga dry tropical forest under varying degrees of disturbance in the Brazilian semiarid region - Wicliton Wagner de Oliveira Lima; Eulene Francisco da Silva; Diana Ferreira de Freitas; Jeane Cruz Portela; Lunara Gleika da Silva Rêgo; Daniela da Costa Leite Coelho; Eveline de Almeida Ferreira; Joaquim Emanuel Fernandes Gondim; Luiz Fernando de Sousa Antunes; Francisco Éder Rodrigues de Oliveira; Yara de Almeida Araújo; Marx Lima da Cunha; et al. (Science of The Total Environment, 2025)

Soil and climatic conditions determine the rhizobia in association with Phaseolus vulgaris in southern Brazil - Tales Gustavo Ferreto de Araújo; Elisete Pains Rodrigues; Mariangela Hungria; Fernando Gomes Barcellos (Brazilian Journal of Microbiology, 2025)

Gene profile of virulence, antimicrobial resistance and action of enterocins in Campylobacter species isolated from broiler carcasses - Saruanna Millena dos Santos Clemente; Samuel Fernando dos Santos; Priscilla Régia de Andrade Calaça; Maria Taciana Cavalcanti Vieira Soares; Webert Aurino da Silva; Renata Pimentel Bandeira de Melo; Rinaldo Aparecido Mota; Mércia Rodrigues Barros (Brazilian Journal of Microbiology, 2025)

Comparative analysis of marine and agricultural gypsum as nutrient sources: feasibility of marine gypsum as a substitute for acid sandy soils and sodic soil recovery - Maria Valdete da Costa; José Francismar de Medeiros; Eulene Francisco da Silva; Ana Kaline da Costa Ferreira; Paula Romyne de Morais Cavalcante Neitzke; Kelly Kaliane Rego da Paz Rodrigues; Francisco Vanies da Silva Sá; Eveline de Almeida Ferreira; Diana Ferreira de Freitas; Lidiane Araujo Vieira dos Santos; Daianni Ariane da Costa Ferreira; Luiz Fernando de Sousa Antunes (Environmental Science and Pollution Research, 2025)

First validation of the method Visual Evaluation of Soil Structure in coal mining area using a long-term field revegetation experiment as testbed - Otávio dos Anjos Leal; Pablo Miguel; Mateus Fonseca Rodrigues; Rachel Muylaert Locks Guimarães; Luiz Fernando Spinelli Pinto; Thais Palumbo Silva; Marilia Alves Brito Pinto; Stephan Domingues Nachtigall; Lizete Stumpf (Soil and Tillage Research, 2025)

SAmMD: The South American mineral deposit database - Guilherme Ferreira da Silva; Martín Ricardo Gozalvez; Alonso Arturo Marchena; Anderson Dourado Rodrigues da Silva; Braulio Ignacio Aguila Aravena; Diego Jesús Rodriguez; Eduardo Linares; Edwin Fernando Gallardo Vargas; Franco Drausin Pinzon Rivas; Guillermo Lopez Aguilera; Jose Amado Rondon Muñoz; Juan Manuel Turra; et al. (Journal of South American Earth Sciences, 2025)

Impact of land use intensification on key drivers of soil organic carbon pools in Brazil’s Central-West - Priscila Silva Matos; Janaína de Moura Oliveira; Marcia Tais de Melo Carvalho; Beata Emoke Madari; André Luiz Rodrigues da Silveira; Júnior Melo Damian; Pedro Augusto de Oliveira Moraes; Wilker Alves de Araujo; Matheus Mentone de Britto Siqueira; Ryan Rodrigues da Silva; Tatiana Maris Ferraresi; Luis Fernando Stone; et al. (CATENA, 2025)

Hydrocooling as a Preservation Method for Mandacaru Fruit (Cereus jamacaru) - Toshik Iarley da Silva; Anderson dos Santos Formiga; Marcio Santos da Silva; Giuliana Naiara Barros Sales; Antonio Carlos de Sena Rodrigues; Brencarla de Medeiros Lima; Paloma Domingues; Fernando dos Santos Leite; Jordânia de Morais Lúcio; Ronaldo Leite da Silva Filho; Yasmin Jaine Alves de Lucena; Franciscleudo Bezerra da Costa (Journal of Plant Growth Regulation, 2025)

Method to Establish Intense Rainfall Equations Based in Geoprocessing - Laura Thebit de Almeida; Roberto Avelino Cecílio; Fernando Falco Pruski; Gerson Rodrigues dos Santos; Marcel Carvalho Abreu (Environmental Modeling & Assessment, 2025)

Domestic cat hepadnavirus genotype B is present in Southern Brazil - Alaíse Tessmann; Juliana Sumienski; Alexandre Sita; Larissa Mallmann; Gabriela Espíndola Birlem; Nilson Júnior da Silva Nunes; Camila Gottlieb Lupion; Juliana Schaeffer Eckert; Meriane Demoliner; Juliana Schons Gularte; Paula Rodrigues de Almeida; Fernando Rosado Spilki; et al. (Virus Genes, 2025)

LandFrag : A Dataset to Investigate the Effects of Forest Loss and Fragmentation on Biodiversity - Thiago Gonçalves‐Souza; Maurício Humberto Vancine; Nathan J. Sanders; Nick M. Haddad; Lucas Cortinhas; Anne Lene T. O. Aase; Willian Moura de Aguiar; Marcelo Adrian Aizen; Víctor Arroyo‐Rodríguez; Arturo Baz; Maíra Benchimol; Enrico Bernard; et al. (Global Ecology and Biogeography, 2025)
Motivation The accelerated and widespread conversion of once continuous ecosystems into fragmented landscapes has driven ecological research to understand the response of biodiversity to local (fragment size) and landscape (forest cover and fragmentation) changes. This information has important theoretical and applied implications, but is still far from complete. We compiled the most comprehensive and updated database to investigate how these local and landscape changes determine species composition, abundance and trait diversity of multiple taxonomic groups in forest fragments across the globe. Main Types of Variables Contained We gathered data for 1472 forest fragments, providing information on the abundance and composition of 9154 species belonging to vertebrates, invertebrates, and plants. For 2703 of these species, we obtained more than 20 functional traits. We provided the spatial location and size of each fragment and metrics of landscape composition and configuration. Spatial Location and Grain The dataset includes 1472 forest fragments sampled in 121 studies from all continents except Antarctica. Most datasets (77%) are from tropical regions, 17% are from temperate regions, and 6% are from subtropical regions. Species abundance and composition were collected at the plot or fragment scale, whereas the landscape metrics were extracted with buffer size ranging from a radius of 200–2000 m. Time Period and Grain Data on the abundance of species and community composition were collected between 1994 and 2022, and the landscape metrics were extracted from the same year that a given study collected the abundance and composition data. Major Taxa and Level of Measurement The studied organisms included invertebrates (Arachnida, Insecta and Gastropoda; 41% of the datasets), vertebrates (Amphibia, Squamata, Aves and Mammalia; 44%), and vascular plants (19%), and the lowest level of identification was species or morphospecies. Software Format The dataset and code can be downloaded on Zenodo or GitHub.

Potential Mechanisms Underlying COVID-19-Mediated Central and Peripheral Demyelination: Roles of the RAAS and ADAM-17 - Kellysson Bruno Oliveira; Fernanda Maria Araujo de Souza; Letícia Barros Maurício de Sá; Amanda Larissa Dias Pacheco; Mariana Reis Prado; Célio Fernando de Sousa Rodrigues; Ênio José Bassi; Igor Santana-Melo; Abelardo Silva-Júnior; Robinson Sabino-Silva; Ashok K. Shetty; Olagide Wagner de Castro (Molecular Neurobiology, 2025)

Detection of a novel hepacivirus in wild cavies (Cavia aperea aperea) - Gabriela Espíndola Birlem; Alexandre Sita; Juliana Schons Gularte; Deivid de Souza da Silva; Meriane Demoliner; Paula Rodrigues de Almeida; Juliane Deise Fleck; Fernando Rosado Spilki; Severino Silvano dos Santos Higino; Sergio Santos de Azevedo; Matheus Nunes Weber (Archives of Virology, 2025)

Retraction notice to “Toxicity of spike fragments SARS-CoV-2 S protein for zebrafish: A tool to study its hazardous for human health?” [Sci. Total Environ. 813 (2022) / 152345] - Bianca H. Ventura Fernandes; Natália Martins Feitosa; Ana Paula Barbosa; Camila Gasque Bomfim; Anali M.B. Garnique; Ivana F. Rosa; Maira S. Rodrigues; Lucas B. Doretto; Daniel F. Costa; Bruno Camargo-dos-Santos; Gabrielli A. Franco; João Favero Neto; et al. (Science of The Total Environment, 2024)

Magnetometric and seismic investigation of the Nova Colinas impact structure, Parnaíba Basin, Brazil - Fernando Lessa Pereira; Alvaro Penteado Crósta; Pietro Demattê Avona; Marcos Alberto Rodrigues Vasconcelos; Ana Maria Goés (Journal of South American Earth Sciences, 2024)

Sulfated polysaccharide extracted from the alga Gracilaria domingensis modified with propionic anhydride negatively modulates acute inflammation and experimental hypernociception - Jayro dos Santos Ferreira; Rafael da Silva Prudêncio; Antonio Kleiton de Sousa; Stefany Guimarães Sousa; Fernando Mesquita de Sousa de Lima; André dos Santos Carvalho; Ana Clara Coelho da Costa; Denise Mayara Melo Silva; Maria da Graça Sales Furtado; Danyela Maria Leal Rocha; Vanderlene Oliveira Rodrigues; Daniel Fernando Pereira Vasconcelos; et al. (Bioactive Carbohydrates and Dietary Fibre, 2024)

Dietary supplementation of mineral nanoparticles for channel catfish (Ictalurus punctatus) - Vitor F. Silva; José Luiz P. Mouriño; Maurício L. Martins; Pedro L. P. F. Carvalho; Edgar D. Rodrigues; Delbert M. Gatlin; Matt J. Griffin; Caitlin E. Older; Fernando Y. Yamamoto (Fish Physiology and Biochemistry, 2024)

Hepatitis E virus prevalence among HIV-2 infected individuals in central Portugal - João Pereira-Vaz; Anália Carmo; Vítor Duque; Cristina Luxo; Ana Alves; Alexandra Mendes; Célia Morais; Cláudio Gaspar; Raquel Costa; Lurdes Correia; Fernando Rodrigues; Ana Matos (European Journal of Clinical Microbiology & Infectious Diseases, 2024)

Chlorantraniliprole mediating the survival and behavior of adults of Tuta absoluta (Meyrick) (Lepidoptera: Gelechiidae) in tomato - Matheus Rodrigues Martins; Ana Flávia Soares Nascimento; Maria Elisa de Sena Fernandes; Jairo Tronto; Luciano Ferreira da Fonseca; Ryan Fernando Silva e Silva; Flávio Lemes Fernandes (International Journal of Tropical Insect Science, 2024)

Disentangling the veil line for Brazilian biodiversity: An overview from two long-term research programs reveals huge gaps in ecological data reporting - Aretha Franklin Guimaraes; Luciano Carramaschi de Alagao Querido; Taina Rocha; Domingos de Jesus Rodrigues; Pedro Lage Viana; Helena de Godoy Bergallo; Geraldo Wilson Fernandes; Tiago Shizen Pacheco Toma; Helena Streit; Gerhard Ernst Overbeck; Alberico Queiroz Salgueiro de Souza; Albertina Pimentel Lima; et al. (Science of The Total Environment, 2024)

Cardiovascular effects of dog-appeasing pheromone in the hospital environment - Tainá Minuzzo; Juliana Schmitz Bascherotto; Fernando Luis Cemenci Gnoatto; Marina Marangoni; Melissa Rodrigues de Souza; Tatiana Champion (Journal of Veterinary Behavior, 2024)

Berthierine/Chamosite ooids and associated phases in Devonian deposits of the Parnaíba Basin, Brazil: Genesis and diagenetic evolution - Matheus Moreira Schirmbeck; Amanda Goulart Rodrigues; Leonardo Borghi; Luiz Fernando De Ros (Journal of South American Earth Sciences, 2024)

Impact of processing on polyphenols content in food: A nutritional and statistical analysis of Brazilian menus - Valéria Silva de Lana; Thais Barcelos de Castro; Livya Alves Oliveira; Stephanie Michelin Santana Pereira; Kelly Aparecida Dias; Rafaela Neto dos Santos Rodrigues; Ceres Mattos Della Lucia; Fernando Frei; Izabela Maria Montezano de Carvalho (Food Research International, 2024)

The bioactive potential of cheese whey peptides from different animal origins (bovine, goat, sheep, buffalo, and camel): A systematic review and meta-analysis - Marcy Heli Paiva Rodrigues; Cláudia Andréia Gräff; Diego Santiago Tupuna-Yerovi; Caroline Schmitz; Jeferson Camargo de Lima; Luís Fernando Saraiva Macedo Timmers; Daniel Neutzling Lehn; Claucia Fernanda Volken de Souza (Food Research International, 2024)

Effect of a thiohydantoin salt derived from -Arginine on Leishmania amazonensis and infected cells: Insights from biological effects to molecular docking interactions - Bruna Taciane da Silva Bortoleti; Priscila Goes Camargo; Manoela Daiele Gonçalves; Fernanda Tomiotto-Pellissier; Taylon Felipe Silva; Virginia Marcia Concato; Mariana Barbosa Detoni; Danielle Larazin Bidóia; Camilo Henrique da Silva Lima; Carlos Rangel Rodrigues; Marcelle de Lima Ferreira Bispo; Fernando Cesar de Macedo; et al. (Chemico-Biological Interactions, 2024)

In Vitro Synergistic Activity of Rifampicin Combined with Minimal Effective Antibiotic Concentration (MEAC) of Polymyxin B Against Extensively Drug-Resistant, Carbapenem-, and Polymyxin B-Resistant Klebsiella pneumoniae Clinical Isolates - Nathália Abichabki; Gilberto Gambero Gaspar; Luísa Vieira Zacharias; Renata Helena Cândido Pocente; Denissani Aparecida Ferrari Santos Lima; Natália Augusta Barbosa de Freitas; Guilherme Thomaz Pereira Brancini; Natália Columbaro Moreira; Gilberto Úbida Leite Braga; Fernando Bellissimo-Rodrigues; Valdes Roberto Bollela; Ana Lúcia Costa Darini; et al. (Current Microbiology, 2024)

Diazepam nanocapsules as an alternative for sleep induction: Development study and toxicity assessment - Julia Gabriele de Jesus Ferreira; Victoria Givankliff Flores; Mariana Roza Marco; Bianca Bordignon Fraga; Roberta Rodrigues Zorzo; Patrícia da Fonseca de Morais; Fernando Dal Pont Morisso; Juliane Deise Fleck; Mariele Feiffer Charão; Cristiane Bastos de Mattos; Andresa Heemann Betti (Food and Chemical Toxicology, 2024)

Orbital multispectral imaging: a tool for discriminating management strategies for nematodes in coffee - Vinicius Silva Werneck Orlando; Bruno Sérgio Vieira; George Deroco Martins; Everaldo Antônio Lopes; Gleice Aparecida de Assis; Fernando Vasconcelos Pereira; Maria de Lourdes Bueno Trindade Galo; Leidiane da Silva Rodrigues (Precision Agriculture, 2024)

Investigating the effects of Brachiaria (Syn. Urochloa) varieties on soil properties and microbiome - Luis Fernando Merloti; João William Bossolani; Lucas William Mendes; Gabriel Silvestre Rocha; Mayara Rodrigues; Fernanda Ometto Asselta; Carlos Alexandre Costa Crusciol; Siu Mui Tsai (Plant and Soil, 2024)

Zoogeographical regions in the Atlantic Forest: patterns and potential drivers - Fernando Rodrigues da Silva; Anna Elizabeth de Oliveira‐Silva; Alexandre Antonelli; Ana Carolina Carnaval; Diogo B. Provete (Journal of Biogeography, 2024)
Aim To delineate present‐day zoogeographical regions of terrestrial vertebrates (frogs, lizards, snakes, birds and non‐volant mammals) in the Atlantic Forest. Within each taxonomic group, we examine the relative importance of abrupt climatic transitions, orographic barriers, past climate change and rivers in shaping zoogeographical boundaries. Location South America's Atlantic Forest. Methods We applied a network‐based method to delineate zoogeographical regions, using distribution data (range maps) for 455 species of frogs, 103 lizards, 220 snakes, 917 birds and 202 non‐volant mammals, in 50 × 50 km grid cells. We used hierarchical generalized linear mixed‐effects models to test environmental predictors associated with zoogeographical boundaries. Finally, we intersected the bioregion maps delineated for each group to identify general patterns across all vertebrates. Results We identified four zoogeographical regions for birds and snakes, and five for frogs, lizards and non‐volant mammals. Depending on the group, contemporary and past climate conditions, elevation variation and/or rivers were associated with zoogeographical boundaries. The combined maps indicate that the Atlantic Forest retains four spatially cohesive zoogeographical regions based on present‐day distribution of vertebrates. Main conclusions Cross‐taxon congruence indicates that the geographical and environmental characteristics of the Atlantic Forest have a strong influence on the location of zoogeographical regions for vertebrates. In contrast, transition zones appear to be associated with the spatial distribution of life history traits of each group, potentially explaining the observed differences in the number of bioregions across groups and the position of zoogeographical boundaries. This work paves the way for further research into the evolutionary assembly of the Atlantic Forest's zoogeographical regions and may help inform conservation priorities for maintaining their distinctive faunas.

Crop functional structure predicts the provision of Nature´s material Contribution to People in diversified agroforestry - Marinice Teleginski; Diego dos Santos; Fernando Joner; Renata Rodrigues Lucas; Larissa Aparecida Augusto; Ilyas Siddique (European Journal of Agronomy, 2024)

Addition of synthetic polymers to a conventional cryoprotectant solution in the vitrification of bovine ovarian tissue - Taynná El Cury-Silva; Cynthia Dela Cruz; Monique G. Nunes; Maíra Casalechi; André L. Caldeira-Brant; Jhenifer K. Rodrigues; Fernando M. Reis (Cryobiology, 2024)

Comparing Bayesian models for the genetic evaluation of oocytes and embryo counts in Dairy Gir cattle - Giovani Luis Feltes; Gabriel Soares Campos; Fernanda Santos Silva Raidan; Luiz Fernando Rodrigues Feres; Virgínia Mara Pereira Ribeiro; Jaime Araújo Cobuci (Journal of Applied Genetics, 2024)

Agronomic potential of different fermented organic composts based on agro-industrial plant waste - Ana Amélia dos Santos Cordeiro; Luiz Fernando de Sousa Antunes; Giulia da Costa Rodrigues dos Santos; José Guilherme Marinho Guerra; Ricardo Luiz Louro Berbara; Ednaldo da Silva Araújo; José Antonio Azevedo Espindola (Environmental Monitoring and Assessment, 2024)

Use of crude glycerin in dairy goat feeding and its effects on milk and cheese performance and quality - Rodrigo Barbosa de Andrade; Kelly Cristina dos Santos; Érica Carla Lopes da Silva; Edneide Rodrigues da Silva; Michel do Vale Maciel; João Paulo Ismério dos Santos Monnerat; Dorgival Morais de Lima Júnior; Neila Mello dos Santos Cortez; Maria Gabriela da Conceição; Susana Paula Almeida Alves; Rui José Branquinho de Bessa; Francisco Fernando Ramos de Carvalho (Animal Feed Science and Technology, 2024)

Continuous UV-C/H2O2 and UV-C/Chlorine applied to municipal secondary effluent and nanofiltration retentate: Removal of contaminants of emerging concern, ecotoxicity, and reuse potential - Fernando Rodrigues-Silva; Carla S. Santos; Joaquín A. Marrero; Rosa Montes; José Benito Quintana; Rosario Rodil; Olga C. Nunes; Maria Clara V.M. Starling; Camila C. Amorim; Ana I. Gomes; Vítor J.P. Vilar (Chemosphere, 2024)

Cyclopenta[b]indoles as novel antimicrotubule agents with antileukemia activity - Hugo Passos Vicari; Ralph da Costa Gomes; Keli Lima; Nicolas de Oliveira Rossini; Manoel Trindade Rodrigues Junior; Lívia Bassani Lins de Miranda; Marcio Vinicius Bertacini Dias; Leticia Veras Costa-Lotufo; Fernando Coelho; João Agostinho Machado-Neto (Toxicology in Vitro, 2024)

Soil organic carbon stocks and fractions under integrated systems and pasture in the Cerrado of Northeast Brazil - Renato Falconeres Vogado; Henrique Antunes de Souza; Edvaldo Sagrilo; Lucélia de Cássia Rodrigues de Brito; Sammy Sidney Rocha Matias; Marcos Lopes Teixeira Neto; José Oscar Lustosa de Oliveira Junior; Hosana Aguiar Freitas de Andrade; Luiz Fernando Carvalho Leite (CATENA, 2024)

Evaluation of different supportive treatments during packed cell volume replacement in calves naturally infected with tick fever agents - Alexandre Braga Scarpa; Vanessa Ferreira Salvador; Luccas Lourenzzo Lima Lins Leal; Igor Maciel Lopes de Morais; Luiz Fellipe Monteiro Couto; Luciana Maffini Heller; Dina María Beltrán Zapa; Lídia Mendes de Aquino; Daniel de Castro Rodrigues; Nicolas Jalowitzki de Lima; Vando Edésio Soares; Lorena Lopes Ferreira; et al. (Veterinary Research Communications, 2024)

Ultra-diluted complex additive in the diet reveals benefits in the intestinal tract of nursery-phase piglets - Gustavo Zigovski; Isabela Cristina Colaço Bez; Luís Fernando Costa Garrido; Caroline Cintra Rodrigues; Angela Cristina da Fonseca de Oliveira; Paulo Evaristo Rupolo; Liliana Bury de Azevedo; Elmer Modesto Elvir Hernandez; Jansller Luiz Genova; Saulo Henrique Weber; Paulo Levi de Oliveira Carvalho; Leandro Batista Costa (Veterinary Research Communications, 2024)

Depth, hard coral, and turf cover as predictors of micro-scale spatial distribution of fishes in a subtropical rocky reef - Thiago E. Rodrigues; Vinícius J. Giglio; Fernando Z. Gibran; Fernanda A. Rolim; Leonardo M. Neves; Guilherme Henrique Pereira-Filho; Gustavo Shintate; Gabriel R. S. Souza; Domingos Garrone-Neto; Fabio S. Motta (Environmental Biology of Fishes, 2024)

Organ-specific proteomes of Selaginella convoluta provide insights into its desiccation tolerance mechanisms - Fernanda Priscila Santos Reginaldo; Luiz Fernando Rodrigues de Souza; Daisy Sotero Chacon; Marlon Dias Mariano Santos; Taffarel Melo Torres; Ivanice Bezerra da Silva; Alan de Araújo Roque; Carlos André O. Ricart; Mariana S. Castro; Paulo Costa Carvalho; Wagner Fontes; Marcelo Valle de Sousa; et al. (Plant Biosystems, 2024)

Alkaloids (emetine and cephalin) production – affected by full sunlight stress in Carapichea ipecacuanha - Cristina Moll Hüther; Vitor Francisco Ferreira; Fernando de Carvalho da Silva; Wilson da Costa Santos; Junior Borella; Ramonn Diego Barros de Almeida; Daniela Marques Correia; Glauce Christian Alves Duarte; Ana Claudia Langaro; Julia Ramos de Oliveira; Jóice Azeredo Silva; Thelma de Barros Machado; et al. (Natural Product Research, 2024)

Ensemble Smoother with Fully Convolutional VAE for seismic facies inversion - Rodrigo Exterkoetter; Leandro Passos de Figueiredo; Fernando Luis Bordignon; Alexandre Anoze Emerick; Mauro Roisenberg; Bruno Barbosa Rodrigues (Computers & Geosciences, 2024)

Impact of a run-of-river dam in an Amazonian large river on the spatial and temporal patterns of phytoplankton beta diversity - Felipe M. Zanon; Alfonso Pineda; Fernando M. Lansac-Tôha; Luzia C. Rodrigues (Biological Conservation, 2024)

Selecting oocyte donors based on anti-Müllerian hormone (AMH) concentrations: A critical analysis of using cutoff values as exclusion criterion for an in vitro embryo production program in Gir cattle - Luiz Fernando Rodrigues Feres; Luiz Gustavo Bruno Siqueira; Miller Pereira Palhao; Livia Loiola dos Santos; Luiz Francisco Machado Pfeifer; Carlos Antônio de Carvalho Fernandes; Joao Henrique Moreira Viana (Animal Reproduction Science, 2024)

Organic stabilization and methane production under different organic loading rates in UASB treating swine wastewater - Jacineumo Falcão de Oliveira; Ronaldo Fia; Ana Flavia Santos Rabelo de Melo; Fátima Resende Luiz Fia; Fernando Neris Rodrigues; Luciene Alves Batista Siniscalchi; Mateus Pimentel de Matos (Biodegradation, 2024)

Geography and ecology shape the phylogenetic composition of Amazonian tree communities - Bruno Garcia Luize; David Bauman; Hans ter Steege; Clarisse Palma‐Silva; Iêda Leão do Amaral; Luiz de Souza Coelho; Francisca Dionízia de Almeida Matos; Diógenes de Andrade Lima Filho; Rafael P. Salomão; Florian Wittmann; Carolina V. Castilho; Marcelo de Jesus Veiga Carim; et al. (Journal of Biogeography, 2024)
Aim Amazonia hosts more tree species from numerous evolutionary lineages, both young and ancient, than any other biogeographic region. Previous studies have shown that tree lineages colonized multiple edaphic environments and dispersed widely across Amazonia, leading to a hypothesis, which we test, that lineages should not be strongly associated with either geographic regions or edaphic forest types. Location Amazonia. Taxon Angiosperms (Magnoliids; Monocots; Eudicots). Methods Data for the abundance of 5082 tree species in 1989 plots were combined with a mega‐phylogeny. We applied evolutionary ordination to assess how phylogenetic composition varies across Amazonia. We used variation partitioning and Moran's eigenvector maps (MEM) to test and quantify the separate and joint contributions of spatial and environmental variables to explain the phylogenetic composition of plots. We tested the indicator value of lineages for geographic regions and edaphic forest types and mapped associations onto the phylogeny. Results In the terra firme and várzea forest types, the phylogenetic composition varies by geographic region, but the igapó and white‐sand forest types retain a unique evolutionary signature regardless of region. Overall, we find that soil chemistry, climate and topography explain 24% of the variation in phylogenetic composition, with 79% of that variation being spatially structured ( R 2 = 19% overall for combined spatial/environmental effects). The phylogenetic composition also shows substantial spatial patterns not related to the environmental variables we quantified ( R 2 = 28%). A greater number of lineages were significant indicators of geographic regions than forest types. Main Conclusion Numerous tree lineages, including some ancient ones (>66 Ma), show strong associations with geographic regions and edaphic forest types of Amazonia. This shows that specialization in specific edaphic environments has played a long‐standing role in the evolutionary assembly of Amazonian forests. Furthermore, many lineages, even those that have dispersed across Amazonia, dominate within a specific region, likely because of phylogenetically conserved niches for environmental conditions that are prevalent within regions.

Sampling completeness changes perceptions of continental scale climate–species richness relationships in odonates - Fernanda Alves‐Martins; Juliana Stropp; Leandro Juen; Richard J. Ladle; Jorge M. Lobo; Javier Martinez‐Arribas; Paulo De Marco Júnior; Leandro Schlemmer Brasil; Victor Rennan Santos Ferreira; Rafael Costa Bastos; Alex Córdoba‐Aguilar; Emmy Fiorella Medina‐Espinoza; et al. (Journal of Biogeography, 2024)
Aim Insects are one of the least studied taxa, with most species lacking basic ecological and biogeographical information. This problem is particularly acute in the tropics, where low sampling effort hampers accurate estimates of species richness at scale and potentially confounds efforts to identify the drivers of biogeographical gradients. Here, we evaluate the quality of the data on the distribution and diversity of odonate species in the Neotropics, while also examining the influence of sampling completeness on climate–richness relationships using a comprehensive database of odonates. Location The Neotropics. Taxon Odonata. Methods Using 56,535 records collected from 1970 to 2021, we assess whether climate–species richness models vary under different scenarios of survey completeness. Results Our survey compilation revealed that most Neotropical diversity of Odonata likely remains unknown. Only 1% of the one‐degree cells covering the Neotropics held reliable information on odonate species richness, with particularly severe gaps in the Caribbean, Central America, northeastern Brazil and northern Chile. Temperature, precipitation and potential evapotranspiration exert consistent effects on Odonata richness across the entire Neotropics, regardless the level of survey completeness. Whereas seasonality‐related variables are less important predictors of species richness at the biogeographical scale. Main Conclusions By highlighting areas where inventories are more reliable and identifying regions that require increased data collection efforts and mobilization, our assessment offers a roadmap for improving the reliability of odonate inventories in the Neotropics. Furthermore, our findings underscore the importance of accounting for varying levels of survey completeness in macroecological models to reveal robust climate–species richness relationships. Simultaneously, they highlight strong climatic predictors of species richness, irrespective of survey effort intensity. These predictors provide a solid foundation for modelling and predicting odonate species richness in the Neotropics.

Ecotoxicological strategies employing biochemical markers and organisms to monitor the efficacy of malathion photolysis treatment - Rafaela Imoski; Laís Jarenko da Cruz; Angela Maria Palacio-Cortés; Ana Marta Schafaschek; Eric Schwamberger; Pamella Regina Mariotti; Andre Luis Bichibichi Borges; Fernando Rodrigues-Silva; Liziê Daniela Tentler Prola; Mario Antônio Navarro da Silva; Adriane Martins de Freitas; Marcus Vinicius de Liz (Chemosphere, 2024)

In vitro effects of the harmful benthic dinoflagellates Prorocentrum hoffmannianum and Ostreopsis cf. ovata on immune responses of the farmed oyster Crassostrea gasar - Fernando Ramos Queiroga; Hélène Hegaret; Wanderson Fernandes Carvalho; Clarissa Naveira; Nathália Rodrigues; Fernanda Silva dos Santos; Silvia Mattos Nascimento; Raquel A.F. Neves (Marine Environmental Research, 2024)

Do invasive and native grasses in Brazilian Savanna differ in their photosynthetic performance under natural light radiation? - Áurea Rodrigues Cordeiro; Alexandre Aparecido Duarte; Felipe Della-Torre; Fernando Afonso Nonato França; Marcel Giovanni Costa França (Flora, 2024)

ENSO effects on the relationship between aerosols and evapotranspiration in the south of the Amazon biome - Rafael Palácios; Daniela Castagna; Luzinete Barbosa; Adilson P. Souza; Breno Imbiriba; Cornélio A. Zolin; Danielle Nassarden; Leilane Duarte; Fernando G. Morais; Marco A. Franco; Glauber Cirino; Paulo Kuhn; et al. (Environmental Research, 2024)

Effects of a Mining Dam Disaster on Antimicrobial-Resistant and Metal-Tolerant Bacterial Strains Recovered from Environmental Samples - João Pedro Rueda Furlan; Micaela Santana Ramos; Lucas David Rodrigues dos Santos; Rafael da Silva Rosa; Ana Carolina Paulelli; Cecilia Cristina de Souza Rocha; Cibele Aparecida Cesila; Matheus Gallimberti; Paula Pícoli Devóz; Fernando Barbosa Júnior; Eliana Guedes Stehling (Water, Air, & Soil Pollution, 2024)

Effect of quantitative feed restriction and sex class on sheep skin quality - Anna Neusa Eduarda Ferreira de Brito; Rafael Torres de Souza Rodrigues; Glayciane Costa Gois; Ivonete Ferreira da Silva; José Gledyson da Silva; Joanigo Fernando Simão; Mario Luiz Chizzotti; Nataline Silva Araújo; Daniel Ribeiro Menezes; Mariliz Gutterres Soares; Mário Adriano Ávila Queiroz (Tropical Animal Health and Production, 2024)

Predation of a neonate caiman, Caiman latirostris (Daudin, 1802) by red fire ants Solenopsis sp. in Atlantic Forest, North-eastern Brazil - Carlos Fernando Rodrigues De Souza Neto; Rafael Sá Leitão Barboza; Ednilza Maranhão Dos Santos; Jozelia Maria de Sousa Correia (Tropical Ecology, 2024)

In vitro activity of the anthelmintic drug niclosamide against Sporothrix spp. strains with distinct genetic and antifungal susceptibility backgrounds - Mariana Lucy Mesquita Ramos; Fernando Almeida-Silva; Vanessa Brito de Souza Rabello; Juliana Nahal; Maria Helena Galdino Figueiredo-Carvalho; Andrea Reis Bernardes-Engemann; Vanice Rodrigues Poester; Melissa Orzechowski Xavier; Wieland Meyer; Rosely Maria Zancopé-Oliveira; Susana Frases; Rodrigo Almeida-Paes (Brazilian Journal of Microbiology, 2024)

Evaluation of Mastadenovirus and Rotavirus Presence in Phyllostomid, Vespertilionid, and Molossid Bats Captured in Rio Grande do Sul, Southern Brazil - Alexandre Sita; Gabriela Espíndola Birlem; Deivid de Souza da Silva; Gabriela Mattos Possamai; Karla Petry; Paula Rodrigues de Almeida; Larissa Mallmann; Janaína Franciele Stein; Meriane Demoliner; Juliana Schons Gularte; Alana Witt Hansen; André Alberto Witt; et al. (Food and Environmental Virology, 2024)

Beyond beta: diversity partitioning reveals different underlying patterns in ant assemblages along two small scale gradients in a Brazilian neotropical forest - Francisko de Moraes Rezende; Fernando Augusto Schmidt; Rodrigo Silva Jesus; Carla Rodrigues Ribas; José Henrique Schoereder (International Journal of Tropical Insect Science, 2024)

The influence of serum selenium in differential epigenetic and transcriptional regulation of CPT1B gene in women with obesity - Lígia Moriguchi Watanabe; Vanessa Aparecida Batista Pereira; Natalia Yumi Noronha; Marcela Augusta de Souza Pinhel; Leticia Santana Wolf; Cristiana Cortes de Oliveira; Jessica Rodrigues Plaça; Isabella Harumi Yonehara Noma; Guilherme da Silva Rodrigues; Vanessa Cristina Oliveira de Souza; Fernando Barbosa Júnior; Carla Barbosa Nonino (Journal of Trace Elements in Medicine and Biology, 2024)

Provenance of volcano-sedimentary features using tourmaline and REE compositional analysis, in the Paraná Basin, southern Brazil - Isaque C. Rodrigues; Ana M.P. Mizusaki; Glaucia N. Queiroga; Cassiana R.L. Michelin; Fernando R. Rios (Journal of South American Earth Sciences, 2024)

Immune response in paper wasp workers: Task matters more than age - Amanda Prato; Eduardo Fernando Santos; Helena Mendes Ferreira; Cintia Akemi Oi; Fábio Santos do Nascimento; Markus J. Rantala; Indrikis Krams; André Rodrigues de Souza (Journal of Insect Physiology, 2024)

Camera trap surveys of A tlantic F orest mammals: A data set for analyses considering imperfect detection (2004–2020) - Ingridi Camboim Franceschi; Rubem Augusto da Paixão Dornas; Isabel Salgueiro Lermen; Artur Vicente Pfeifer Coelho; Ademir Henrique Vilas Boas; Adriano Garcia Chiarello; Adriano Pereira Paglia; Agnis Cristiane de Souza; Alana Rafaela Borsekowsky; Alessandro Rocha; Alex Bager; Alexander Zaidan de Souza; et al. (Ecology, 2024)
Camera traps became the main observational method of a myriad of species over large areas. Data sets from camera traps can be used to describe the patterns and monitor the occupancy, abundance, and richness of wildlife, essential information for conservation in times of rapid climate and land‐cover changes. Habitat loss and poaching are responsible for historical population losses of mammals in the Atlantic Forest biodiversity hotspot, especially for medium to large‐sized species. Here we present a data set from camera trap surveys of medium to large‐sized native mammals (>1 kg) across the Atlantic Forest. We compiled data from 5380 ground‐level camera trap deployments in 3046 locations, from 2004 to 2020, resulting in 43,068 records of 58 species. These data add to existing data sets of mammals in the Atlantic Forest by including dates of camera operation needed for analyses dealing with imperfect detection. We also included, when available, information on important predictors of detection, namely the camera brand and model, use of bait, and obstruction of camera viewshed that can be measured from example pictures at each camera location. Besides its application in studies on the patterns and mechanisms behind occupancy, relative abundance, richness, and detection, the data set presented here can be used to study species' daily activity patterns, activity levels, and spatiotemporal interactions between species. Moreover, data can be used combined with other data sources in the multiple and expanding uses of integrated population modeling. An R script is available to view summaries of the data set. We expect that this data set will be used to advance the knowledge of mammal assemblages and to inform evidence‐based solutions for the conservation of the Atlantic Forest. The data are not copyright restricted; please cite this paper when using the data.

Differentiating Bagasse and Straw as Feedstocks for Sugarcane Cellulosic Ethanol: Insights from Pilot-Scale Pretreatments - Viviane M. Nascimento; Simone C. Nakanishi; Carlos Alberto de Oliveira Filho; Absai da Conceição Gomes; Aline Machado de Castro; Ana Paula Rodrigues Torres; Christian Alejandro Queipo; Danuza Nogueira Moyses; Felipe de Oliveira Brito; Luiz Fernando Martins Bandeira; Carlos Driemeier (BioEnergy Research, 2024)

Evaluation of dual-energy X-ray absorptiometry (DXA) technique for the determination of body composition of Pacu and Nile tilapia in vivo - Cleber Fernando Menegasso Mansano; Edney Pereira da Silva; Kifayat Ullah Khan; Thiago Matias Torres do Nascimento; Nilva Kazue Sakomura; Andressa Tellechea Rodrigues; André Zuffo Boaratti; Rafael de Souza Romaneli; Daniel Monge de Almeida Queiroz; Juliana Heloisa Pinê Américo-Pinheiro; Acacio Aparecido Navarrete; Beatrice Ingrid Macente; et al. (Aquaculture, 2024)

Suitable areas for temperate fruit trees in a Brazilian hotspot area: Changes driven by new IPCC scenarios - Alysson Fernando Ribeiro; Fabrina Bolzan Martins; Diego Felipe dos Santos; Roger Rodrigues Torres; Flávia Fernanda Azevedo Fagundes (European Journal of Agronomy, 2024)

In the line of fire: Analyzing burning impacts on air pollution and air quality in an Amazonian city, Brazil - Fernando Rafael de Moura; Petter Djeison Witte Machado; Paula Florêncio Ramires; Ronan Adler Tavella; Helotonio Carvalho; Flávio Manoel Rodrigues da Silva Júnior (Atmospheric Pollution Research, 2024)

The vicariant role of Caribbean formation in driving speciation in American loliginid squids: the case of Doryteuthis pealeii (Lesueur 1821) - João Bráullio Luna Sales; Frank E. Anderson; Bianca Lima Paiva; Yasmim T. C. Cunha; Alan Érik Souza Rodrigues; Yrlene Ferreira; Luis Fernando S. Rodrigues-Filho; Paul W. Shaw; Manuel Haimovici; Unai Markaida; Jonathan S. Ready; Iracilda Sampaio (Marine Biology, 2024)

Chemical attributes, bacterial community, and antibiotic resistance genes are affected by intensive use of soil in agro-ecosystems of the Atlantic Forest, Southeastern Brazil - Paula Fernanda Alves Ferreira; Fernando Igne Rocha; Adina Howe; Daniele Rodrigues Barbosa; Ederson da Conceição Jesus; Nelson Moura Brasil do Amaral Sobrinho; Irene da Silva Coelho (Environmental Geochemistry and Health, 2024)

Performance of spray nozzles and droplet size on glufosinate deposition and weed biological efficacy - Evandro P. Prado; Júlio C. Guerreiro; Pedro J. Ferreira-Filho; Vagner do Nascimento; Samuel Ferrari; Fernando S. Galindo; Marina Funichello; Carlos G. Raetano; Paulo H. Pagliari; Rodolfo G. Chechetto; Arthur D. Rodrigues Neto (Crop Protection, 2024)

Anthocyanins extracted from Jamelon fruits (Syzygium cumini L.): Effect of microencapsulation on the properties and bioaccessibility - Francisco Elvino Rodrigues Paes; Luiz Bruno de Sousa Sabino; Larissa Morais Ribeiro da Silva; Ivanildo José da Silva; Nágila Maria Pontes Silva Ricardo; Débora Hellen Almeida de Brito; Fernando Lima de Menezes; Raimundo Wilane de Figueiredo (South African Journal of Botany, 2024)

Correction: Synergism between molecules derived from Garcinia brasiliensis and antimicrobial drugs on field isolates of Mycoplasma hyopneumoniae - Bruna Araújo Euzébio Alves Jacob Lopes; Leonardo Teófilo Toledo; Jéssica Lobo Albuquerque Caldeira; Fábio Assad Feres Rodrigues; Mariana de Barros; Luiz Fernando Lino de Souza; Natália Fialho Gonzaga; Marcelo Henrique dos Santos; Abelardo Silva-Júnior; Maria Aparecida Scatamburlo Moreira (Brazilian Journal of Microbiology, 2024)

Synergism between molecules derived from Garcinia brasiliensis and antimicrobial drugs on field isolates of Mycoplasma hyopneumoniae - Bruna Araújo Euzébio Alves Jacob Lopes; Leonardo Teófilo Toledo; Jessica Lobo Albuquerque Caldeira; Fábio Assad Feres Rodrigues; Mariana de Barros; Luiz Fernando Lino de Souza; Natália Fialho Gonzaga; Marcelo Henrique dos Santos; Abelardo Silva-Júnior; Maria Aparecida Scatamburlo Moreira (Brazilian Journal of Microbiology, 2024)

Integrating pollutant levels and biochemical biomarkers in oysters (Crassostrea rhizophorae and Crassostrea gasar) indicates anthropic impacts on marine environments along the coast of Santa Catarina state, Brazil - Fernando de Campos Guerreiro; Thiago Caíque Alves; Miguel Saldaña-Serrano; Carlos Henrique Araújo de Miranda Gomes; Daína de Lima; Camila Lisarb Velasquez Bastolla; Clarissa Pellegrini Ferreira; Daiane Bitschinski; Camila Fatima Rutkoski; Suelen Cristina Grott; Nicole Grasmuk Israel; Karim Hahn Lüchmann; et al. (Marine Environmental Research, 2024)

Airborne geophysics, petrophysics, geochemistry and geology of Ni-Cu (Co-Au-PGE) footprints to define exploration targets in mafic-ultramafic rocks - Thiago Lima Mendes; Marcelo Henrique Leão-Santos; Luiz Fernando Cursino Tabosa; Welitom Rodrigues Borges; Cleber dos Santos Alves; Marcos Tadeu de Freitas Suita (Journal of South American Earth Sciences, 2024)

Assessing the efficacy of gutiferone E in photodynamic therapy for oral candidiasis - Luis Fernando Gonçalves Lima; Vítor de Paula Castro; Carmen Magaly Ormeño Álvarez; Sérgio Ricardo Ambrósio; Marcela Aldrovani Rodrigues; Regina Helena Pires (Journal of Photochemistry and Photobiology B: Biology, 2024)

Impact of heat stress on genetic evaluation of oocyte and embryo production in Gir dairy cattle - Giovani Luis Feltes; Renata Negri; Fernanda Santos Silva Raidan; Alexandra Fabielle Pereira Viana; Luiz Fernando Rodrigues Feres; Virgínia Mara Pereira Ribeiro; Jaime Araújo Cobuci (Tropical Animal Health and Production, 2024)

Environmental monitoring of SARS-CoV-2 in the metropolitan area of Porto Alegre, Rio Grande do Sul (RS), Brazil - Leticia Batista Dutra; Janaína Francieli Stein; Bruna Seixas da Rocha; Andresa Berger; Beatriz Andrade de Souza; Bruno Aschidamini Prandi; Arthur Tonietto Mangini; André Jarenkow; Aline Alves Scarpellini Campos; Fernando Mainardi Fan; Maria Cristina de Almeida Silva; Katia Helena Lipp-Nissinen; et al. (Environmental Science and Pollution Research, 2023)
Since starts the coronavirus disease 2019 (COVID-19) pandemic identified the presence of genomic fragments of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) in various environmental matrices: domestic sewage, surface waters, and contaminated freshwater. Environmental monitoring of SARS-CoV-2 is a tool for evaluating trend curves over the months, compared to several clinical cases of the disease. The objective of this study was to monitor the SARS-CoV-2 in environmental samples collected in different sites in a metropolitan area of Porto Alegre, Southern Brazil. During 10 months from 2020 to 2021, 300 samples were collected weekly and biweekly from nine points located in 3 cities: one point from a wastewater treatment plant (WWTP) in São Leopoldo (fortnightly collection), two points in Dilúvio Stream in Porto Alegre (fortnightly collection), two points in Pampa and Luiz Rau Streams (weekly collection), and two points in public fountains (fortnightly collection) in Novo Hamburgo. After collection, samples were concentrated by ultracentrifugation, and viral nucleic acids were extracted using MagMax® Core Nucleic Acid Purifications kits and submitted to RT-qPCR, using E, N1, and N2 gene targets of SARS-CoV-2. Only 7% (3/41) samples from public fountains were positive, with a mean viral load (VL) of SARS-CoV-2 RNA of 5.02 × 10 1 gc/l (2.41~8.59 × 10 1 gc/l), while the streams had average VL of 7.43 × 10 5 gc/l (Pampa), 7.06 × 10 5 gc/l (Luiz Rau), 2.01 × 10 5 gc/l (Dilúvio), and 4.46 × 10 5 cg/l (WWTP). The results showed varying levels of viral presence in different sample types, with a demonstrated correlation between environmental viral load and clinical COVID-19 cases. These findings contribute to understanding virus persistence and transmission pathways in the environment. Continuous monitoring, especially in less developed regions, is crucial for early detection of vaccine resistance, new variants, and potential COVID-19 resurgence.

Effects of chronic exposure to sublethal doses of neonicotinoids in the social wasp Polybia paulista: Survival, mobility, and histopathology - Nathan Rodrigues Batista; Cliver Fernandes Farder-Gomes; Roberta Cornélio Ferreira Nocelli; William Fernando Antonialli-Junior (Science of The Total Environment, 2023)

Curvature analysis and its correlation with faults and fractures in presalt carbonates, Santos Basin, Brazil - Eberton Rodrigues de Oliveira Neto; Tuany Younis Abdul Fatah; Raquel Macedo Dias; Antonio Fernando Menezes Freire; Wagner Moreira Lupinacci (Marine and Petroleum Geology, 2023)

The Maracangalha injectite complex: An overlooked hydrocarbon play in the Lower Cretaceous Recôncavo Basin, NE Brazil - Deise Marli da Silveira; Fernando Farias Vesely; Claus Fallgatter; Mérolyn Camila Naves De Lima Rodrigues; Andreas Pauli de Castro (Marine and Petroleum Geology, 2023)

Impacts of the insecticide thiamethoxam on the native stingless bee Plebeia catamarcensis (Hymenoptera, Apidae, Meliponini) - Michele Castro de Paula; Nathan Rodrigues Batista; Dayana Alves da Silva Cunha; Poliana Galvão dos Santos; William Fernando Antonialli-Junior; Claudia Andrea Lima Cardoso; Euclésio Simionatto (Environmental Pollution, 2023)

A review of adsorbents for removal of yellow tartrazine dye from water and wastewater - Débora Hungaro Micheletti; João Gabriel da Silva Andrade; Carlos Eduardo Porto; Bruna Hungaro Micheletti Alves; Fernando Rodrigues de Carvalho; Otávio Akira Sakai; Vagner Roberto Batistela (Bioresource Technology Reports, 2023)

Bezafibrate reduces the damage, activation and mechanical properties of lung fibroblast cells induced by hydrogen peroxide - Camille Kirinus Reghelin; Matheus Scherer Bastos; Bruno de Souza Basso; Bruna Pasqualotto Costa; Kelly Goulart Lima; Arieli Cruz de Sousa; Gabriela Viegas Haute; Fernando Mendonça Diz; Henrique Bregolin Dias; Carolina Luft; Kétlin Fernanda Rodrigues; Maria Cláudia Rosa Garcia; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2023)

Molecularly imprinted polymers in online extraction liquid chromatography methods: Current advances and recent applications - Alessandra Timóteo Cardoso; Rafael Oliveira Martins; Fernando Mauro Lanças; Andréa Rodrigues Chaves (Analytica Chimica Acta, 2023)

Evaluation of the social impacts of small- and medium-sized biorefineries in the Southern Coast Territory of Bahia considering the selection of technologies for bioactives: an MCDA model - Dayvid Souza Santos; Rilton Gonçalo Bonfim Primo; Ana Paula Henriques Gusmão de Araújo Lima; Vanessa Batista Schramm; Yan Valdez Santos Rodrigues; Mischel Carmen Neyra Belderrain; Fernando Luiz Pellegrini Pessoa; Ricardo de Araújo Kalid; Mario Henrique Bueno Moreira Callefi (Environment, Development and Sustainability, 2023)

Biodiversity and carbon conservation under the ecosystem stability of tropical forests - Lucas Andrigo Maure; Milena Fiuza Diniz; Marco Túlio Pacheco Coelho; Paulo Guilherme Molin; Fernando Rodrigues da Silva; Erica Hasui (Journal of Environmental Management, 2023)

Optimization of a combined system of vertical flow constructed wetland and solar photo-Fenton for ketoprofen removal in sewage and landfill leachate - Priscila Sabioni Cavalheri; Beatriz Santos Machado; Thalita Ferreira da Silva; João Pedro Baza Garcia Rodrigues; Fabio Gozzi; Fernando Jorge Correa Magalhães Filho; Rodrigo Pereira Cavalcante; Silvio César de Oliveira; Amilcar Machulek Junior (Chemical Engineering Journal, 2023)

Comprehensive adsorption and spectroscopic studies on the interaction of magnetic biochar from black wattle sawdust with beta-blocker metoprolol - Cristiane Ferraz de Azevedo; Daniel Lucas Costa Rodrigues; Leandro Lemos Silveira; Eder Claudio Lima; Alice Goncalves Osorio; Robson Andreazza; Claudio Martin Pereira de Pereira; Tais Poletti; Fernando Machado Machado (Bioresource Technology, 2023)

Preclinical data on morpholine (3,5-di-tertbutyl-4-hydroxyphenyl) methanone induced anxiolysis - Iara Barbosa Cabral; Caroline Vitória de Lima Moreira; Ana Carolina Cavalcante Rodrigues; Lorrane Kelle da Silva Moreira; Jhon Kennedy Alves Pereira; Christian Dias Gomides; Luciano M. Lião; Lucas S. Machado; Boniek G. Vaz; Luiz Carlos da Cunha; Jerônimo Raimundo de Oliveira Neto; Edeildo Ferreira da Silva-Júnior; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2023)

Effects of chemotherapeutic drugs on the antioxidant capacity of human erythroleukemia cells with MDR phenotype - Maiara Bernardes Marques; Filipe Reis Teodoro Andrade; Estela Fernandes e Silva; Bruno Rodrigues Oliveira; Daniela Volcan Almeida; Ana Paula de Souza Votto; Luis Fernando Marins (Molecular and Cellular Biochemistry, 2023)

Non-invasive methods to quantify the carcass parameters of sheep: Interaction between thermal environment and residual feed intake - Gabriel Ravi Gama Fontes; Glayciane Costa Gois; Rafael Torres de Souza Rodrigues; David Ramos da Rocha; Tiago Santos Silva; Joanigo Fernando Simão; Nataline Silva Araújo; Silvia Helena Nogueira Turco; Flávio Barbosa Matias; José Gledyson da Silva; Bernardo José Marques Ferreira; Daniel Ribeiro Menezes; et al. (Journal of Thermal Biology, 2023)

How do intrinsic and extrinsic causes interact in the extinction vulnerability of South American savanna shrub and tree species? - Everton A. Maciel; Valéria Forni Martins; Roger Rodrigues Torres; Fernando R. Martins (Journal of Environmental Management, 2023)

Sustainable treatment of municipal secondary effluent from UASB systems by solar photo-Fenton: CECs removal and toxicity control - Fernando Rodrigues-Silva; Maria Clara V.M. Starling; Daniel Aparecido S. Rodrigues; Camila C. Amorim (Journal of Environmental Chemical Engineering, 2023)

Carbon and biodiversity cobenefits of second-growth tropical forest: The role of leaf phenology - Alice Cristina Rodrigues; Fernando Silla; João Augusto Alves Meira-Neto; Lhoraynne Pereira Gomes; Pedro Manuel Villa; Andreza Viana Neri (Forest Ecology and Management, 2023)

Oxidative Machinery of basidiomycetes as potential enhancers in lignocellulosic biorefineries: A lytic polysaccharide monooxygenases approach - Solange Grace Barrios-Gutiérrez; Martha Inés Vélez-Mercado; Júlia Rodrigues Ortega; Awana da Silva Lima; Ana Luiza da Rocha Fortes Saraiva; Gabriela Leila Berto; Fernando Segato (Bioresource Technology, 2023)

Species-specific growth responses to local and regional climate variability indicate the presence of a diversity portfolio effect in mediterranean tree assemblages - Lorién Tornos-Estupiña; Héctor Hernández-Alonso; Jaime Madrigal-González; Alice Rodrigues; Fernando Silla (Agricultural and Forest Meteorology, 2023)

Unintended consequences of valuing the contributions of non-native species: misguided conservation initiatives in a megadiverse region - Fernando Mayer Pelicice; Angelo Antonio Agostinho; Carlos Bernardo Mascarenhas Alves; Marlene Sofia Arcifa; Valter M. Azevedo-Santos; Marcelo Fulgêncio Guedes Brito; Pâmella Silva de Brito; Paula Maria Gênova de Castro Campanha; Fernando Rogério Carvalho; Gabriel Costa da Costa; Mario Alberto Cozzuol; Almir Manoel Cunico; et al. (Biodiversity and Conservation, 2023)

A predatory social wasp does not avoid nestmates contaminated with a fungal biopesticide - André Rodrigues de Souza; Amanda Prato; Wilson Franca; Sircio Santos; Luan Dias Lima; Denise Araujo Alves; Rodrigo Cupertino Bernardes; Eduardo Fernando Santos; Fábio Santos do Nascimento; Maria Augusta Pereira Lima (Environmental Science and Pollution Research, 2023)

Selective versus strategic control against Rhipicephalus microplus in cattle: A comparative analysis of efficacy, animal health, productivity, cost, and resistance management - João Eduardo Nicaretta; Rubens Dias de Melo Junior; Raphaela Barbosa Naves; Igor Maciel Lopes de Morais; Vanessa Ferreira Salvador; Luccas Lourenzzo Lima Lins Leal; Ana Lucia Coutinho Teixeira; Lorena Lopes Ferreira; Guilherme Marcondes Klafke; Caio Marcio de Oliveira Monteiro; Fernando de Almeida Borges; Livio Martins Costa Junior; et al. (Veterinary Parasitology, 2023)

Environmental and agronomic assessment of soil conditioners produced from bauxite residue and oil palm wastes - Robson da Costa Leite; Adriano Reis Lucheta; Roseanne Barata Holanda; Patricia Magalhães Pereira Silva; André Luiz Vilaça do Carmo; Fernando Gama Gomes; Rubson da Costa Leite; Caio Cesar Amorim de Melo; Raphael Vieira da Costa; Marcelo Montini; Antonio Rodrigues Fernandes (Environmental Research, 2023)

Fitness costs associated with spinetoram resistance in Spodoptera frugiperda is driven by host plants - Rubens H. Kanno; Aline S. Guidolin; Fernando E. O. Padovez; Juliana G. Rodrigues; Celso Omoto (Journal of Pest Science, 2023)

Biochar and Forage Peanut improve pastures: Evidence from a field experiment in Brazil - Agnieszka E. Latawiec; Aline F. Rodrigues; Katarzyna A. Korys; Maiara Mendes; Marcio Rangel; Ana Castro; Wenceslau Teixeira; Judson F. Valentim; Ednaldo Araujo; Luiz Fernando Duarte de Moraes; Vinicius Pacheco; Marcos Mendes; et al. (Agriculture, Ecosystems & Environment, 2023)

Giants of the Amazon: How does environmental variation drive the diversity patterns of large trees? - Robson Borges de Lima; Eric Bastos Görgens; Diego Armando S. da Silva; Cinthia Pereira de Oliveira; Anderson Pedro B. Batista; Rinaldo L. Caraciolo Ferreira; Flavia R. C. Costa; Renato A. Ferreira de Lima; Perseu da Silva Aparício; Jadson Coelho de Abreu; José Antônio Aleixo da Silva; Aretha Franklin Guimaraes; et al. (Global Change Biology, 2023)
For more than three decades, major efforts in sampling and analyzing tree diversity in South America have focused almost exclusively on trees with stems of at least 10 and 2.5 cm diameter, showing highest species diversity in the wetter western and northern Amazon forests. By contrast, little attention has been paid to patterns and drivers of diversity in the largest canopy and emergent trees, which is surprising given these have dominant ecological functions. Here, we use a machine learning approach to quantify the importance of environmental factors and apply it to generate spatial predictions of the species diversity of all trees (dbh ≥ 10 cm) and for very large trees (dbh ≥ 70 cm) using data from 243 forest plots (108,450 trees and 2832 species) distributed across different forest types and biogeographic regions of the Brazilian Amazon. The diversity of large trees and of all trees was significantly associated with three environmental factors, but in contrasting ways across regions and forest types. Environmental variables associated with disturbances, for example, the lightning flash rate and wind speed, as well as the fraction of photosynthetically active radiation, tend to govern the diversity of large trees. Upland rainforests in the Guiana Shield and Roraima regions had a high diversity of large trees. By contrast, variables associated with resources tend to govern tree diversity in general. Places such as the province of Imeri and the northern portion of the province of Madeira stand out for their high diversity of species in general. Climatic and topographic stability and functional adaptation mechanisms promote ideal conditions for species diversity. Finally, we mapped general patterns of tree species diversity in the Brazilian Amazon, which differ substantially depending on size class.

Forest restoration rehabilitates soil multifunctionality in riparian zones of sugarcane production landscapes - Wanderlei Bieluczyk; Luis Fernando Merloti; Maurício Roberto Cherubin; Lucas William Mendes; José Albertino Bendassolli; Ricardo Ribeiro Rodrigues; Plínio Barbosa de Camargo; Wim H. van der Putten; Siu Mui Tsai (Science of The Total Environment, 2023)

Development of a multigrid operational forecast system for the oceanic region off Rio de Janeiro State - Fernando T.C. Barreto; Franciane E. Curbani; Gabriel M. Zielinsky; Matheus B.L. da Silva; Kaio C. Lacerda; Douglas F. Rodrigues (Ocean Modelling, 2023)

Volcano-sedimentary interactions – A key to understand Cretaceous paleoenvironments in the Paraná basin (southern Brazil) - Fernando R. Rios; Ana M.P. Mizusaki; Cassiana R.L. Michelin; Isaque C. Rodrigues (Journal of South American Earth Sciences, 2023)

Paleoenvironmental reconstruction of the Permian coal beds in the Paraná Basin (Brazil): evidence from organic geochemical and sedimentological analyses - Ricardo Maahs; Juliano Kuchle; Amanda Goulart Rodrigues; Taís Freitas da Silva; Marleny Blanco González; Fernando Erthal (Journal of South American Earth Sciences, 2023)

Zeolite associated with silicification in a volcano-sedimentary context, southern Brazil - Isaque C. Rodrigues; Ana M.P. Mizusaki; Glaucia N. Queiroga; Cassiana R.L. Michelin; Fernando R. Rios (Journal of South American Earth Sciences, 2023)

Volcanoclastic and epiclastic diagenesis of sandstones associated with volcano-sedimentary deposits from the upper Jurassic, Lower cretaceous, Paraná Basin, southern Brazil - Fernando R. Rios; Ana M.P. Mizusaki; Cassiana R.L. Michelin; Isaque C. Rodrigues (Journal of South American Earth Sciences, 2023)

Evaluation of imazalil dissipation/migration in postharvest papaya using low-temperature partition extraction and GC–MS analysis - Jéssika Faêda de Freitas; Maria Eliana Lopes Ribeiro de Queiroz; André Fernando de Oliveira; Leandro de Paulo Ribeiro; Davi Vittorazzi Salvador; Liany Divina Lima Miranda; Robson Ribeiro Alves; Alessandra Aparecida Zinato Rodrigues (Food Chemistry, 2023)

Potential oil resources from underutilized seeds of Cynophalla flexuosa (Capparaceae) from coastal and semiarid regions of Northeast Brazil - João Bosco da Silva Júnior; Suzene Izídio da Silva; Pablo Rodrigues de Medeiros; Antônio Fernando Morais de Oliveira (Biocatalysis and Agricultural Biotechnology, 2023)

Genetic parameters and multi-trait genomic prediction for hemoparasites infection levels in cattle - Andrea Renata da Silva Romero; André Vieira do Nascimento; Marcia Cristina de Sena Oliveira; Cintia Hiromi Okino; Camila Urbano Braz; Daiane Cristina Becker Scalez; Diercles Francisco Cardoso; Fernando Flores Cardoso; Claudia Cristina Gulias Gomes; Alexandre Rodrigues Caetano; Humberto Tonhati; Cedric Gondro; et al. (Livestock Science, 2023)

Deleterious Effects of Polypropylene Microplastic Ingestion in Nile Tilapia (Oreochromis niloticus) - Luan Souza do Nascimento; Susana Luporini de Oliveira; Camila Carlino da Costa; Mayumi Fernanda Aracati; Letícia Franchin Rodrigues; Ives Charlie-Silva; Gabriel Conde; Cleber Fernando Menegasso Mansano; Dora Ines Kozusny Andreani; Marco Antonio de Andrade Belo (Bulletin of Environmental Contamination and Toxicology, 2023)

Occurrence of bean-associated cytorhabdovirus and cowpea mild mottle virus infecting cultivated and wild Passiflora spp. in Brazil - Andreza Henrique Vidal; Gustavo Pereira Felix; Emanuel Felipe Medeiros Abreu; Bruna Pinheiro-Lima; Monique Jacob Xavier Vianna; Isadora Nogueira; Ana Clara Rodrigues Abreu; Marcio Martinello Sanches; José Leonardo Santos-Jiménez; Raul Castro Carriello Rosa; Maitê Freitas Silva Vaslin; Fábio Gelape Faleiro; et al. (Crop Protection, 2023)

Intraplate records of a transform margin formation: Brittle deformation in the basement of the basins from the northeastern extremity of the Brazilian equatorial margin - Ricardo de Souza Rodrigues; Fernando César Alves da Silva; Alex Francisco Antunes (Journal of South American Earth Sciences, 2023)

Extruded urea levels in lamb supplementation in rainy tropical savanna conditions: the triad host-gastrointestinal nematodes-environment - Francisca Fernanda da Silva Roberto; Gelson dos Santos Difante; Roberto Germano Costa; Fernando de Almeida Borges; Luis Carlos Vinhas Ítavo; Camila Celeste Brandão Ferreira Ítavo; Neila Lidiany Ribeiro; Jéssica Gomes Rodrigues; Marislayne de Gusmão Pereira; Gabriela Oliveira de Aquino Monteiro; Emmanuel Lievio de Lima Véras; Antonio Leandro Chaves Gurgel; et al. (Tropical Animal Health and Production, 2023)

Use of a Concerning Sewage Sludge in the Manufacture of Organomineral Fertilizers: Agronomical Implications and Sustainable Disposal - Mayra Maniero Rodrigues; Douglas Gomes Viana; Guilherme Lucio Martins; Adijailton José de Souza; Júlio Flávio Osti; Fernando Carvalho Oliveira; Marcelo Corrêa Alves; Aline Renee Coscione; Jussara Borges Regitano (Journal of Soil Science and Plant Nutrition, 2023)

Genetic Diversity and Insights into the Distribution of Brown Howler Monkeys (Alouatta guariba Group) (Atelidae, Alouattinae) - Cintia Povill; Marcione B. de Oliveira; Filipe Vieira Santos de Abreu; Ricardo Lourenço de Oliveira; Fernando Araújo Perini; Cauê Monticelli; Cecilia Bueno; Edmilson dos Santos; Alcides Pissinatti; Cibele Rodrigues Bonvicino (International Journal of Primatology, 2023)

Environmental sensitivity index maps to manage oil spill risks: A review and perspectives - Fernando Mazo D'Affonseca; Fábio Augusto Gomes Vieira Reis; Claudia Vanessa dos Santos Corrêa; Arthur Wieczorek; Lucilia do Carmo Giordano; Mara Lúcia Marques; Flávio Henrique Rodrigues; Daiana Marques Costa; André de Andrade Kolya; Vinicius Mendes Veiga; Sarah Félix Santos; Laila Milani Magalhães; et al. (Ocean & Coastal Management, 2023)

Climatic seasons and time of the day influence thermoregulation and testicular hemodynamics in Santa Inês rams raised under humid tropical conditions - Juliana Nascimento Duarte Rodrigues; José Domingos Guimarães; Jeferson Ferreira Fonseca; Jurandy Mauro Penitente-Filho; Paulo Sergio Cerqueira Rangel; Camilo José Ramírez López; Rafael Souza Freitas; Erick Fonseca de Castilho; Luiz Fernando de Souza Rodrigues; Maria Emilia Franco Oliveira; Alexandre Rossetto Garcia (Journal of Thermal Biology, 2023)

Danger is just a click away–A survey on online shopping for glyphosate-based pesticides for gardening/horticulture - Fernando Rafael de Moura; Rafaela Danemberg de Oliveira; Eduarda Rosa Feijó; Flavio Manoel Rodrigues da Silva Júnior (Environmental Science & Policy, 2023)

Physicochemical and bacterial changes during composting of vegetable and animal-derived agro-industrial wastes - Guilherme Lucio Martins; Adijailton José de Souza; Lucas William Mendes; Júlia Brandão Gontijo; Mayra Maniero Rodrigues; Aline Renée Coscione; Fernando Carvalho Oliveira; Jussara Borges Regitano (Bioresource Technology, 2023)

Embryotoxicity of silica nanoparticles in the drug delivery of domperidone in zebrafish - Lorranny Pereira de Assis Valadares; Larise Caroline Oliveira Lima; Simone Maria Teixeira de Saboia-Morais; Tatiane Moraes Arantes; Fernando Henrique Cristovan; Naiton Martins da Silva; Aline Borges Andrade; Sandra Aparecida Benite Ribeiro; Benner Geraldo Alves; Barbara do Carmo Rodrigues Virote; Ives Charlie da Silva; Mônica Rodrigues Ferreira Machado (Aquatic Toxicology, 2023)

Using rice husk ash as a SiO2 source in the preparation of SiO2/Nb2O5 and SiO2/ZnS heterostructures for photocatalytic application - Cátia Liane Ücker; Suelen Rodrigues Almeida; Guilherme Kurz Maron; Neftali Lenin Villarreal Carreno; Fernando Dal Pont Morisso; Sergio da Silva Cava; Cristiane Wienke Raubach (Environmental Science and Pollution Research, 2023)

Correction: Oxidative damage in the Vesper mouse (Calomys laucha) exposed to a simulated oil spill—a multi-organ study - Krissia Aparecida de Almeida; Fernando Rafael de Moura; Juliane Ventura Lima; Edariane Menestrino Garcia; Ana Luíza Muccillo-Baisch; Paula Florencio Ramires; Julia Oliveira Penteado; Maria da Luz Mathias; Deodália Dias; Flavio Manoel Rodrigues da Silva Júnior (Ecotoxicology, 2023)

Oxidative damage in the Vesper mouse (Calomys laucha) exposed to a simulated oil spill—a multi-organ study - Krissia Aparecida de Almeida; Fernando Rafael de Moura; Juliane Ventura Lima; Edariane Menestrino Garcia; Ana Luíza Muccillo-Baisch; Paula Florencio Ramires; Julia Oliveira Penteado; Maria da Luz Mathias; Deodália Dias; Flavio Manoel Rodrigues da Silva Júnior (Ecotoxicology, 2023)

Means, motive and opportunity for biological invasions: Genetic introgression in a fungal pathogen - Flávia Rogério; Cock Van Oosterhout; Maisa Ciampi‐Guillardi; Fernando Henrique Correr; Guilherme Kenichi Hosaka; Sandrine Cros‐Arteil; Gabriel Rodrigues Alves Margarido; Nelson S. Massola Júnior; Pierre Gladieux (Molecular Ecology, 2023)
Invasions by fungal plant pathogens pose a significant threat to the health of agricultural ecosystems. Despite limited standing genetic variation, many invasive fungal species can adapt and spread rapidly, resulting in significant losses to crop yields. Here, we report on the population genomics of Colletotrichum truncatum , a polyphagous pathogen that can infect more than 460 plant species, and an invasive pathogen of soybean in Brazil. We study the whole‐genome sequences of 18 isolates representing 10 fields from two major regions of soybean production. We show that Brazilian C . truncatum is subdivided into three phylogenetically distinct lineages that exchange genetic variation through hybridization. Introgression affects 2%–30% of the nucleotides of genomes and varies widely between the lineages. We find that introgressed regions comprise secreted protein‐encoding genes, suggesting possible co‐evolutionary targets for selection in those regions. We highlight the inherent vulnerability of genetically uniform crops in the agro‐ecological environment, particularly when faced with pathogens that can take full advantage of the opportunities offered by an increasingly globalized world. Finally, we discuss “the means, motive and opportunity” of fungal pathogens and how they can become invasive species of crops. We call for more population genomic studies because such analyses can help identify geographical areas and pathogens that pose a risk, thereby helping to inform control strategies to better protect crops in the future.

Synthetic hydrazones: In silico studies and in vitro evaluation of the antileishmania potential - Valéria Carlos de Sousa; Rita de Cássia Viana Carvalho; Karla Germana dos Reis Barcelar; Danielly Silva de Melo; Jamylle Melo Nunes; Paulo Sérgio de Araújo Sousa; Jefferson Almeida Rocha; Cristiane Costa Lima; Arlan de Assis Gonsalves; Cleônia Roberta Melo Araújo; Marcília Pinheiro da Costa; Klinger Antônio da Franca Rodrigues; et al. (Toxicology in Vitro, 2023)

Assessing the precision irrigation potential for increasing crop yield and water savings through simulation - Silas Alves Souza; Lineu Neiva Rodrigues; Fernando França da Cunha (Precision Agriculture, 2023)

Genetic polymorphism detection in brazilian perennial cottons (Gossypium spp.) using an ISSR marker system and its application for molecular interspecific differentiation - Fernando dos Santos Araújo; Riselane de Lucena Alcântara Bruno; Nair Helena Castro Arriel; Everaldo Paulo de Medeiros; Liziane Maria de Lima; Mayara Andrade de Souza; Alberício Pereira de Andrade; Richeliel Albert Rodrigues Silva; Francival Cardoso Felix; Karialane da Silva Belarmino (Molecular Biology Reports, 2023)

Spatial non-stationarity in the distribution of fish species richness of tropical streams - Thiago Bernardi Vieira; Jorge Iván Sánchez-Botero; Danielle Sequeira Garcez; Sergio Maia Queiroz Lima; Carla Simone Pavanelli; Lilian Casatti; Welber Senteio Smith; Evanilde Benedito; Rosana Mazzoni; Paulo Santos Pompeu; Carlos Sérgio Agostinho; Luciano Fogaça de Assis Montag; et al. (Community Ecology, 2023)

Assessment of Health Risk and Presence of Metals in Water and Fish Samples from Doce River, Brazil, After Fundão Dam Collapse - Amanda Oliveira Mourão; Mayra Soares Santos; Alexandre Sylvio Vieira da Costa; Heberson Teixeira da Silva; Luiz Fernando Oliveira Maia; Márcia Cristina da Silva Faria; Mariandry del Vale Rodriguez Rodriguez; Jairo Lisboa Rodrigues (Archives of Environmental Contamination and Toxicology, 2023)

NEOTROPICAL FRESHWATER FISHES : A dataset of occurrence and abundance of freshwater fishes in the Neotropics - Lívia Helena Tonella; Renata Ruaro; Vanessa Salete Daga; Diego Azevedo Zoccal Garcia; Oscar Barroso Vitorino; Tatiana Lobato‐de Magalhães; Roberto Esser dos Reis; Fabio Di Dario; Ana Cristina Petry; Michael Maia Mincarone; Luciano Fogaça de Assis Montag; Paulo Santos Pompeu; et al. (Ecology, 2023)
The Neotropical region hosts 4225 freshwater fish species, ranking first among the world's most diverse regions for freshwater fishes. Our NEOTROPICAL FRESHWATER FISHES data set is the first to produce a large‐scale Neotropical freshwater fish inventory, covering the entire Neotropical region from Mexico and the Caribbean in the north to the southern limits in Argentina, Paraguay, Chile, and Uruguay. We compiled 185,787 distribution records, with unique georeferenced coordinates, for the 4225 species, represented by occurrence and abundance data. The number of species for the most numerous orders are as follows: Characiformes (1289), Siluriformes (1384), Cichliformes (354), Cyprinodontiformes (245), and Gymnotiformes (135). The most recorded species was the characid Astyanax fasciatus (4696 records). We registered 116,802 distribution records for native species, compared to 1802 distribution records for nonnative species. The main aim of the NEOTROPICAL FRESHWATER FISHES data set was to make these occurrence and abundance data accessible for international researchers to develop ecological and macroecological studies, from local to regional scales, with focal fish species, families, or orders. We anticipate that the NEOTROPICAL FRESHWATER FISHES data set will be valuable for studies on a wide range of ecological processes, such as trophic cascades, fishery pressure, the effects of habitat loss and fragmentation, and the impacts of species invasion and climate change. There are no copyright restrictions on the data, and please cite this data paper when using the data in publications.

Physical restoration of a minesoil after 10.6 years of revegetation - Pablo Miguel; Lizete Stumpf; Luiz Fernando Spinelli Pinto; Eloy Antonio Pauletto; Mateus Fonseca Rodrigues; Lucas Silva Barboza; Jéferson Diego Leidemer; Thábata Barbosa Duarte; Marília Alves Brito Pinto; Maria Bertaso de Garcia Fernandez; Livia Oliveira Islabão; Luisa Menezes da Silveira; et al. (Soil and Tillage Research, 2023)

Impact of different kernel grades on volatile compounds profile, fatty acids and oxidative quality of cashew nut oil - Amanda Rodrigues Leal; Ana Paula Dionísio; Fernando Antonio Pinto de Abreu; Gilleno Ferreira de Oliveira; Idila Maria da Silva Araújo; Hilton César Rodrigues Magalhães; Andressa Barbosa Leite; Emilly Kaiane Maia da Silva; Ronaldo Ferreira do Nascimento; Hélio Oliveira do Nascimento; Paulo Henrique Machado de Sousa (Food Research International, 2023)

When forest loss leads to biodiversity gain: Insights from the Brazilian Atlantic Forest - Julia Rodrigues Barreto; Renata Pardini; Jean Paul Metzger; Fernando Augusto Barbosa Silva; Elizabeth S. Nichols (Biological Conservation, 2023)

Bacterial identification in cerebrospinal fluid of domestic species with neurologic signs: a retrospective case-series study in 136 animals (2005–2021) - Márcio Garcia Ribeiro; Thiago Tourinho Pereira; Patrik Júnior de Lima Paz; Beatriz Oliveira de Almeida; Carmen S. Araújo Cerviño; Carolina Aparecida Rodrigues; Gabrielly Terra Sartori Santos; Larissa Maria de Souza Freire; Fábio Vinicius Ramos Portilho; Marcelo Fagali Árabe Filho; Natália Rodrigues Paschoal; Thaís Spessotto Bello; et al. (Brazilian Journal of Microbiology, 2023)

Sarcocyst Quantification and Viability: Freezing Treatment as an Alternative to Carcass Condemnation - Bibiana Rodrigues de Freitas; Isac Junior Roman; Bibiana Rossi Reis; Fernando de Souza Rodrigues; Patrícia Braünig; Juliana Felipetto Cargnelutti; Rodrigo Casquero Cunha; Fernanda Silveira Flôres Vogel (Acta Parasitologica, 2023)

Atlantic flower–invertebrate interactions: A data set of occurrence and frequency of floral visits - Danilo Boscolo; Bárbara Nobrega Rodrigues; Patrícia Alves Ferreira; Luciano Elsinor Lopes; Vinicius Rodrigues Tonetti; Isabela Cristhina Reis dos Santos; Juliana Akemi Hiruma‐Lima; Laura Nery; Karoline Baptista de Lima; Jéssica Perozi; André Victor Lucci Freitas; Blandina Felipe Viana; et al. (Ecology, 2023)
Encounters between flowers and invertebrates are key events for the functioning of tropical forests. Assessing the structure of networks composed of the interactions between those partners leads to a better understanding of ecosystem functioning and the effects of environmental factors on ecological processes. Gathering such data is, however, costly and time‐consuming, especially in the highly diverse tropics. We aimed to provide a comprehensive repository of available flower–invertebrate interaction information for the Atlantic Forest, a South American tropical forest domain. Data were obtained from published works and “gray literature,” such as theses and dissertations, as well as self‐reports by co‐authors. The data set has ~18,000 interaction records forming 482 networks, each containing between one and 1061 interaction links. Each network was sampled for about 200 h or less, with few exceptions. A total of 641 plant genera within 136 different families and 39 orders were reported, with the most abundant and rich families being Asteraceae, Fabaceae, and Rubiaceae. Invertebrates interacting with these plants were all arthropods from 10 orders, 129 families, and 581 genera, comprising 2419 morphotypes (including 988 named species). Hymenoptera was the most abundant and diverse order, with at least six times more records than the second‐ranked order (Lepidoptera). The complete data set shows Hymenoptera interacting with all plant orders and also shows Diptera, Lepidoptera, Coleoptera, and Hemiptera to be important nodes. Among plants, Asterales and Fabales had the highest number of interactions. The best sampled environment was forest (~8000 records), followed by pastures and crops. Savanna, grasslands, and urban environments (among others) were also reported, indicating a wide range of approaches dedicated to collecting flower–invertebrate interaction data in the Atlantic Forest domain. Nevertheless, most reported data were from forest understory or lower strata, indicating a knowledge gap about flower–invertebrate interactions at the canopy. Also, access to remote regions remains a limitation, generating sampling bias across the geographical range of the Atlantic Forest. Future studies in these continuous and hard‐to‐access forested areas will yield important new information regarding the interactions between flowers and invertebrates in the Atlantic Forest. There are no copyright restrictions on the data set. Please cite this data paper if the data are used in publications and teaching events.

Lethal and Sublethal Dose of Thiamethoxam and Its Effects on the Behavior of a Non-target Social Wasp - Paula Danyelle Crispim; Vinicius Edson Soares de Oliveira; Nathan Rodrigues Batista; Roberta Cornélio Ferreira Nocelli; William Fernando Antonialli-Junior (Neotropical Entomology, 2023)

Exposure to tolerable concentrations of aluminum triggers systemic and local oxidative stress and global proteomic modulation in the spinal cord of rats - Luciana Eiró-Quirino; Weslley Ferreira de Lima; Walessa Alana Bragança Aragão; Leonardo Oliveira Bittencourt; Paulo Fernando Santos Mendes; Rafael Monteiro Fernandes; Caroline Azulay Rodrigues; Aline Dionízio; Marília Afonso Rabelo Buzalaf; Marta Chagas Monteiro; Ana Cirovic; Aleksandar Cirovic; et al. (Chemosphere, 2023)

Clinical and Parasitological Evaluation of Ivermectin and Ivermectin + Pyrantel Against Oxyuris Equi in Equines - Vinícius D. Rodrigues; Mariana G. de Freitas; Bruno Milan; Guilherme H. Reckziegel; Dyego G.L. Borges; Matheus T.M. Nakatani; Juliane F. Tutija; Fernando de A. Borges (Journal of Equine Veterinary Science, 2023)

Sustainable thinking toward to industry's future combined with new knowledge on greenhouse effect mitigation generated by the grinding process - José Claudio Lopes; Guilherme Antonio de Carvalho; Guilherme Bressan Moretti; Benício Nacif Ávila; Matheus de Souza Rodrigues; Mateus Vinícius Garcia; Fernando Sabino Fonteque Ribeiro; Alessandro Roger Rodrigues; Luiz Eduardo de Angelo Sanchez; Eduardo Carlos Bianchi (Journal of Cleaner Production, 2023)

Local administration of curcumin-loaded nanoparticles enhances periodontal repair in vivo - Cindy Grace Perez-Pacheco; Natalie Aparecida Rodrigues Fernandes; Angelo Constantino Camilli; Danilo Paschoal Ferrarezi; Amanda Favoreto Silva; Mayara Cristina Zunareli; Camila Fernanda Amantino; Fernando Lucas Primo; Morgana Rodrigues Guimarães-Stabilli; Carlos Rossa Junior (Naunyn-Schmiedeberg's Archives of Pharmacology, 2023)

Triazoles with inhibitory action on P2X7R impaired the acute inflammatory response in vivo and modulated the hemostatic balance in vitro and ex vivo - Nathalia Gugick Pinheiro; Daniel Tadeu Gomes Gonzaga; Aldo Rodrigues da Silva; Andre Lopes Fuly; Natalia Lidmar von Ranke; Carlos Rangel Rodrigues; Betina Quintanilha Magalhães; Julianne Soares Pereira; Paulo Anastácio F. Pacheco; Ana Cláudia Silva; Vitor Francisco Ferreira; Fernando de Carvalho da Silva; et al. (Inflammation Research, 2023)

FK506 impairs neutrophil migration that results in increased polymicrobial sepsis susceptibility - Vanessa de Fátima Borges; Leticia Selinger Galant; Alexandre Kanashiro; Fernanda Vargas e Silva Castanheira; Valter Vinícius Silva Monteiro; Diego Ângelo Duarte; Filipe Camargo Rodrigues; Camila Meirelles de Souza Silva; Ayda Henriques Schneider; Guilherme Cesar Martelossi Cebinelli; Mikhael Haruo Fernandes de Lima; João Paulo de Biaso Viola; et al. (Inflammation Research, 2023)

Disentangling the role of soil bacterial diversity in phosphorus transformation in the maize rhizosphere - Yasmin Florentino Rodrigues; Fernando Dini Andreote; Antonio Marcos Miranda Silva; Armando Cavalcante Franco Dias; Rodrigo Gouvea Taketani; Simone Raposo Cotta (Applied Soil Ecology, 2023)

Gap-filling of daily precipitation and streamflow time series: a method comparison at random and sequential gaps - Letícia Lopes Martins; Wander Araújo Martins; Iam Caio de Abreu Rodrigues; Ana Carolina Freitas Xavier; Jener Fernando Leite de Moraes; Gabriel Constantino Blain (Hydrological Sciences Journal, 2023)

Functional composition enhances aboveground carbon stock during tropical late-secondary forest succession - Alice Cristina Rodrigues; Pedro Manuel Villa; Fernando Silla; Lhoraynne Pereira Gomes; João Augusto Alves Meira-Neto; Carlos Moreira M. E. Torres; Andreza Viana Neri (Plant Biosystems, 2023)

Dietary glutamine improves growth and intestinal morphology of juvenile GIFT tilapia (Oreochromis niloticus) but has limited effects on innate immunity and antioxidant capacity - Pedro L.P.F. Carvalho; William dos S. Xavier; Matheus G. Guimarães; Edgar J.D. Rodrigues; Wilson M. Furuya; Fernando Y. Yamamoto; Luiz E. Pezzato; Delbert M. Gatlin; Margarida M. Barros (Aquaculture, 2023)

Oblique rifting along transfer zones: The structural evolution model revealed by physical modeling - Ricardo de Souza Rodrigues; Fernando César Alves da Silva; Marilia Barbosa Venâncio (Journal of South American Earth Sciences, 2023)

Detrital zircon U–Pb analysis constrain the depositional age and provenance of Cryogenian glacial successions of the Macaúbas group in the northeastern Araçuaí orogen, eastern Brazil - Fernando Estevão Rodrigues Crincoli Pacheco; Fabrício de Andrade Caxito; Maria Eugênia Souza; Ciro Couto Bento; Antônio Pedrosa-Soares; Cristiano de Carvalho Lana (Journal of South American Earth Sciences, 2023)

Exposure to polystyrene nanoplastics induces an anxiolytic-like effect, changes in antipredator defensive response, and DNA damage in Swiss mice - Abraão Tiago Batista Guimarães; Ítalo Nascimento Freitas; Nabisab Mujawar Mubarak; Md. Mostafizur Rahman; Fernando Postalli Rodrigues; Aline Sueli de Lima Rodrigues; Damià Barceló; Abu Reza Md. Towfiqul Islam; Guilherme Malafaia (Journal of Hazardous Materials, 2023)

2030 Agenda: discussion on Brazilian priorities facing air pollution and climate change challenges - Fernando Rafael de Moura; Flavio Manoel Rodrigues da Silva Júnior (Environmental Science and Pollution Research, 2023)

Geographic patterns of tree dispersal modes in Amazonia and their ecological correlates - Diego F. Correa; Pablo R. Stevenson; Maria Natalia Umaña; Luiz de Souza Coelho; Diógenes de Andrade Lima Filho; Rafael P. Salomão; Iêda Leão do Amaral; Florian Wittmann; Francisca Dionízia de Almeida Matos; Carolina V. Castilho; Oliver L. Phillips; Juan Ernesto Guevara; et al. (Global Ecology and Biogeography, 2023)
Aim To investigate the geographic patterns and ecological correlates in the geographic distribution of the most common tree dispersal modes in Amazonia (endozoochory, synzoochory, anemochory and hydrochory). We examined if the proportional abundance of these dispersal modes could be explained by the availability of dispersal agents (disperser‐availability hypothesis) and/or the availability of resources for constructing zoochorous fruits (resource‐availability hypothesis). Time period Tree‐inventory plots established between 1934 and 2019. Major taxa studied Trees with a diameter at breast height (DBH) ≥ 9.55 cm. Location Amazonia, here defined as the lowland rain forests of the Amazon River basin and the Guiana Shield. Methods We assigned dispersal modes to a total of 5433 species and morphospecies within 1877 tree‐inventory plots across terra‐firme, seasonally flooded, and permanently flooded forests. We investigated geographic patterns in the proportional abundance of dispersal modes. We performed an abundance‐weighted mean pairwise distance (MPD) test and fit generalized linear models (GLMs) to explain the geographic distribution of dispersal modes. Results Anemochory was significantly, positively associated with mean annual wind speed, and hydrochory was significantly higher in flooded forests. Dispersal modes did not consistently show significant associations with the availability of resources for constructing zoochorous fruits. A lower dissimilarity in dispersal modes, resulting from a higher dominance of endozoochory, occurred in terra‐firme forests (excluding podzols) compared to flooded forests. Main conclusions The disperser‐availability hypothesis was well supported for abiotic dispersal modes (anemochory and hydrochory). The availability of resources for constructing zoochorous fruits seems an unlikely explanation for the distribution of dispersal modes in Amazonia. The association between frugivores and the proportional abundance of zoochory requires further research, as tree recruitment not only depends on dispersal vectors but also on conditions that favour or limit seedling recruitment across forest types.

Small mammals from the C aatinga: A dataset for the B razilian semiarid biome - Anna Ludmilla da Costa‐Pinto; Ricardo S. Bovendorp; Adriana Bocchiglieri; Aldo Caccavo; Ana Cláudia Delciellos; Ana Cláudia Malhado; Ana Karolina Rodrigues de Almeida; Caryne Braga; Diogo Loretto; Edeltrudes Maria Valadares Calaça Câmara; Fernando Heberson Menezes; Gabby Guilhon; et al. (Ecology, 2023)
The Caatinga is an exclusively Brazilian biome, and is the largest and most biodiverse Seasonal Tropical Dry Forest in the world. Despite that, the mammalian fauna, especially small mammals, is the least studied of all Brazilian biomes. In order to fill gaps and provide detailed information on small mammals (Didelphimorphia, Rodentia) in the Caatinga biome, we compiled reliable records focusing on richness, composition and some biometric data. These records came from mammal collections, papers, theses, books, and unpublished data, prioritizing records with vouchers housed in scientific collections. We compiled a total of 3133 records from 816 locations, resulting in a richness of 47 native species (12 marsupials and 35 rodents, plus three exotic rodents, Rattus rattus , Rattus norvegicus , and Mus musculus ). This dataset includes records of three new species for the biome and its transition zone: the rodents Calomys mattevii , Holochilus oxe , and Nectomys squamipes . Of the total number of records, 1808 (57.71%) are from consulting activities, 95 (3.03%) are from zoonoses studies and 104 (3.32%) are from the National Plague Service (SNP). All nine Brazilian states with territory in the Caatinga have sampling data for small mammals, but the number of records and localities are unevenly distributed, with the state of Rio Grande do Norte having the lowest number of records and locations sampled. Our dataset is the first of its kind for the Caatinga biome and has considerable potential value for studies of habitat use, landscape ecology, macroecology, biogeography, and conservation. There are no copyright restrictions on the data. Please cite this data paper when the data are used in publications. We also request that researchers and teachers inform us of how they are using the data.

Rock n' Seeds: A database of seed functional traits and germination experiments from Brazilian rock outcrop vegetation - Carlos A. Ordóñez‐Parra; Roberta L. C. Dayrell; Daniel Negreiros; Antônio C. S. Andrade; Letícia G. Andrade; Yasmine Antonini; Leilane C. Barreto; Fernanda de V. Barros; Vanessa da Cruz Carvalho; Blanca Auxiliadora Dugarte Corredor; Antônio Cláudio Davide; Alexandre A. Duarte; et al. (Ecology, 2023)
Advancing functional ecology depends fundamentally on the availability of data on reproductive traits, including those from tropical plants, which have been historically underrepresented in global trait databases. Although some valuable databases have been created recently, they are mainly restricted to temperate areas and vegetative traits such as leaf and wood traits. Here, we present Rock n' Seeds, a database of seed functional traits and germination experiments from Brazilian rock outcrop vegetation, recognized as outstanding centers of diversity and endemism. Data were compiled through a systematic literature search, resulting in 103 publications from which seed functional traits were extracted. The database includes information on 16 functional traits for 383 taxa from 148 genera, 50 families, and 25 orders. These 16 traits include two dispersal, six production, four morphological, two biophysical, and two germination traits—the major axes of the seed ecological spectrum. The database also provides raw data for 48 germination experiments, for a total of 10,187 records for 281 taxa. Germination experiments in the database assessed the effect of a wide range of abiotic and biotic factors on germination and different dormancy‐breaking treatments. Notably, 8255 of these records include daily germination counts. This input will facilitate synthesizing germination data and using this database for a myriad of ecological questions. Given the variety of seed traits and the extensive germination information made available by this database, we expect it to be a valuable resource advancing comparative functional ecology and guiding seed‐based restoration and biodiversity conservation in tropical megadiverse ecosystems. There are no copyright restrictions on the data; please cite this paper when using the current data in publications; also the authors would appreciate notification of how the data are used in publications.

Substrate gleaning: Plasticity in the foraging and echolocation behavior of the bat Molossus molossus - Crasso Paulo Bosco Breviglieri; Fernando Rodrigues da Silva (Ecology, 2023)

A molecular perspective on the systematics and distribution of Loxopholis lizards in South and Central America, with advances on the biogeography of the tribe Ecpleopodini (Gymnophthalmidae: Squamata) - Sergio Marques-Souza; Katia Cristina M. Pellegrino; Tuliana O. Brunes; Fernando J. M. Rojas-Runjaic; Miguel Trefaut Rodrigues (Systematics and Biodiversity, 2022)

Variability of the β-casein gene polymorphism in Curraleiro Pé-Duro cattle: a geographical genetics approach - Marcelo Corrêa da Silva; Ana Beatriz Bezerra Souza; José Bento Sterman Ferraz; Fernando Oliveira Bussiman; Matheus Henrique Dias Rodrigues; Susana Queiroz Santos Mello; Rachel dos Santos Bueno; Minos Esperandio de Carvalho; Raryanne Dias Folhas; Helcileia Dias Santos; Leandro Lopes Nepomuceno; Jorge Luís Ferreira (Tropical Animal Health and Production, 2022)

Apparent prevalence and risk factors for bovine tuberculosis in the state of Paraná, Brazil: an assessment after 18 years since the beginning of the Brazilian program - Diego Leonardo Rodrigues; Elenice Aparecida Amorim; Fernando Ferreira; Marcos Amaku; Oswaldo Santos Baquero; José Henrique de Hildebrand e Grisi Filho; Ricardo Augusto Dias; Marcos Bryan Heinemann; Evelise Oliveira Telles; Vitor Salvador Picão Gonçalves; Christopher Compton; José Soares Ferreira Neto (Tropical Animal Health and Production, 2022)
Bovine tuberculosis (bTB) impacts considerably animal production and one health worldwide. To describe the prevalence, risk factors, and spatial pattern of the disease in the state of Paraná, Brazil, a cross-sectional study was conducted from September 2018 to February 2019. The area was divided into seven regions. Within each region, farms were randomly selected, and a predetermined number of cows was selected and tested by a comparative cervical tuberculin test. 17,210 animals were tested across 1757 farms. Herd prevalence of bTB-infected herds in Paraná was 2.5% [1.87–3.00%]. It has varied from 0.8 to 3.98% among seven regions, with clustering being detected in the west, central, and northeast areas. Animal prevalence was 0.35% [0.21–0.59%] and has varied from 0.08 to 0.6% among the pre-set regions. No major shifts in the prevalence of bTB were detected since 2007. Large-sized herds, dairy production, and feeding with whey were detected to be correlated with the presence of bTB. Exclusively among dairy herds, veterinary assistance from cooperatives, possession of self-owned equipment to cool milk, and feeding with whey were correlated with the disease. Considering these results, it is recommended that the state of Paraná seek to implement a surveillance system for the detection of bTB-infected herds transforming them into free ones, if possible, incorporating elements of risk-based surveillance. Health education is also recommended to inform farmers about the risks of introducing animals without testing and of feeding raw whey to calves.

Evaluation of the toxicity of di-iso-pentyl-phthalate (DiPeP) using the fish Danio rerio as an experimental model - Sheila Gabriel Santos; Marília Cristina Oliveira Souza; Fernando Barbosa-Junior; Maritana Mela Prodocimo; Fellip Rodrigues Marcondes; William Almeida; Marta Margarete Cestari; Luciana Rodrigues Souza-Bastos; Anderson Joel Martino-Andrade; Izonete Cristina Guiloski (Environmental Science and Pollution Research, 2022)

Proportions of concentrate and rehydrated ground grain corn silage at different storage times for better use of starch by lambs - Gilmara Santos Guimarães; José Augusto Gomes Azevedo; Fernando Correia Cairo; Cristiane Simplício da Silva; Lígia Lins Souza; Flavia dos Santos Nunes; Gleidson Giordano Pinto de Carvalho; Gherman Garcia Leal de Araújo; Robério Rodrigues Silva (Tropical Animal Health and Production, 2022)

The potential of animal manure management pathways toward a circular economy: a bibliometric analysis - Camila Ester Hollas; Heloisa Campeão Rodrigues; Vitoria Mitsue Agliardi Oyadomari; Alice Chiapetti Bolsan; Bruno Venturin; Gabriela Bonassa; Deisi Cristina Tápparo; Hélen Caroline Zonta Abilhôa; João Fernando Ferri da Silva; William Michelon; Jadiane Paola Cavaler; Fabiane Goldschmidt Antes; et al. (Environmental Science and Pollution Research, 2022)

Evaluating loggerhead sea turtle (Caretta caretta) bycatch in the small-scale fisheries of Cabo Verde - Samir Martins; Manjula Tiwari; Fernando Rocha; Edson Rodrigues; Ravidson Monteiro; Sónia Araújo; Elena Abella; Nuno de Santos Loureiro; Leo J. Clarke; Adolfo Marco (Reviews in Fish Biology and Fisheries, 2022)

Genetic gains in Passiflora for resistance to cowpea aphid-borne mosaic virus using recurrent selection - Débora Souza Mendes; Alexandre Pio Viana; Eileen Azevedo Santos; Natan Ramos Cavalcante; Cleidiane Alves Rodrigues; Joameson Antunes Lima; Ravena Ferreira Vidal; Fernando Henrique de Barros Walter; Luan Baritiello da Silva Bezerra; Marcelo Eiras; Huarrisson Azevedo Santos (Euphytica, 2022)

Viral isolation allows characterization of early samples of SARS-CoV-2 lineage B1.1.33 with unique mutations (S: H655Y and T63N) circulating in Southern Brazil in 2020 - Juliana Schons Gularte; Mariana Soares da Silva; Micheli Filippi; Meriane Demoliner; Karoline Schallenberger; Alana Witt Hansen; Vyctoria Malayhka de Abreu Góes Pereira; Fágner Henrique Heldt; Viviane Girardi; Matheus Nunes Weber; Paula Rodrigues de Almeida; Bruno Lopes Abbadi; et al. (Brazilian Journal of Microbiology, 2022)

Ingoldian fungal assemblages from Brazilian rainforests, shrubland and savanna - Patrícia Oliveira Fiuza; Flavia Rodrigues Barbosa; Adriana Oliveira Medeiros; Luís Fernando Pascholati Gusmão (New Zealand Journal of Botany, 2022)
Ingoldian fungi are a dominant group in aquatic environments. However, they are poorly known and studied, especially in the tropics. To increase knowledge about their diversity and distribution, samples of foam and decaying submerged leaves were collected from 12 areas in Brazil across four biomes (Amazon, Atlantic Forest, Caatinga, and Cerrado). Slides were deposited in the HUEFS Herbarium. Thirty‐five taxa were identified from foam and 24 from leaf spore suspension. These were distributed in five classes, mostly belonging to Ascomycota , with Leotiomycetes being the most representative class. Angulospora aquatica, Biflagellosporella amazonensis , Isthmotricladia laeensis and Lateriramulosa bi‐inflata are new records for Brazil; Variocladium rangiferinum and Tricladium fuscum are new records for the Neotropics; and Polylobatispora deltoidea is a new record for the Americas. Description, illustration, and geographical distribution details are provided for the new records. The study showed a high richness of Ingoldian fungi and provides a basis for determining the biodiversity and ultimate conservation of the studied areas.

AMAZONIA CAMTRAP: A data set of mammal, bird, and reptile species recorded with camera traps in the Amazon forest - Ana Carolina Antunes; Anelise Montanarin; Diogo Maia Gräbin; Erison Carlos dos Santos Monteiro; Fernando Ferreira de Pinho; Guilherme Costa Alvarenga; Jorge Ahumada; Robert B. Wallace; Emiliano Esterci Ramalho; Adrian Paul Ashton Barnett; Alex Bager; Alexandre Martins Costa Lopes; et al. (Ecology, 2022)
The Amazon forest has the highest biodiversity on Earth. However, information on Amazonian vertebrate diversity is still deficient and scattered across the published, peer‐reviewed, and gray literature and in unpublished raw data. Camera traps are an effective non‐invasive method of surveying vertebrates, applicable to different scales of time and space. In this study, we organized and standardized camera trap records from different Amazon regions to compile the most extensive data set of inventories of mammal, bird, and reptile species ever assembled for the area. The complete data set comprises 154,123 records of 317 species (185 birds, 119 mammals, and 13 reptiles) gathered from surveys from the Amazonian portion of eight countries (Brazil, Bolivia, Colombia, Ecuador, French Guiana, Peru, Suriname, and Venezuela). The most frequently recorded species per taxa were: mammals: Cuniculus paca (11,907 records); birds: Pauxi tuberosa (3713 records); and reptiles: Tupinambis teguixin (716 records). The information detailed in this data paper opens up opportunities for new ecological studies at different spatial and temporal scales, allowing for a more accurate evaluation of the effects of habitat loss, fragmentation, climate change, and other human‐mediated defaunation processes in one of the most important and threatened tropical environments in the world. The data set is not copyright restricted; please cite this data paper when using its data in publications and we also request that researchers and educators inform us of how they are using these data.

On the replacement of traditional stabilizers by guaiacol in environmentally safe nitrocellulose-based propellants - Rodrigo L. B. Rodrigues; Ana Paula da Silva; Rogério Rosato; Maurício F. Lemos; Fernando C. Peixoto; Tanos C. C. França; Letivan G. Mendonça Filho (Clean Technologies and Environmental Policy, 2022)

MAMMALS IN PORTUGAL : A data set of terrestrial, volant, and marine mammal occurrences in P ortugal - Clara Grilo; Beatriz C. Afonso; Filipe Afonso; Marta Alexandre; Sara Aliácar; Ana Almeida; Ivan Prego Alonso; Francisco Álvares; Paulo Alves; Paulo Célio Alves; Pedro Alves; Anabela Amado; et al. (Ecology, 2022)
Mammals are threatened worldwide, with ~26% of all species being included in the IUCN threatened categories. This overall pattern is primarily associated with habitat loss or degradation, and human persecution for terrestrial mammals, and pollution, open net fishing, climate change, and prey depletion for marine mammals. Mammals play a key role in maintaining ecosystems functionality and resilience, and therefore information on their distribution is crucial to delineate and support conservation actions. MAMMALS IN PORTUGAL is a publicly available data set compiling unpublished georeferenced occurrence records of 92 terrestrial, volant, and marine mammals in mainland Portugal and archipelagos of the Azores and Madeira that includes 105,026 data entries between 1873 and 2021 (72% of the data occurring in 2000 and 2021). The methods used to collect the data were: live observations/captures (43%), sign surveys (35%), camera trapping (16%), bioacoustics surveys (4%) and radiotracking, and inquiries that represent less than 1% of the records. The data set includes 13 types of records: (1) burrows | soil mounds | tunnel, (2) capture, (3) colony, (4) dead animal | hair | skulls | jaws, (5) genetic confirmation, (6) inquiries, (7) observation of live animal (8), observation in shelters, (9) photo trapping | video, (10) predators diet | pellets | pine cones/nuts, (11) scat | track | ditch, (12) telemetry and (13) vocalization | echolocation. The spatial uncertainty of most records ranges between 0 and 100 m (76%). Rodentia ( n =31,573) has the highest number of records followed by Chiroptera ( n = 18,857), Carnivora ( n = 18,594), Lagomorpha ( n = 17,496), Cetartiodactyla ( n = 11,568) and Eulipotyphla ( n = 7008). The data set includes records of species classified by the IUCN as threatened (e.g., Oryctolagus cuniculus [ n = 12,159], Monachus monachus [ n = 1,512], and Lynx pardinus [ n = 197]). We believe that this data set may stimulate the publication of other European countries data sets that would certainly contribute to ecology and conservation‐related research, and therefore assisting on the development of more accurate and tailored conservation management strategies for each species. There are no copyright restrictions; please cite this data paper when the data are used in publications.

Which birds are Brazilians seeing on urban and non-urban feeders? An analysis based on a collective online birding - Eduardo Roberto Alexandrino; Thaís Abreu Camboim; Flávia Guimarães Chaves; Alex Augusto Abreu Bovo; Marco Aurélio Galvão da Silva; Daniela Alves Maia da Silva; Margi Moss; Tatiana Pongiluppi Souza; Clarissa de Oliveira Santos; Caio Bezerra de Mattos Brito; Maristela Camolesi Alcantara; Karlla V. C. Barbosa; et al. (Ornithology Research, 2022)

Multilocus phylogeography of the endemic and endangered angular angelshark (Squatina guggenheim) in the Southwest Atlantic Ocean - Ingrid Vasconcellos Bunholi; Bruno Lopes da Silva Ferrette; Rodrigo Rodrigues Domingues; Matheus Marcos Rotundo; Juan Martín Cuevas; Mirta García; Sebastián Gómez; Renato Hajenius Aché de Freitas; Claudio Oliveira; Fausto Foresti; Fernando Fernandes Mendonça (Hydrobiologia, 2022)

Phosphorus in soils and fluvial sediments from a Cerrado biome watershed under agricultural expansion - Fernando Braga Rimá; Yuri Jacques Agra Bezerra da Silva; Marcos Paulo Rodrigues Teixeira; Angelo Jamil Maia; Kamylla Gonçalves Oliveira Assis; Rayanna Jacques Agra Bezerra da Silva; Valdomiro Severino de Souza Júnior; Ygor Jacques Agra Bezerra da Silva; José Wellington Batista Lopes; Ronny Sobreira Barbosa; Vijay P. Singh (Environmental Monitoring and Assessment, 2022)

Klebsiella-induced infections in domestic species: a case-series study in 697 animals (1997–2019) - Márcio Garcia Ribeiro; Amanda Bonalume Cordeiro de Morais; Ana Carolina Alves; Carmen Alicia Daza Bolaños; Carolina Lechinski de Paula; Fábio Vinicius Ramos Portilho; Geraldo de Nardi Júnior; Gustavo Henrique Batista Lara; Lorrayne de Souza Araújo Martins; Lucieny Sierra Moraes; Rafaela Mastrangelo Risseti; Simony Trevizan Guerra; et al. (Brazilian Journal of Microbiology, 2022)

Escherichia coli, Species C Human Adenovirus, and Enterovirus in Water Samples Consumed in Rural Areas of Goiás, Brazil - Fernando Santos Lima; Paulo Sérgio Scalize; Ellen Flávia Moreira Gabriel; Raylane Pereira Gomes; Aline Rodrigues Gama; Meriane Demoliner; Fernando Rosado Spilki; José Daniel Gonçalves Vieira; Lilian Carla Carneiro (Food and Environmental Virology, 2022)

Role of the YehD fimbriae in the virulence‐associated properties of enteroaggregative Escherichia coli - Jorge Soria‐Bustos; Waleska Saitz; Abraham Medrano; Cristina Lara‐Ochoa; Zineb Bennis; Valerio Monteiro‐Neto; Camilla Itapary dos Santos; Josias Rodrigues; Rodrigo T. Hernandes; Jorge A. Yáñez; Javier Torres; Fernando Navarro‐García; et al. (Environmental Microbiology, 2022)
Summary The interaction of enteroaggregative Escherichia coli (EAEC) strains with the colonic gut mucosa is characterized by the ability of the bacteria to form robust biofilms, to bind mucin, and induce a local inflammatory response. These events are mediated by a repertoire of five different aggregative adherence fimbriae variants (AAF/I‐V) typically encoded on virulence plasmids. In this study, we report the production in EAEC strains of a new Y eh D f imbriae (YDF), which is encoded by the chromosomal gene cluster yehABCD , also present in most E. coli strains. Immuno‐labelling of EAEC strain 042 with anti‐AAF/II and anti‐YDF antibodies demonstrated the presence of both AAF/II and YDF on the bacterial surface. We investigated the role of YDF in cell adherence, biofilm formation, colonization of spinach leaves, and induction of pro‐inflammatory cytokines release. To this aim, we constructed yehD deletion mutants in different EAEC backgrounds (strains 17‐2, 042, 55989, C1010, 278‐1, J7) each harbouring one of the five AAFs. The effect of the YDF mutation was strain dependent and AAF independent as the lack of YDF had a different impact on the phenotypes manifested by the different EAECs tested. Expression of the yehABCD operon in a E. coli K12 ORN172 showed that YDF is important for biofilm formation but not for adherence to HeLa cells. Lastly, screening of pro‐inflammatory cytokines in supernatants of Caco‐2 cells infected with EAEC strains 042 and J7 and their isogenic Δ yehD mutants showed that these mutants were significantly defective in release of IL‐8 and TNF‐α. This study contributes to the understanding of the complex and diverse mechanisms of adherence of EAEC strains and identifies a new potential target for preventive measures of gastrointestinal illness caused by EAEC and other E. coli pathogroups.

ATLANTIC ANTS: a data set of ants in Atlantic Forests of South America - Rogério R. Silva; Felipe Martello; Rodrigo Machado Feitosa; Otávio Guilherme M. Silva; Lívia Pires do Prado; Carlos Roberto F. Brandão; Emília Zoppas de Albuquerque; Maria Santina C. Morini; Jacques Hubert Charles Delabie; Erison Carlos dos Santos Monteiro; Agripino Emanuel Oliveira Alves; Alexander L. Wild; et al. (Ecology, 2022)
Ants, an ecologically successful and numerically dominant group of animals, play key ecological roles as soil engineers, predators, nutrient recyclers, and regulators of plant growth and reproduction in most terrestrial ecosystems. Further, ants are widely used as bioindicators of the ecological impact of land use. We gathered information of ant species in the Atlantic Forest of South America. The ATLANTIC ANTS data set, which is part of the ATLANTIC SERIES data papers, is a compilation of ant records from collections (18,713 records), unpublished data (29,651 records), and published sources (106,910 records; 1,059 references), including papers, theses, dissertations, and book chapters published from 1886 to 2020. In total, the data set contains 153,818 ant records from 7,636 study locations in the Atlantic Forest, representing 10 subfamilies, 99 genera, 1,114 ant species identified with updated taxonomic certainty, and 2,235 morphospecies codes. Our data set reflects the heterogeneity in ant records, which include ants sampled at the beginning of the taxonomic history of myrmecology (the 19th and 20th centuries) and more recent ant surveys designed to address specific questions in ecology and biology. The data set can be used by researchers to develop strategies to deal with different macroecological and region‐wide questions, focusing on assemblages, species occurrences, and distribution patterns. Furthermore, the data can be used to assess the consequences of changes in land use in the Atlantic Forest on different ecological processes. No copyright restrictions apply to the use of this data set, but we request that authors cite this data paper when using these data in publications or teaching events.

There is more than chitin synthase in insect resistance to benzoylureas: molecular markers associated with teflubenzuron resistance in Spodoptera frugiperda - Antonio Rogério Bezerra do Nascimento; Vitor Antonio Corrêa Pavinato; Juliana Gonzales Rodrigues; Karina Lucas Silva-Brandão; Fernando Luis Consoli; Andrew Michel; Celso Omoto (Journal of Pest Science, 2022)

The antileishmanial activity of the antarctic brown alga Ascoseira mirabilis Skottsberg - Leandro da Costa Clementino; Fernando Bombarda Oda; Thaiz Rodrigues Teixeira; Renata Spagolla Napoleão Tavares; Pio Colepicolo; André Gonzaga dos Santos; Hosana Maria Debonsi; Márcia A. S. Graminha (Natural Product Research, 2021)

Sugarcane Resilience to Recurrent Water Deficit is Dependent on the Systemic Acclimation of Leaf Physiological Traits - Fernando Henrique Silva Garcia; Marcelo Rodrigues; João Paulo Pennacchi; Ane Marcela das Chagas Mendonça; Daynara Aparecida Rodrigues Gonçalves; Nayara Cristina de Melo; João Paulo Rodrigues Alves Delfino Barbosa (Tropical Plant Biology, 2021)

Soil Microbiological Attributes and Soybean Grain Yield in Succession to Corn Intercropped with Forage in the Maranhão Eastern Cerrado - Smaiello Flores da Conceição Borges dos Santos; Henrique Antunes de Souza; Raimundo Bezerra de Araújo Neto; Edvaldo Sagrilo; Ane Caroline Melo Ferreira; Suzane Pereira Carvalho; Lucelia de Cássa Rodrigues de Brito; Luiz Fernando Carvalho Leite (International Journal of Plant Production, 2021)

Dynamics of bacterial and archaeal communities along the composting of tannery sludge - Ademir Sergio Ferreira Araujo; Arthur Prudêncio de Araujo de Pereira; Jadson Emanuel Lopes Antunes; Louise Melo de Souza Oliveira; Wanderley José de Melo; Sandra Mara Barbosa Rocha; Marineide Rodrigues do Amorim; Fabio Fernando Araujo; Vania Maria Maciel Melo; Lucas William Mendes (Environmental Science and Pollution Research, 2021)

Reinfection cases by closely related SARS-CoV-2 lineages in Southern Brazil - Juliana Schons Gularte; Mariana Soares da Silva; Meriane Demoliner; Alana Witt Hansen; Fágner Henrique Heldt; Flávio Silveira; Micheli Filippi; Vyctoria Malayhka de Abreu Góes Pereira; Francini Pereira da Silva; Larissa Mallmann; Pietra Fink; Jéssica Luísa Laux; et al. (Brazilian Journal of Microbiology, 2021)

Isoquinoline alkaloids reduce beta-amyloid peptide toxicity in Caenorhabditis elegans - Wamberto Alristenio Moreira de Almeida; Jean Paulo de Andrade; Daisy Sotero Chacon; Cecília Rodrigues Lucas; Estela Mariana; Leandro de Santis Ferreira; Thais Guaratini; Euzebio Guimarães Barbosa; José Angelo Zuanazzi; Fernando Hallwass; Warley de Souza Borges; Riva de Paula Oliveira; et al. (Natural Product Research, 2021)

Proteome of Erythroxylum pungens (Erythroxylaceae): an endemic species of the semiarid Caatinga - Daisy Sotero Chacon; Ivanice Bezerra da Silva; Taffarel Melo Torres; Gabrielle Macedo Pereira; Letícia Gondim Lambert Moreira; Luiz Fernando Rodrigues de Souza; Fernanda Priscila Santos Reginaldo; Alan de Araújo Roque; José Angelo S. Zuanazzi; Renata Libonati; Julia A. Rodrigues; Filippe L.M Santos; et al. (Plant Biosystems, 2021)

Chemical and morpho-structural characterization of atmospheric aerosol (PM10 and PM2.5) in a city of São Paulo state, Brazil - Bruno Trevizan Franzin; Filipe Corrêa Guizellini; Ossamu Hojo; Iêda Aparecida Pastre; Mary Rosa Rodrigues de Marchi; Hugo Félix Silva; Fernando Luis Fertonani; Cristina Maria Oliveira (Environmental Science and Pollution Research, 2021)

Low-cost Gent type sampler constructed for urban atmospheric aerosol sampling - Bruno Trevizan Franzin; Ossamu Hojo; Maicon Roberto Ferreira; Maria Cristina Forti; Carlos Daniel Meneghetti; Mary Rosa Rodrigues de Marchi; Cristina Maria Roque Ramiro de Oliveira; Fernando Luis Fertonani (Environmental Science and Pollution Research, 2021)

Seroprevalence and risk factors for bovine brucellosis in the state of Paraná, Brazil: an analysis after 18 years of ongoing control measures - Diego Leonardo Rodrigues; Elenice Aparecida Amorim; Fernando Ferreira; Marcos Amaku; Oswaldo Santos Baquero; José Henrique de Hildebrand e Grisi Filho; Ricardo Augusto Dias; Marcos Bryan Heinemann; Evelise Oliveira Telles; Vitor Salvador Picão Gonçalves; Cord Heuer; José Soares Ferreira Neto (Tropical Animal Health and Production, 2021)

Effects of supplementation on production and age anticipation at first mating of ewe lambs in tropical pastures - Thais Fernanda Farias de Souza Arco; Camila Celeste Brandão Ferreira Ítavo; Luís Carlos Vinhas Ítavo; Maria Inês Lenz Souza; Alexandre Menezes Dias; Gelson dos Santos Difante; Eliane Vianna da Costa e Silva; Fernando de Almeida Borges; Dyego Gonçalves Lino Borges; Kedma Leonora da Silva Monteiro Ferelli; Bruna Junqueira Rodrigues; Aline Aparecida da Silva Miguel; et al. (Tropical Animal Health and Production, 2021)

Combined and isolated effects of alcohol consumption and sleep deprivation on maximal strength, muscle endurance and aerobic exercise performance in healthy men: a cross-over randomized controlled trial - Rodrigo Rodrigues; Rodrigo de Azevedo Franke; Bruno C. Teixeira; Rodrigo C. O. Macedo; André Luiz Lopes; Fernando Diefenthaeler; Álvaro Reischak-Oliveira; Bruno Manfredini Baroni; Marco Aurélio Vaz (Sleep and Biological Rhythms, 2021)

Global phylogeography of sailfish: deep evolutionary lineages with implications for fisheries management - Bruno Lopes da Silva Ferrette; Bruno Mourato; Fábio Hissa Vieira Hazin; Freddy Arocha; Samuel Mackey Williams; Carlos Egberto Rodrigues Junior; Fábio Porto-Foresti; Alberto Ferreira de Amorim; Matheus Marcos Rotundo; Rui Coelho; John P. Hoolihan; Fambaye Ngom Sow; et al. (Hydrobiologia, 2021)

A fast and direct determination of bisphenol S in thermal paper samples using paper spray ionization mass spectrometry - Ricardo Alves Bernardo; Jean Carlos Pereira Sousa; Matheus Gallimberti; Fernando Barbosa Junior; Boniek Gontijo Vaz; Andréa Rodrigues Chaves (Environmental Science and Pollution Research, 2021)

Jundiá Fish Skin ( Rhamdia quelen ): An Unexplored By-product with Great Potential to Be Used as a Novel Source of Collagen - Camila Giacomelli Da Silva; Angela Souza Rodrigues; Daniela Pedrolo Weber Toniasso; Fernando Dal Pont Morisso; Paulo Cezar Bastianello Campagnol; Renius de Oliveira Mello; Rosa Cristina Prestes Dornelles; Ernesto Hashime Kubota (Journal of Aquatic Food Product Technology, 2021)

Toxicity Assays of Commercial Chlorpyrifos Under UV/H2O2 and UVC Photolysis Treatments - Suelen Angeli; Eliane Adams; Gabriella P. Masceno; Rúbia M. Lima; Larisa M. Utzig; Fernando Rodrigues-Silva; Liziê D. T. Prola; Adriane M. Freitas; Marcus V. Liz (Water, Air, & Soil Pollution, 2021)

The genome of a thorny species: comparative genomic analysis among South and North American Cactaceae - Danilo Trabuco Amaral; Juliana Rodrigues Bombonato; Sónia Cristina da Silva Andrade; Evandro Marsola Moraes; Fernando Faria Franco (Planta, 2021)

Swine polioencephalomyelitis in Brazil: identification of Teschovirus A, Sapelovirus A, and Enterovirus G in a farm from Southern Brazil - Márcia Elisa Hammerschmitt; Paula Rodrigues de Almeida; Bianca Santana de Cecco; Marina Paula Lorenzett; Claiton Ismael Schwertz; Raquel Aparecida Sales da Cruz; Rafaela Albuquerque Caprioli; Daniela Teresa Schuh; Meriane Demoliner; Ana Karolina Antunes Eisen; Fernando Rosado Spilki; Saulo Petinatti Pavarini; et al. (Brazilian Journal of Microbiology, 2021)

The auxin-producing Bacillus thuringiensis RZ2MS9 promotes the growth and modifies the root architecture of tomato (Solanum lycopersicum cv. Micro-Tom) - Bruna Durante Batista; Manuella Nóbrega Dourado; Everthon Fernandes Figueredo; Renata Ockner Hortencio; João Paulo Rodrigues Marques; Fernando Angelo Piotto; Maria Letícia Bonatelli; Matthew L. Settles; João Lucio Azevedo; Maria Carolina Quecine (Archives of Microbiology, 2021)

Mercury Accumulation and Elimination in Different Tissues of Zebrafish (Danio rerio) Exposed to a Mercury-Supplemented Diet - Hugo C. Vieira; Andreia C. M. Rodrigues; Amadeu M. V. M. Soares; Sizenando Abreu; Fernando Morgado (Journal of Marine Science and Engineering, 2021)
In this study, we evaluated the bioaccumulation of mercury in zebrafish (Danio rerio) exposed to mercury-contaminated food for 21 days and the depuration of mercury for a subsequent post-exposure period of 28 days. Four tissues (muscle, liver, gills, and skin) were analyzed for mercury content. Overall, data indicated that Hg accumulation in the liver is faster than in other tissues. Furthermore, the liver is the tissue with the highest accumulation rate per day (0.021 µg Hg g−1 day−1), followed by muscle, skin, and gills. Conversely, the Hg depuration rates in different tissues showed the following order: gills > skin > muscle > liver. The bioaccumulation factor values of liver and muscle increased linearly during the uptake period. The ratios between mercury concentration in liver and muscle during the experiment also increased during the uptake period and remained higher than 1 during the elimination period, suggesting that Danio rerio needed more than 4 weeks of depuration. Finally, the distribution of Hg in the water column during the accumulation period is Hg particulate > Hg dissolved, and during the depuration period it is the opposite, mercury particulate

A coordinated approach for the assessment of molecular subgroups in pediatric ependymomas using low-cost methods - Graziella Ribeiro de Sousa; Régia Caroline Peixoto Lira; Taciani de Almeida Magalhães; Keteryne Rodrigues da Silva; Luis Fernando Peinado Nagano; Fabiano Pinto Saggioro; Mirella Baroni; Suely Kazue Nagahashi Marie; Sueli Mieko Oba-Shinjo; Silvia Brandelise; Rosane Gomes de Paula Queiroz; María Sol Brassesco; et al. (Journal of Molecular Medicine, 2021)

Climate change impact on the initial development of tropical forest species: a multi-model assessment - Fernando Yuri da Silva Reis; Fabrina Bolzan Martins; Roger Rodrigues Torres; Gabriel Wilson Lorena Florêncio; Jefferson Martiniano Cassemiro; Vanessa da Fontoura Custódio Monteiro; Mábele de Cássia Ferreira (Theoretical and Applied Climatology, 2021)

Plastic pollution: A focus on freshwater biodiversity - Valter M. Azevedo-Santos; Marcelo F. G. Brito; Pedro S. Manoel; Júlia F. Perroca; Jorge Luiz Rodrigues-Filho; Lucas R. P. Paschoal; Geslaine R. L. Gonçalves; Milena R. Wolf; Martín C. M. Blettler; Marcelo C. Andrade; André B. Nobile; Felipe P. Lima; et al. (Ambio, 2021)

Cultivation Practices of Sugarcane: An Analysis of the Competitiveness of Sugarcane Suppliers in Brazil - Fernando Rodrigues de Amorim; Timóteo Ramos Queiroz; Sandra Cristina de Oliveira; Wagner Luiz Lourenzani (Sugar Tech, 2021)

Effect of a purine derivative containing selenium to improve memory decline and anxiety through modulation of the cholinergic system and Na+/K+-ATPase in an Alzheimer’s disease model - Mikaela Peglow Pinz; Ane Gabriela Vogt; Karline da Costa Rodrigues; Angélica Schiavom dos Reis; Luis Fernando Barbosa Duarte; Mariana Gallio Fronza; William Borges Domingues; Eduardo Bierhaus Blodorn; Diego Alves; Vinicius Farias Campos; Lucielli Savegnago; Ethel Antunes Wilhelm; et al. (Metabolic Brain Disease, 2021)

High-intensity exercise training induces mitonuclear imbalance and activates the mitochondrial unfolded protein response in the skeletal muscle of aged mice - André Victor Cordeiro; Guilherme Francisco Peruca; Renata Rosseto Braga; Rafael Santos Brícola; Luciene Lenhare; Vagner Ramon Rodrigues Silva; Chadi Pellegrini Anaruma; Carlos Kiyoshi Katashima; Barbara Moreira Crisol; Lucas Torres Barbosa; Fernando Moreira Simabuco; Adelino Sanchez Ramos da Silva; et al. (GeroScience, 2021)

From molecule to conservation: DNA-based methods to overcome frontiers in the shark and ray fin trade - Rodrigo Rodrigues Domingues; Ingrid Vasconcellos Bunholi; Danillo Pinhal; Agostinho Antunes; Fernando Fernandes Mendonça (Conservation Genetics Resources, 2021)

Environmental correlates of taxonomic and phylogenetic diversity in the Atlantic Forest - Andrea Paz; Jason L. Brown; Carlos L. O. Cordeiro; Julian Aguirre‐Santoro; Claydson Assis; Renata Cecilia Amaro; Fabio Raposo do Amaral; Thuane Bochorny; Lucas F. Bacci; Mayara K. Caddah; Fernando d’Horta; Miriam Kaehler; et al. (Journal of Biogeography, 2021)
Aim There is little consensus on which environmental variables are best at predicting multiple dimensions of diversity. We ask whether there are common environmental correlates of diversity, despite ecological differences, across nine clades of plants and animals distributed along a single rainforest domain. For that, we compare the environmental correlates of species richness, phylogenetic diversity, and phylogenetic endemism. Location Brazilian Atlantic Forest. Taxon: Five clades of plants (Bromelioideae, Miconieae, Bertolonia , Cambessedesieae, and the Fridericia and allies) and four clades of animals (butterlies in the tribe Ithomiini, frogs in the genera Boana and Proceratophrys , and birds in the subfamily Thraupinae). Methods Using curated occurrence localities and phylogenetic data, we generated maps of (a) species richness, (b) phylogenetic diversity, (c) residuals of phylogenetic diversity regressed on species richness, and (d) phylogenetic endemism for all groups. We also compiled a set of 30 environmental descriptors, including records of current temperature and precipitation, climatic stability over time, and topography. Through a machine learning framework, we explored the environmental correlates of each of these diversity measures for each group. Results The environmental variables used here were strong predictors of diversity for all studied groups. However, models for phylogenetic endemism had lower predictive power. Although patterns of diversity are different among groups, correlates of diversity are consistent across taxa. For both species richness and phylogenetic diversity, current precipitation and precipitation stability over time were consistently ranked among the variables that strongly correlate with diversity patterns. The correlates of phylogenetic endemism were less homogeneous across groups. The results suggest that including climate stability over time is important when predicting diversity measures that reflect historical components. Main conclusions Investigating environmental correlates of diversity for multiple clades and diversity measures in a single geographic area allows for a better understanding of common patterns across taxa. This study shows that environmental conditions, particularly precipitation, are good predictors of the patterns of species richness and phylogenetic diversity‐but not phylogenetic endemism‐across different Atlantic Forest groups.

Cactus cladodes cause intestinal damage, but improve sheep performance - Tomás Guilherme Pereira da Silva; Ângela Maria Vieira Batista; Adriana Guim; Francisco de Assis Leite Souza; Francisco Fernando Ramos de Carvalho; Valdemiro Amaro da Silva Júnior; Janaina Kelli Gomes Arandas; Maria Edna Gomes de Barros; Daurivane Rodrigues Sousa; Suellen Maria Costa da Silva (Tropical Animal Health and Production, 2021)

A multivariate approach to the physical and physiological quality of hybrid corn seeds affected by Molicutes and MRFV - Jhonata Cantuária Medeiros; Juliana de Fátima Sales; Jacson Zuchi; Kelly Juliane Teles Nascimento; Fernando Higino de Lima e Silva; Stella Tomaz de Castro; Adriano Carvalho Costa; Arthur Almeida Rodrigues (Euphytica, 2021)

Treatment of a clinical analysis laboratory wastewater from a hospital by photo-Fenton process at four radiation settings and toxicity response - Roberson Davis Sá; Adriana Patricia Rodríguez-Pérez; Fernando Rodrigues-Silva; Vinicius de Carvalho Soares de Paula; Liziê Daniela Tentler Prola; Adriane Martins de Freitas; Karina Querne de Carvalho; Marcus Vinicius de Liz (Environmental Science and Pollution Research, 2021)

Nitrogen use efficiency and recovery in a wheat-corn rotation under tropical savannah conditions - Fernando Shintate Galindo; Edson Cabral da Silva; Paulo Humberto Pagliari; Guilherme Carlos Fernandes; Willian Lima Rodrigues; Antônio Leonardo Campos Biagini; Eduardo Bianchi Baratella; Castro Alves da Silva Júnior; Mário João Moretti Neto; Takashi Muraoka; Marcelo Carvalho Minhoto Teixeira Filho (Nutrient Cycling in Agroecosystems, 2021)

(3,3’-Methylene)bis-2-hydroxy-1,4-naphthoquinones induce cytotoxicity against DU145 and PC3 cancer cells by inhibiting cell viability and promoting cell cycle arrest - Paula Priscilla de Freitas; Ruan Carlos Busquet Ribeiro; Isabella dos Santos Guimarães; Caroline S. Moreira; David R. Rocha; Fernando de Carvalho da Silva; Vitor Francisco Ferreira; Etel Rodrigues Pereira Gimba (Molecular Biology Reports, 2021)

Detection of fusariosis on black pepper plants using multispectral sensor - Daniel Dourado Lacastagneratte; Fernando da Silva Rocha; Maria de Fátima Gonçalves Fernandes; Maria de Fátima Silva Muniz; Hugo César Rodrigues Moreira Catão; Carlos Juliano Brant Albuquerque (Journal of Plant Diseases and Protection, 2021)

The commonality of core biological groups across freshwater food webs - Fernando Miranda Lansac‐Tôha; Bárbara Angélio Quirino; Yasmin Rodrigues Souza; Fábio Amodêo Lansac‐Tôha; Luiz Felipe Machado Velho; Matheus Tenório Baumgartner (Limnology and Oceanography, 2021)
Assessing how organisms interact is fundamental to understand biodiversity patterns. Like many ecosystems, most freshwater environments are susceptible to spatial and temporal variations, especially floodplains. In spite of the expected variability, the structure of interactions in food webs is a paramount aspect to uncover processes related to ecosystem functioning. Here, we surveyed four large floodplains to identify the biological groups that are protagonists across different freshwater food webs. We used limnological data on physical and biochemical variables, combined with biological information on 10 communities grouped into 41 trait‐based categories. Despite the expected differences among floodplains and between hydrologic periods (dry and flood), we identified that complex freshwater food webs shared core network compartments. Using the eigenvector centrality as a measure of importance to the whole food web, we found that both primary producers (i.e., phytoplankton) and potential top predators (i.e., fish) were the core groups in freshwater trophic networks. These biological groups were consistently among the most linked compartments in all reconstructed food webs. Considering variations among food webs, we found that most differences were dictated by how compartments interact, rather than by their co‐occurrences. Perhaps equally important is that omnivory was important for the reconstructed food webs, drawing attention to this interaction type as a fundamental aspect to unveil ecosystem processes. Although more empirical research is required to fully understand the importance of biotic interactions in freshwater food webs, our findings underline that ecosystems are more likely to collapse when disturbances affect the boundaries of the energy paths.

Scale‐dependent patterns of metacommunity structuring in aquatic organisms across floodplain systems - Fernando M. Lansac‐Tôha; Luis M. Bini; Jani Heino; Bianca R. Meira; Bianca T. Segovia; Carla S. Pavanelli; Claudia C. Bonecker; Claudia P. de Deus; Evanilde Benedito; Geziele M. Alves; Gislaine I. Manetta; Juliana D. Dias; et al. (Journal of Biogeography, 2021)
Aim Evaluating how groups of organisms vary in dispersal capability and how environmental, spatial and temporal signals vary across multiple scales is critical to elucidating metacommunity theory. We examined whether the relative contributions of environmental, spatial and hydrological factors have different effects on organismal groups with different dispersal abilities at three spatial scales, and how this knowledge contributes to our understanding of metacommunity dynamics. Location Four major Brazilian floodplains, with the largest distance among them of 2,300 Km. Taxon 10 aquatic organismal groups, ranging from bacterioplankton to fish. Methods We sampled lakes connected to the main river in the low‐ and high‐water periods of each floodplain between 2011 and 2012. Different biological groups were analysed across three hierarchical spatial scales (fine, intermediate and subcontinental) within and between floodplain systems. We applied a series of partial redundancy analyses to estimate the relative contributions of environmental factors, spatial factors and hydrological period for each biological group. Results At the fine spatial scale, predominantly environmental factors and hydrological period structure metacommunities, although less so for microorganisms than for micro‐invertebrates and macro‐organisms. The relative importance of environmental factors increased at the intermediate spatial scale. At the subcontinental scale, the relative importance of spatial factors increased for all biological groups, but environmental factors remained the primary regulators of microorganisms even at the largest scale. Main conclusions This study design allowed us to make more robust inferences about the mechanisms responsible for regulating community structure of distinct biological groups at different spatial scales. Our results suggest that biological groups displaying distinct body size likely determine the spatial extent at which environmental, spatial and hydrological processes prevail as the primary regulators of community structure. These findings are important in guiding the conservation and management of floodplain biodiversity because these systems are naturally highly heterogeneous in space and time.

Performance of broiler chicken submitted to a quantitative feed restriction program - Tiago Bordin; Fernando Pilotto; Daniela Pesenatto; Bruno Sebastião de Mendonça; Luciane Daroit; Laura Beatriz Rodrigues; Ezequiel Davi dos Santos; Elci Lotar Dickel (Tropical Animal Health and Production, 2021)

Correlations between water quality and precipitation in areas with different levels of human occupation - Lucas Augusto Pereira Rodrigues; Fernando Aparecido Dias Radomski; Rodrigo Felipe Bedim Godoy; Elias Trevisan; Enzo Luigi Crisigiovanni (International Journal of Energy and Water Resources, 2021)

Pelletizing of lignocellulosic wastes as an environmentally friendly solution for the energy supply: insights on the properties of pellets from Brazilian biomasses - Diego Abner Rodrigues Santana; Mário Vanoli Scatolino; Michael Douglas Roque Lima; Udson de Oliveira Barros Junior; Dorival Pinheiro Garcia; Carlos Rogério Andrade; Angélica de Cássia Oliveira Carneiro; Paulo Fernando Trugilho; Thiago de Paula Protásio (Environmental Science and Pollution Research, 2021)

Bacteriological, cytological, and molecular investigation of Corynebacterium pseudotuberculosis, mycobacteria, and other bacteria in caseous lymphadenitis and healthy lymph nodes of slaughtered sheep - Thiago de Oliveira Zamprogna; Dayana Ribeiro; Vasco A.C. Azevedo; Gustavo Henrique Batista Lara; Rodrigo Garcia Motta; Rodrigo Costa da Silva; Amanda Keller Siqueira; Geraldo de Nardi Júnior; Fernando José Paganini Listoni; Lorrayne de Souza Araújo Martins; Aristeu Vieira da Silva; Fábio Vinícius Ramos Portilho; et al. (Brazilian Journal of Microbiology, 2021)

Capsaicin lacks tumor-promoting effects during colon carcinogenesis in a rat model induced by 1,2-dimethylhydrazine - Brunno Felipe Ramos Caetano; Mariana Baptista Tablas; Marcela Gonçalves Ignoti; Nelci Antunes de Moura; Guilherme Ribeiro Romualdo; Luís Fernando Barbisan; Maria Aparecida Marchesan Rodrigues (Environmental Science and Pollution Research, 2021)

Soil loss and sediment yield in a perennial catchment in southwest Piauí, Brazil - Kamylla Gonçalves Oliveira Assis; Yuri Jacques Agra Bezerra da Silva; José Wellington Batista Lopes; João Carlos Medeiros; Marcos Paulo Rodrigues Teixeira; Fernando Braga Rimá; Vijay P. Singh (Environmental Monitoring and Assessment, 2021)

Genes and SNPs in the pathway of immune response and caries risk: a systematic review and meta-analysis - Luiz Alexandre Chisini; Mariana Gonzalez Cademartori; Marucs Cristian Muniz Conde; Francine Dos Santos Costa; Luciana Tovo-Rodrigues; Rodrigo Varella de Carvalho; Flávio Fernando Demarco; Marcos Britto Correa (Biofouling, 2020)

Topical application of (S)-(–)-limonene is as effective as phonophoresis for improving oxidative parameters of injured skeletal muscle in rats - Marta Maria Barbosa Santos; Luís Fernando Sousa Filho; Jéssica Batista De Souza; José Evaldo Rodrigues De Menezes Filho; Thássio Ricardo Ribeiro Mesquita; Michel Santana Santos; Carla Maria Lins De Vasconcelos; Sandra Lauton-Santos; Evaleide Diniz De Oliveira (Naunyn-Schmiedeberg's Archives of Pharmacology, 2020)

Investigation of Azospirillum brasilense Inoculation and Silicon Application on Corn Yield Responses - Fernando Shintate Galindo; Paulo Humberto Pagliari; Willian Lima Rodrigues; Maikon Richer de Azambuja Pereira; Salatiér Buzetti; Marcelo Carvalho Minhoto Teixeira Filho (Journal of Soil Science and Plant Nutrition, 2020)

Mitoxantrone impairs proteasome activity and prompts early energetic and proteomic changes in HL-1 cardiomyocytes at clinically relevant concentrations - Vera Marisa Costa; João Paulo Capela; Joana R. Sousa; Rute P. Eleutério; Patrícia R. S. Rodrigues; José Luís Dores-Sousa; Rui A. Carvalho; Maria Lourdes Bastos; José Alberto Duarte; Fernando Remião; M. Gabriela Almeida; Kurt J. Varner; et al. (Archives of Toxicology, 2020)

Molecular Inferences on Scomberomorus brasiliensis, From the Western South Atlantic, Based on Two Mitochondrial Genes - Divino B. da Cunha; Luis Fernando S. Rodrigues-Filho; João Braúllio de Luna Sales; Pericles Rêgo; Cleonilde Queiroz; Iracilda Sampaio; Marcelo Vallinoto (Frontiers in Marine Science, 2020)

Adsorption of amoxicillin onto high surface area–activated carbons based on olive biomass: kinetic and equilibrium studies - Daniel Lucas Costa Rodrigues; Fernando Machado Machado; Alice Gonçalves Osório; Cristiane Ferraz de Azevedo; Eder Claudio Lima; Raphaelle S. da Silva; Diana Ramos Lima; Fernanda Medeiros Gonçalves (Environmental Science and Pollution Research, 2020)

NEOTROPICAL CARNIVORES: a data set on carnivore distribution in the Neotropics - Mariana Nagy‐Reis; Júlia Emi de Faria Oshima; Claudia Zukeran Kanda; Francesca Belem Lopes Palmeira; Fabiano Rodrigues de Melo; Ronaldo Gonçalves Morato; Lilian Bonjorne; Marcelo Magioli; Caroline Leuchtenberger; Fabio Rohe; Frederico Gemesio Lemos; Felipe Martello; et al. (Ecology, 2020)
Mammalian carnivores are considered a key group in maintaining ecological health and can indicate potential ecological integrity in landscapes where they occur. Carnivores also hold high conservation value and their habitat requirements can guide management and conservation plans. The order Carnivora has 84 species from 8 families in the Neotropical region: Canidae; Felidae; Mephitidae; Mustelidae; Otariidae; Phocidae; Procyonidae; and Ursidae. Herein, we include published and unpublished data on native terrestrial Neotropical carnivores (Canidae; Felidae; Mephitidae; Mustelidae; Procyonidae; and Ursidae). NEOTROPICAL CARNIVORES is a publicly available data set that includes 99,605 data entries from 35,511 unique georeferenced coordinates. Detection/non‐detection and quantitative data were obtained from 1818 to 2018 by researchers, governmental agencies, non‐governmental organizations, and private consultants. Data were collected using several methods including camera trapping, museum collections, roadkill, line transect, and opportunistic records. Literature (peer‐reviewed and grey literature) from Portuguese, Spanish and English were incorporated in this compilation. Most of the data set consists of detection data entries (n = 79,343; 79.7%) but also includes non‐detection data (n = 20,262; 20.3%). Of those, 43.3% also include count data (n = 43,151). The information available in NEOTROPICAL CARNIVORES will contribute to macroecological, ecological, and conservation questions in multiple spatio‐temporal perspectives. As carnivores play key roles in trophic interactions, a better understanding of their distribution and habitat requirements are essential to establish conservation management plans and safeguard the future ecological health of Neotropical ecosystems. Our data paper, combined with other large‐scale data sets, has great potential to clarify species distribution and related ecological processes within the Neotropics. There are no copyright restrictions and no restriction for using data from this data paper, as long as the data paper is cited as the source of the information used. We also request that users inform us of how they intend to use the data.

NEOTROPICAL ALIEN MAMMALS: a data set of occurrence and abundance of alien mammals in the Neotropics - Clarissa Alves da Rosa; Bruno R. Ribeiro; Vanesa Bejarano; Fernando Henrique Puertas; Adriana Bocchiglieri; Adriana Loeser dos Santos Barbosa; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adriele Aparecida Pereira; Adryelle Francisca de Souza Moreira; Agnis Cristiane de Souza; Aiesca Pellegrin; et al. (Ecology, 2020)
Biological invasion is one of the main threats to native biodiversity. For a species to become invasive, it must be voluntarily or involuntarily introduced by humans into a nonnative habitat. Mammals were among first taxa to be introduced worldwide for game, meat, and labor, yet the number of species introduced in the Neotropics remains unknown. In this data set, we make available occurrence and abundance data on mammal species that (1) transposed a geographical barrier and (2) were voluntarily or involuntarily introduced by humans into the Neotropics. Our data set is composed of 73,738 historical and current georeferenced records on alien mammal species of which around 96% correspond to occurrence data on 77 species belonging to eight orders and 26 families. Data cover 26 continental countries in the Neotropics, ranging from Mexico and its frontier regions (southern Florida and coastal‐central Florida in the southeast United States) to Argentina, Paraguay, Chile, and Uruguay, and the 13 countries of Caribbean islands. Our data set also includes neotropical species (e.g., Callithrix sp., Myocastor coypus , Nasua nasua) considered alien in particular areas of Neotropics. The most numerous species in terms of records are from Bos sp. ( n = 37,782), Sus scrofa ( n = 6,730), and Canis familiaris ( n = 10,084); 17 species were represented by only one record (e.g., S yncerus caffer, Cervus timorensis, Cervus unicolor, Canis latrans ). Primates have the highest number of species in the data set ( n = 20 species), partly because of uncertainties regarding taxonomic identification of the genera Callithrix, which includes the species Callithrix aurita, Callithrix flaviceps, Callithrix geoffroyi, Callithrix jacchus, Callithrix kuhlii, Callithrix penicillata , and their hybrids. This unique data set will be a valuable source of information on invasion risk assessments, biodiversity redistribution and conservation‐related research. There are no copyright restrictions. Please cite this data paper when using the data in publications. We also request that researchers and teachers inform us on how they are using the data.

Loss of phytoplankton functional and taxonomic diversity induced by river regulation in a large tropical river - Idelina Gomes da Silva; Fernando Mayer Pelicice; Luzia Cleide Rodrigues (Hydrobiologia, 2020)

Melaleuca leucadendra Essential Oil Promotes Loss of Cell Membrane and Wall Integrity and Inhibits Bacterial Growth: An In Silico and In Vitro Approach - Jessica P. Bautista-Silva; Janaína B. Seibert; Tatiane R. Amparo; Ivanildes V. Rodrigues; Luiz Fernando M. Teixeira; Gustavo Henrique B. Souza; Orlando D. H. dos Santos (Current Microbiology, 2020)

Productivity and Profitability of the Sugarcane Production in the State of Sao Paulo, Brazil - Fernando Rodrigues de Amorim; Marco Tulio Ospina Patino; Petra Maria Bartmeyer; David Ferreira Lopes Santos (Sugar Tech, 2020)

Modulation of ERG Genes Expression in Clinical Isolates of Candida tropicalis Susceptible and Resistant to Fluconazole and Itraconazole - Maria Cláudia Silva; Débora Cardozo Bonfim Carbone; Pedro Fernando Diniz; Fabrício Freitas Fernandes; Carlos Alessandro Fuzo; Carolina Santos Pereira Cardoso Trindade; Marilene Rodrigues Chang; João Santana Silva (Mycopathologia, 2020)

Mating system of Thrichomys fosteri in the Brazilian Pantanal: spatial patterns indicate promiscuity - Pâmela Antunes; Luiz Gustavo Rodrigues Oliveira-Santos; Thiago Mateus Rocha dos Santos; Jorge Fernando Saraiva de Menezes; Walfrido Moraes Tomas; James D. Forester; Fernando Antonio Santos Fernandez (Mammalian Biology, 2020)

Role of the antioxidant properties in the gastroprotective and gastric healing activity promoted by Brazilian green propolis and the healing efficacy of Artepillin C - Philipe Costa; Lincon Bordignon Somensi; Rita de Cássia Melo Vilhena de Andr da Silva; Luísa Nathalia Bolda Mariano; Thaise Boeing; Bruna Longo; Ellen Perfoll; Priscila de Souza; Lucas Fernando Sérgio Gushiken; Cláudia Helena Pellizzon; Débora Munhoz Rodrigues; Jairo Kenupp Bastos; et al. (Inflammopharmacology, 2020)

Changes in salivary protein composition of lambs supplemented with aerial parts and condensed tannins: extract from Cistus ladanifer L.—a preliminary study - Elsa Lamy; Lénia Rodrigues; Olinda Guerreiro; David Soldado; Alexandra Francisco; Monica Lima; Fernando Capela e Silva; Orlando Lopes; José Santos-Silva; Eliana Jerónimo (Agroforestry Systems, 2020)

Factors affecting occurrence of demodecosis by Demodex bovis in Sindhi cattle (Bos indicus) - José Nerivaldo de Araújo Wanderley; Ana Célia Rodrigues Athayde; José Fabio Paulino de Moura; Leilson Rocha Bezerra; Antônio Fernando de Melo Vaz; Ednaldo Queiroga de Lima; Juliana Paula Felipe de Oliveira; Wilson Wouflan Silva (Tropical Animal Health and Production, 2020)

Time-series expression profiling of sugarcane leaves infected with Puccinia kuehnii reveals an ineffective defense system leading to susceptibility - Fernando Henrique Correr; Guilherme Kenichi Hosaka; Sergio Gregorio Pérez Gómez; Mariana Cicarelli Cia; Claudia Barros Monteiro Vitorello; Luis Eduardo Aranha Camargo; Nelson Sidnei Massola; Monalisa Sampaio Carneiro; Gabriel Rodrigues Alves Margarido (Plant Cell Reports, 2020)

Correction to: CpG‑creating mutations are costly in many human viruses - Victoria R. Caudill; Sarina Qin; Ryan Winstead; Jasmeen Kaur; Kaho Tisthammer; E. Geo Pineda; Caroline Solis; Sarah Cobey; Trevor Bedford; Oana Carja; Rosalind M. Eggo; Katia Koelle; et al. (Evolutionary Ecology, 2020)

CpG-creating mutations are costly in many human viruses - Victoria R. Caudill; Sarina Qin; Ryan Winstead; Jasmeen Kaur; Kaho Tisthammer; E. Geo Pineda; Caroline Solis; Sarah Cobey; Trevor Bedford; Oana Carja; Rosalind M. Eggo; Katia Koelle; et al. (Evolutionary Ecology, 2020)
Mutations can occur throughout the virus genome and may be beneficial, neutral or deleterious. We are interested in mutations that yield a C next to a G, producing CpG sites. CpG sites are rare in eukaryotic and viral genomes. For the eukaryotes, it is thought that CpG sites are rare because they are prone to mutation when methylated. In viruses, we know less about why CpG sites are rare. A previous study in HIV suggested that CpG-creating transition mutations are more costly than similar non-CpG-creating mutations. To determine if this is the case in other viruses, we analyzed the allele frequencies of CpG-creating and non-CpG-creating mutations across various strains, subtypes, and genes of viruses using existing data obtained from Genbank, HIV Databases, and Virus Pathogen Resource. Our results suggest that CpG sites are indeed costly for most viruses. By understanding the cost of CpG sites, we can obtain further insights into the evolution and adaptation of viruses.

Development of a novel anti-biofilm peptide derived from profilin of Spodoptera frugiperda - Amanda Carolina Borges da Silva; Janaina de Cassia Orlandi Sardi; Daniella Gorete Lourenço de Oliveira; Caio Fernando Ramalho de Oliveira; Helder Freitas dos Santos; Edson Lucas dos Santos; Edson Crusca; Marlon Henrique Cardoso; Octávio Luiz Franco; Maria Lígia Rodrigues Macedo (Biofouling, 2020)

Histomorphometric changes of the fore-stomach of lambs fed with diets containing spineless cactus genotypes resistant to Dactylopius sp. - Tomás Guilherme Pereira da Silva; Ângela Maria Vieira Batista; Adriana Guim; Valdemiro Amaro da Silva; Francisco Fernando Ramos de Carvalho; Maria Edna Gomes de Barros; Daurivane Rodrigues de Sousa; Suellen Maria Costa da Silva (Tropical Animal Health and Production, 2020)

Total-evidence phylogeny and divergence times of Vermilingua (Mammalia: Pilosa) - Daniel de melo Casali; José EustáQuio Dos Santos Júnior; Flávia Regina Miranda; Fabrício Rodrigues Santos; Fernando Araújo Perini (Systematics and Biodiversity, 2020)

Industrial Quality of Sugarcane Under Fertigation with Nitrogen and Zinc - Fernando Nobre Cunha; Marconi Batista Teixeira; Frederico Antonio Loureiro Soares; Edson Cabral da Silva; Antonio Evami Cavalcante Sousa; Leonardo Nazário Silva dos Santos; Nelmício Furtado da Silva; Wilker Alves Morais; Vitor Marques Vidal; Fernando Rodrigues Cabral Filho; Gustavo da Silva Vieira (Sugar Tech, 2020)

Nitrogen sources and application rates affect emissions of N2O and NH3 in sugarcane - Iracema Alves Manoel Degaspari; Johnny Rodrigues Soares; Zaqueu Fernando Montezano; Stephen J. Del Grosso; André Cesar Vitti; Raffaella Rossetto; Heitor Cantarella (Nutrient Cycling in Agroecosystems, 2020)

Macromolecule extracted from Gracilaria caudata reduces inflammation and restores hepatic function in nimesulide-induced hepatic damage - Genilson José Dias Júnior; Sarah Izabelly Alves Lemos; Tarcisio Vieira de Brito; Cynthia Maria Carvalho Pereira; José Simião da Cruz Júnior; Jayro dos Santos Ferreira; Lauanda da Rocha Rodrigues; José Victor do Nascimento Lima; Carlos Eduardo da Silva Monteiro; Alvaro Xavier Franco; Pedro Marcos Gomes Soares; Even Herlany Pereira Alves; et al. (Journal of Applied Phycology, 2020)

Gold-Coated Superparamagnetic Iron Oxide Nanoparticles Attenuate Collagen-Induced Arthritis after Magnetic Targeting - Maria Fernanda Hornos Carneiro; Ana Rita T. Machado; Lusânia M. G. Antunes; Talita E. Souza; Victor A. Freitas; Luiz C. A. Oliveira; Jairo L. Rodrigues; Marcio C. Pereira; Fernando Barbosa (Biological Trace Element Research, 2020)

Tree diversity and above-ground biomass in the South America Cerrado biome and their conservation implications - Paulo S. Morandi; Beatriz Schwantes Marimon; Ben Hur Marimon-Junior; James A. Ratter; Ted R. Feldpausch; Guarino Rinaldi Colli; Cássia Beatriz Rodrigues Munhoz; Manoel Cláudio da Silva Júnior; Edson de Souza Lima; Ricardo Flores Haidar; Luzmila Arroyo; Alejandro Araujo Murakami; et al. (Biodiversity and Conservation, 2020)

Influence of the Holocene relative sea level on the coastal plain of Sepetiba Bay (Southeast Brazil) - Maria Virgínia Alves Martins; Anita Fernandes Souza Pinto; Leonardo Borghi; Thiago Gonçalves Carelli; Maider Morlote; Daniel Rey; Egberto Pereira; José Carlos Martins Ramalho; Fernando Rocha; Mauro Geraldes; Guilherme Loriato Potratz; Wania Duleba; et al. (Journal of Sedimentary Environments, 2020)

Ricinus communis as a phytoremediator of soil mineral oil: morphoanatomical and physiological traits - Larissa Saeki Rehn; Arthur Almeida Rodrigues; Sebastião Carvalho Vasconcelos-Filho; Douglas Almeida Rodrigues; Luciana Minervina de Freitas Moura; Alan Carlos Costa; Leandro Carlos; Juliana de Fátima Sales; Jacson Zuchi; Lucas Peres Angelini; Fernando Higino de Lima Silva; Caroline Müller (Ecotoxicology, 2020)

Physiological effects of overexpressed sigma factors on fermentative stress response of Zymomonas mobilis - Tiago Benoliel; Marciano Régis Rubini; Carolina de Souza Baptistello; Christiane Ribeiro Janner; Vanessa Rodrigues Vieira; Fernando Araripe Torres; Adrian Walmsley; Lidia Maria Pepe de Moraes (Brazilian Journal of Microbiology, 2020)

Anti-Sarcocystis Antibodies in Lambs Deprived of Colostrum - Camila Encarnação Minuzzi; Fernando de Souza Rodrigues; Camila Balconi Marques; Tiago Gallina; Thiago Cardoso dos Santos; Luiza Pires Portella; Patricia Bräunig; Alisson Rodrigues Döhler; Luis Antonio Sangioni; Fernanda Silveira Flores Vogel (Acta Parasitologica, 2020)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Exercise Modalities Improve Aversive Memory and Survival Rate in Aged Rats: Role of Hippocampal Epigenetic Modifications - Louisiana Carolina Ferreira de Meireles; Fernando Galvão; Deena M. Walker; Laura Reck Cechinel; Ágnis Iohana de Souza Grefenhagen; Gisele Andrade; Roberta Passos Palazzo; Gisele Agustini Lovatel; Carla Giovanna Basso; Eric J. Nestler; Ionara Rodrigues Siqueira (Molecular Neurobiology, 2019)

Expression of MicroRNAs miR-145, miR-181c, miR-199a and miR-1183 in the Blood and Hippocampus of Patients with Mesial Temporal Lobe Epilepsy - Luana Grupioni Lourenço Antônio; Priscila Freitas-Lima; Gabriela Pereira-da-Silva; João Alberto Assirati; Caio Marconato Matias; Mucio Luiz Assis Cirino; Luis Fernando Tirapelli; Tonicarlo Rodrigues Velasco; Americo Ceiki Sakamoto; Carlos Gilberto Carlotti; Daniela Pretti da Cunha Tirapelli (Journal of Molecular Neuroscience, 2019)

DNA-based species identification of shark finning seizures in Southwest Atlantic: implications for wildlife trade surveillance and law enforcement - Bruno Lopes da Silva Ferrette; Rodrigo Rodrigues Domingues; Luis Henrique Fregadolli Ussami; Letícia Moraes; Carolina de Oliveira Magalhães; Alberto Ferreira de Amorim; Alexandre Wagner Silva Hilsdorf; Claudio Oliveira; Fausto Foresti; Fernando Fernandes Mendonça (Biodiversity and Conservation, 2019)

How deep can ectomycorrhizas go? A case study on Pisolithus down to 4 meters in a Brazilian eucalypt plantation - Agnès Robin; Céline Pradier; Hervé Sanguin; Frédéric Mahé; George Rodrigues Lambais; Arthur Prudêncio de Araujo Pereira; Amandine Germon; Maiele Cintra Santana; Pierre Tisseyre; Anne-Laure Pablo; Pauline Heuillard; Marie Sauvadet; et al. (Mycorrhiza, 2019)

Development and characterization of 19 polymorphic microsatellite loci from the Red-cowled Cardinal (Paroaria dominicana, Passeriformes, Aves) using next-generation sequencing - Ana Laura Rosa; Cássia Alves Lima-Rezende; Fernando Pacheco Rodrigues; Renato Caparroz (Molecular Biology Reports, 2019)

Performance of SSEBop model for estimating wheat actual evapotranspiration in the Brazilian Savannah region - Juliana Dias Lopes; Lineu Neiva Rodrigues; Hewlley Maria Acioli Imbuzeiro; Fernando Falco Pruski (International Journal of Remote Sensing, 2019)

Fungal communities in different aged leaves of Eucalyptus microcorys F. Muell - Lorena Tigre Lacerda; Luís Fernando Pascholati Gusmão; Andre Rodrigues (Brazilian Journal of Botany, 2019)

Assessing Proximate Composition, Extractive Concentration, and Lignin Quality to Determine Appropriate Parameters for Selection of Superior Eucalyptus Firewood - Thiago de Paula Protásio; Mário Vanoli Scatolino; Ana Clara Caxito de Araújo; Ana Flávia Cunha Fernandes de Oliveira; Izabel Cristina Rodrigues de Figueiredo; Maíra Reis de Assis; Paulo Fernando Trugilho (BioEnergy Research, 2019)

Polymorphic microsatellite loci and partial mitogenome for the Chestnut-bellied Seed-finch Sporophila angolensis (Aves, Passeriformes) using next generation sequencing - Cássia Alves Lima-Rezende; Sarah Dobkowski-Marinho; Gislaine Aparecida Fernandes; Fernando Pacheco Rodrigues; Renato Caparroz (Molecular Biology Reports, 2019)

Degradation of haloacetic acids with the Fenton-like and analysis by GC-MS: use of bioassays for monitoring of genotoxic, mutagenic and cytotoxic effects - Amanda Oliveira Mourão; Diego Francis Silva; Mariandry Rodriguez; Thamyris Souza Torres; Elton Santos Franco; Valter Lúcio Pádua; Márcia Cristina da Silva Faria; Luiz Fernando Oliveira Maia; Jairo Lisboa Rodrigues (Environmental Monitoring and Assessment, 2019)

Physicochemical parameters, fatty acid profile, and sensory attributes of meat from lambs fed with cassava dregs in replacement of corn - Daniel Barros Cardoso; Robson Magno Liberal Véras; Francisco Fernando Ramos de Carvalho; André Luiz Rodrigues Magalhães; Gustavo Araújo de Vasconcelos; Maria Inês Sucupira Maciel; Marta Suely Madruga; Stela Antas Urbano; Janaina de Lima Silva (Tropical Animal Health and Production, 2019)

Involvement of the Cholinergic Parameters and Glial Cells in Learning Delay Induced by Glutaric Acid: Protection by N-Acetylcysteine - Fernanda Silva Rodrigues; Viviane Nogueira de Zorzi; Marla Parizzi Funghetto; Fernanda Haupental; Alexandra Seide Cardoso; Sara Marchesan; Andréia M. Cardoso; Maria Rosa C. Schinger; Alencar Kolinski Machado; Ivana Beatrice Mânica da Cruz; Marta Maria Medeiros Frescura Duarte; Léder L. Xavier; et al. (Molecular Neurobiology, 2019)

NEOTROPICAL XENARTHRANS: a data set of occurrence of xenarthran species in the Neotropics - Paloma Marques Santos; Adriana Bocchiglieri; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adryelle Moreira; Agnis Cristiane de Souza; Agustin Manuel Abba; Agustin Paviolo; Ailin Gatica; Akyllan Zoppi Medeiro; Alan Nilo Costa; Alberto Gonzalez Gallina; et al. (Ecology, 2019)
Xenarthrans—anteaters, sloths, and armadillos—have essential functions for ecosystem maintenance, such as insect control and nutrient cycling, playing key roles as ecosystem engineers. Because of habitat loss and fragmentation, hunting pressure, and conflicts with domestic dogs, these species have been threatened locally, regionally, or even across their full distribution ranges. The Neotropics harbor 21 species of armadillos, 10 anteaters, and 6 sloths. Our data set includes the families Chlamyphoridae (13), Dasypodidae (7), Myrmecophagidae (3), Bradypodidae (4), and Megalonychidae (2). We have no occurrence data on Dasypus pilosus (Dasypodidae). Regarding Cyclopedidae, until recently, only one species was recognized, but new genetic studies have revealed that the group is represented by seven species. In this data paper, we compiled a total of 42,528 records of 31 species, represented by occurrence and quantitative data, totaling 24,847 unique georeferenced records. The geographic range is from the southern United States, Mexico, and Caribbean countries at the northern portion of the Neotropics, to the austral distribution in Argentina, Paraguay, Chile, and Uruguay. Regarding anteaters, Myrmecophaga tridactyla has the most records ( n = 5,941), and Cyclopes sp. have the fewest ( n = 240). The armadillo species with the most data is Dasypus novemcinctus ( n = 11,588), and the fewest data are recorded for Calyptophractus retusus ( n = 33). With regard to sloth species, Bradypus variegatus has the most records ( n = 962), and Bradypus pygmaeus has the fewest ( n = 12). Our main objective with Neotropical Xenarthrans is to make occurrence and quantitative data available to facilitate more ecological research, particularly if we integrate the xenarthran data with other data sets of Neotropical Series that will become available very soon (i.e., Neotropical Carnivores, Neotropical Invasive Mammals, and Neotropical Hunters and Dogs). Therefore, studies on trophic cascades, hunting pressure, habitat loss, fragmentation effects, species invasion, and climate change effects will be possible with the Neotropical Xenarthrans data set. Please cite this data paper when using its data in publications. We also request that researchers and teachers inform us of how they are using these data.

Occurrence and antimicrobial resistance of E. coli non-O157 isolated from beef in Mato Grosso, Brazil - Vinicius Silva Castro; Larrayane Albuês Carvalho Teixeira; Dália dos Prazeres Rodrigues; Luis Fernando dos Santos; Carlos Adam Conte-Junior; Eduardo Eustáquio de Souza Figueiredo (Tropical Animal Health and Production, 2019)

Photochemistry and hydric responses of congeneric Croton species at restoration sites under dry season: implications for species selection - Angélica L. Rodrigues; Angelo A. S. Bertholdi; Luís Paulo B. Mantoan; Gabriela M. Vasconcellos; Luiz Fernando R. Almeida (Theoretical and Experimental Plant Physiology, 2019)

Antimicrobial Activity of Compounds Containing Silver Nanoparticles and Calcium Glycerophosphate in Combination with Tyrosol - José Antonio Santos Souza; Debora Barros Barbosa; Jackeline Gallo do Amaral; Douglas Roberto Monteiro; Luiz Fernando Gorup; Francisco Nunes de Souza Neto; Renan Aparecido Fernandes; Gabriela Lopes Fernandes; Emerson Rodrigues de Camargo; Alessandra Marçal Agostinho; Alberto Carlos Botazzo Delbem (Indian Journal of Microbiology, 2019)

Phylogeography of eagle rays of the genus Aetobatus: Aetobatus narinari is restricted to the continental western Atlantic Ocean - João Bráullio L. Sales; Cintia Negrão de Oliveira; Wagner César Rosa dos Santos; Matheus Marcos Rotundo; Yrlene Ferreira; Jonathan Ready; Iracilda Sampaio; Claudio Oliveira; Vanessa P. Cruz; Raul E. Lara-Mendoza; Luis Fernando da Silva Rodrigues-Filho (Hydrobiologia, 2019)

ATLANTIC BIRD TRAITS : a data set of bird morphological traits from the Atlantic forests of South America - Rodolpho Credo Rodrigues; Érica Hasui; Julia Camara Assis; João Carlos Castro Pena; Renata L. Muylaert; Vinicius Rodrigues Tonetti; Felipe Martello; André Luis Regolin; Thiago Vernaschi Vieira da Costa; Mauro Pichorim; Eduardo Carrano; Leonardo Esteves Lopes; et al. (Ecology, 2019)
Scientists have long been trying to understand why the Neotropical region holds the highest diversity of birds on Earth. Recently, there has been increased interest in morphological variation between and within species, and in how climate, topography, and anthropogenic pressures may explain and affect phenotypic variation. Because morphological data are not always available for many species at the local or regional scale, we are limited in our understanding of intra‐ and interspecies spatial morphological variation. Here, we present the ATLANTIC BIRD TRAITS , a data set that includes measurements of up to 44 morphological traits in 67,197 bird records from 2,790 populations distributed throughout the Atlantic forests of South America. This data set comprises information, compiled over two centuries (1820–2018), for 711 bird species, which represent 80% of all known bird diversity in the Atlantic Forest. Among the most commonly reported traits are sex ( n = 65,717), age ( n = 63,852), body mass ( n = 58,768), flight molt presence ( n = 44,941), molt presence ( n = 44,847), body molt presence ( n = 44,606), tail length ( n = 43,005), reproductive stage ( n = 42,588), bill length ( n = 37,409), body length ( n = 28,394), right wing length ( n = 21,950), tarsus length ( n = 20,342), and wing length ( n = 18,071). The most frequently recorded species are Chiroxiphia caudata ( n = 1,837), Turdus albicollis ( n = 1,658), Trichothraupis melanops ( n = 1,468), Turdus leucomelas ( n = 1,436), and Basileuterus culicivorus ( n = 1,384). The species recorded in the greatest number of sampling localities are Basileuterus culicivorus ( n = 243), Trichothraupis melanops ( n = 242), Chiroxiphia caudata ( n = 210), Platyrinchus mystaceus ( n = 208), and Turdus rufiventris ( n = 191). ATLANTIC BIRD TRAITS ( ABT ) is the most comprehensive data set on measurements of bird morphological traits found in a biodiversity hotspot; it provides data for basic and applied research at multiple scales, from individual to community, and from the local to the macroecological perspectives. No copyright or proprietary restrictions are associated with the use of this data set. Please cite this data paper when the data are used in publications or teaching and educational activities.

Mathematical models applied to thyroid cancer - Jairo Gomes da Silva; Rafael Martins de Morais; Izabel Cristina Rodrigues da Silva; Paulo Fernando de Arruda Mancera (Biophysical Reviews, 2019)

Phylogenetic and spatial analyses suggest minimum temperature as an environmental filter for turtle communities - João Fabrício Mota Rodrigues; Fernando Landa Sobral; John B. Iverson; José Alexandre Felizola Diniz‐Filho (Journal of Biogeography, 2019)
Aim This study aims to evaluate phylogenetic structure of turtle communities and their potential correlates on a global scale. More specifically, we tested whether cold temperatures and low precipitation could act as potential environmental filters of turtle communities and whether the dispersal limitation caused by altitudinal range could generate phylogenetic clustered patterns in these communities. Location Global. Taxon Turtles. Methods We used phylogenetic and distributional data of 257 species of turtles on a grid of 100 km × 100 km to generate measures of phylogenetic structure (mean nearest taxon distance and the mean pairwise distance, and their standardized effect sizes— SES ) of turtle communities using three different species pools. We evaluated the relationship between SES s with climatic and altitudinal data in order to evaluate our hypotheses. Finally, we inspected whether there was phylogenetic signal in the climatic variables classified as potential filters, as it is a basic assumption for using phylogenetic structure metrics to infer assembly rules. Results Phylogenetic clustering was generally stronger than phylogenetic overdispersion in turtle communities. There was a positive relationship between minimum temperature and the phylogenetic structure metrics, while minimum precipitation and altitudinal range were negatively related to these metrics. We found a strong phylogenetic signal in the minimum temperature, while precipitation had a weak signal. Main conclusions The positive correlation between phylogenetic community structure metrics and minimum temperature and the phylogenetic signal present in this climatic variable are in accordance with our initial hypothesis regarding minimum temperature acting as an environmental filter for turtles. However, we did not find evidence to support minimum precipitation as a filter. Altitudinal range followed the expected patterns, suggesting that it increases dispersal limitation and allows a concentration of closely related species.

Biochemical characterization of a Kunitz inhibitor from Inga edulis seeds with antifungal activity against Candida spp. - Heloisa Xavier Dib; Daniella Gorete Lourenço de Oliveira; Caio Fernando Ramalho de Oliveira; Gabriel Bonan Taveira; Erica de Oliveira Mello; Newton Valério Verbisk; Marilene Rodrigues Chang; Dario Corrêa Junior; Valdirene Moreira Gomes; Maria Lígia Rodrigues Macedo (Archives of Microbiology, 2019)

Ruminal and morphometric parameters of the rumen and intestines of sheep fed with increasing levels of spineless cactus (Nopalea cochenillifera Salm-Dyck) - Talma Jordana Lima; Roberto Germano Costa; Geovergue Rodrigues de Medeiros; Ariosvaldo Nunes de Medeiros; Neila Lidiany Ribeiro; Juliana Silva de Oliveira; Ricardo Romão Guerra; Francisco Fernando Ramos de Carvalho (Tropical Animal Health and Production, 2019)

Sugarcane Vinasse Cations Dynamics in Cerrado Soils, Brazil - Fernando Rodrigues Cabral Filho; Gustavo da Silva Vieira; Nelmício Furtado da Silva; Eduardo Sousa Cunha; Leonardo Nazário Silva dos Santos; Carlos Ribeiro Rodrigues; Fernando Nobre Cunha; Marconi Batista Teixeira; Frederico Antonio Loureiro Soares (Sugar Tech, 2019)

Development and characterization of novel microsatellite loci for the Blue-fronted Amazon (Amazona aestiva, Psittaciformes, Aves) and cross-species amplification for other two threatened Amazona species - Gislaine Aparecida Fernandes; Sarah Dobkowski-Marinho; Victor Fernandes Santos; Cássia Alves Lima-Rezende; Helder Elias da Silva; Fernando Pacheco Rodrigues; Renato Caparroz (Molecular Biology Reports, 2019)

Kinetic, equilibrium, and thermodynamic studies on the adsorption of ciprofloxacin by activated carbon produced from Jerivá (Syagrus romanzoffiana) - Caroline de Oliveira Carvalho; Daniel Lucas Costa Rodrigues; Éder Cláudio Lima; Cibele Santanna Umpierres; Diana Fernanda Caicedo Chaguezac; Fernando Machado Machado (Environmental Science and Pollution Research, 2019)

Seasonal dynamics of the water relations and photochemical efficiency of Copaifera langsdorffii Desf. co-occurring in savanna and seasonal forest - Angélica Lino Rodrigues; Angelo Albano da Silva Bertholdi; Luís Paulo Benetti Mantoan; Danilo Miralha Franco; Gustavo Habermann; Luiz Fernando Rolim de Almeida (Acta Physiologiae Plantarum, 2019)

ATLANTIC EPIPHYTES : a data set of vascular and non‐vascular epiphyte plants and lichens from the Atlantic Forest - Flavio Nunes Ramos; Sara Ribeiro Mortara; Nathalia Monalisa‐Francisco; João Pedro Costa Elias; Luiz Menini Neto; Leandro Freitas; Rodrigo Kersten; André Márcio Amorim; Fernando Bittencourt Matos; André Felippe Nunes‐Freitas; Suzana Alcantara; Marcia Helena Nagahama Alexandre; et al. (Ecology, 2019)
Epiphytes are hyper‐diverse and one of the frequently undervalued life forms in plant surveys and biodiversity inventories. Epiphytes of the Atlantic Forest, one of the most endangered ecosystems in the world, have high endemism and radiated recently in the Pliocene. We aimed to (1) compile an extensive Atlantic Forest data set on vascular, non‐vascular plants (including hemiepiphytes), and lichen epiphyte species occurrence and abundance; (2) describe the epiphyte distribution in the Atlantic Forest, in order to indicate future sampling efforts. Our work presents the first epiphyte data set with information on abundance and occurrence of epiphyte phorophyte species. All data compiled here come from three main sources provided by the authors: published sources (comprising peer‐reviewed articles, books, and theses), unpublished data, and herbarium data. We compiled a data set composed of 2,095 species, from 89,270 holo/hemiepiphyte records, in the Atlantic Forest of Brazil, Argentina, Paraguay, and Uruguay, recorded from 1824 to early 2018. Most of the records were from qualitative data (occurrence only, 88%), well distributed throughout the Atlantic Forest. For quantitative records, the most common sampling method was individual trees (71%), followed by plot sampling (19%), and transect sampling (10%). Angiosperms (81%) were the most frequently registered group, and Bromeliaceae and Orchidaceae were the families with the greatest number of records (27,272 and 21,945, respectively). Ferns and Lycophytes presented fewer records than Angiosperms, and Polypodiaceae were the most recorded family, and more concentrated in the Southern and Southeastern regions. Data on non‐vascular plants and lichens were scarce, with a few disjunct records concentrated in the Northeastern region of the Atlantic Forest. For all non‐vascular plant records, Lejeuneaceae, a family of liverworts, was the most recorded family. We hope that our effort to organize scattered epiphyte data help advance the knowledge of epiphyte ecology, as well as our understanding of macroecological and biogeographical patterns in the Atlantic Forest. No copyright restrictions are associated with the data set. Please cite this Ecology Data Paper if the data are used in publication and teaching events.

ATLANTIC ‐ PRIMATES : a dataset of communities and occurrences of primates in the Atlantic Forests of South America - Laurence Culot; Lucas Augusto Pereira; Ilaria Agostini; Marco Antônio Barreto de Almeida; Rafael Souza Cruz Alves; Izar Aximoff; Alex Bager; María Celia Baldovino; Thiago Ribas Bella; Júlio César Bicca‐Marques; Caryne Braga; Carlos Rodrigo Brocardo; et al. (Ecology, 2019)
Primates play an important role in ecosystem functioning and offer critical insights into human evolution, biology, behavior, and emerging infectious diseases. There are 26 primate species in the Atlantic Forests of South America, 19 of them endemic. We compiled a dataset of 5,472 georeferenced locations of 26 native and 1 introduced primate species, as hybrids in the genera Callithrix and Alouatta . The dataset includes 700 primate communities, 8,121 single species occurrences and 714 estimates of primate population sizes, covering most natural forest types of the tropical and subtropical Atlantic Forest of Brazil, Paraguay and Argentina and some other biomes. On average, primate communities of the Atlantic Forest harbor 2 ± 1 species (range = 1–6). However, about 40% of primate communities contain only one species. Alouatta guariba (N = 2,188 records) and Sapajus nigritus (N = 1,127) were the species with the most records. Callicebus barbarabrownae (N = 35), Leontopithecus caissara (N = 38), and Sapajus libidinosus (N = 41) were the species with the least records. Recorded primate densities varied from 0.004 individuals/km 2 ( Alouatta guariba at Fragmento do Bugre, Paraná, Brazil) to 400 individuals/km 2 ( Alouatta caraya in Santiago, Rio Grande do Sul, Brazil). Our dataset reflects disparity between the numerous primate census conducted in the Atlantic Forest, in contrast to the scarcity of estimates of population sizes and densities. With these data, researchers can develop different macroecological and regional level studies, focusing on communities, populations, species co‐occurrence and distribution patterns. Moreover, the data can also be used to assess the consequences of fragmentation, defaunation, and disease outbreaks on different ecological processes, such as trophic cascades, species invasion or extinction, and community dynamics. There are no copyright restrictions. Please cite this Data Paper when the data are used in publications. We also request that researchers and teachers inform us of how they are using the data.

Production of cold-adapted enzymes by filamentous fungi from King George Island, Antarctica - Alysson Wagner Fernandes Duarte; Mariana Blanco Barato; Fernando Suzigan Nobre; Danilo Augusto Polezel; Tássio Brito de Oliveira; Juliana Aparecida dos Santos; André Rodrigues; Lara Durães Sette (Polar Biology, 2018)

Hepatitis A Virus, Hepatitis E Virus, and Rotavirus in Foods of Animal Origin Traded at the Borders of Brazil, Argentina, and Uruguay - Juliano Gonçalves Pereira; Vanessa Mendonça Soares; Fernanda Gil de Souza; Leonardo Ereno Tadielo; Emanoelli Aparecida Rodrigues dos Santos; Mário Celso Sperotto Brum; Andreia Henzel; Eduarda Hallal Duval; Fernando Rosado Spilki; Wladimir Padilha da Silva (Food and Environmental Virology, 2018)

Pan‐tropical prediction of forest structure from the largest trees - Jean‐François Bastin; Ervan Rutishauser; James R. Kellner; Sassan Saatchi; Raphael Pélissier; Bruno Hérault; Ferry Slik; Jan Bogaert; Charles De Cannière; Andrew R. Marshall; John Poulsen; Patricia Alvarez‐Loyayza; et al. (Global Ecology and Biogeography, 2018)
Aim Large tropical trees form the interface between ground and airborne observations, offering a unique opportunity to capture forest properties remotely and to investigate their variations on broad scales. However, despite rapid development of metrics to characterize the forest canopy from remotely sensed data, a gap remains between aerial and field inventories. To close this gap, we propose a new pan‐tropical model to predict plot‐level forest structure properties and biomass from only the largest trees. Location Pan‐tropical. Time period Early 21st century. Major taxa studied Woody plants. Methods Using a dataset of 867 plots distributed among 118 sites across the tropics, we tested the prediction of the quadratic mean diameter, basal area, Lorey's height, community wood density and aboveground biomass (AGB) from the i th largest trees. Results Measuring the largest trees in tropical forests enables unbiased predictions of plot‐ and site‐level forest structure. The 20 largest trees per hectare predicted quadratic mean diameter, basal area, Lorey's height, community wood density and AGB with 12, 16, 4, 4 and 17.7% of relative error, respectively. Most of the remaining error in biomass prediction is driven by differences in the proportion of total biomass held in medium‐sized trees (50–70 cm diameter at breast height), which shows some continental dependency, with American tropical forests presenting the highest proportion of total biomass in these intermediate‐diameter classes relative to other continents. Main conclusions Our approach provides new information on tropical forest structure and can be used to generate accurate field estimates of tropical forest carbon stocks to support the calibration and validation of current and forthcoming space missions. It will reduce the cost of field inventories and contribute to scientific understanding of tropical forest ecosystems and response to climate change.

BRAZIL ROAD‐KILL: a data set of wildlife terrestrial vertebrate road‐kills - Clara Grilo; Michely R. Coimbra; Rafaela C. Cerqueira; Priscilla Barbosa; Rubem A. P. Dornas; Larissa O. Gonçalves; Fernanda Z. Teixeira; Igor Pfeifer Coelho; Brenda R. Schmidt; Diana L. K. Pacheco; Gabriela Schuck; Isadora B. Esperando; et al. (Ecology, 2018)
Mortality from collision with vehicles is the most visible impact of road traffic on wildlife. Mortality due to roads (hereafter road‐kill) can affect the dynamic of populations of many species and can, therefore, increase the risk of local decline or extinction. This is especially true in Brazil, where plans for road network upgrading and expansion overlaps biodiversity hotspot areas, which are of high importance for global conservation. Researchers, conservationists and road planners face the challenge to define a national strategy for road mitigation and wildlife conservation. The main goal of this dataset is a compilation of geo‐referenced road‐kill data from published and unpublished road surveys. This is the first Data Paper in the BRAZIL series (see ATLANTIC , NEOTROPICAL , and BRAZIL collections of Data Papers published in Ecology ), which aims make public road‐kill data for species in the Brazilian Regions. The dataset encompasses road‐kill records from 45 personal communications and 26 studies published in peer‐reviewed journals, theses and reports. The road‐kill dataset comprises 21,512 records, 83% of which are identified to the species level (n = 450 species). The dataset includes records of 31 amphibian species, 90 reptile species, 229 bird species, and 99 mammal species. One species is classified as Endangered, eight as Vulnerable and twelve as Near Threatened. The species with the highest number of records are: Didelphis albiventris (n = 1,549), Volatinia jacarina (n = 1,238), Cerdocyon thous (n = 1,135), Helicops infrataeniatus (n = 802), and Rhinella icterica (n = 692). Most of the records came from southern Brazil. However, observations of the road‐kill incidence for non‐Least Concern species are more spread across the country. This dataset can be used to identify which taxa seems to be vulnerable to traffic, analyze temporal and spatial patterns of road‐kill at local, regional and national scales and also used to understand the effects of road‐kill on population persistence. It may also contribute to studies that aims to understand the influence of landscape and environmental influences on road‐kills, improve our knowledge on road‐related strategies on biodiversity conservation and be used as complementary information on large‐scale and macroecological studies. No copyright or proprietary restrictions are associated with the use of this data set other than citation of this Data Paper.

Anti-Neospora caninum antibodies in feral cats on the Island of Fernando de Noronha, Brazil - Débora Costa Viegas de Lima; Fernando Jorge Rodrigues Magalhães; Muller Ribeiro Andrade; José Givanildo da Silva; Eduardo Guelfer Ferrer de Morais; Carlos Diógenes Ferreira de Lima Filho; Wagner José Nascimento Porto; Rinaldo Aparecido Mota (Acta Parasitologica, 2018)
Neospora caninum is a protozoan responsible for abortions, stillbirths (mainly among cattle) and neuromuscular diseases in dogs. Its importance in wild species and its impact on the environmental preservation of different ecosystems have been little described. This study aimed to investigate the presence of anti- N . caninum antibodies in feral cats on the island of Fernando de Noronha and contribute epidemiological data on this disease in these animals and its impact on the environmental preservation of the island. Serum samples from 257 feral cats on the island were analyzed through the Neospora agglutination test (NAT) to search for anti- Neospora caninum antibodies. Among the 257 serum samples analyzed, 8 (3.11%) were positive in the NAT. The antibody titers were 20 in seven animals (87.5%) and 40 in one animal (12.5%). These results demonstrate that feral cats are exposed to infection by N . caninum on the island of Fernando de Noronha, at a low frequency. Greater knowledge on this infection in this animal species in this insular environment is important for elucidating its impact on the conservation of species and the maintenance of this parasite on the island.

Nanoparticle vaccines against viral infections - Fernando B. Sulczewski; Raquel B. Liszbinski; Pedro R. T. Romão; Luiz Carlos Rodrigues Junior (Archives of Virology, 2018)

Antibacterial activity of extract and fractions from branches of Protium spruceanum and cytotoxicity on fibroblasts - Tatiane Roquete Amparo; Ivanildes Vasconcelos Rodrigues; Janaína Brandão Seibert; Rafaella Hilda Zaniti Souza; Amanda Ribeiro de Oliveira; Vivette Appolinário Rodrigues Cabral; Paula Melo de Abreu Vieira; Geraldo Célio Brandão; Adriana Akemi Okuma; Sidney Augusto Vieira Filho; Luiz Fernando Medeiros Teixeira; Gustavo Henrique Bianco de Souza (Natural Product Research, 2018)

Targeting the mitochondrial VDAC in hepatocellular carcinoma using a polyclonal antibody-conjugated to a nitrosyl ruthenium complex - Loyanne C. B. Ramos; Fernando P. Rodrigues; Juliana C. Biazzotto; Sergio de Paula Machado; Leonardo D. Slep; Michael R. Hamblin; Roberto S. da Silva (JBIC Journal of Biological Inorganic Chemistry, 2018)

Maternal care, larviparous and oviparous reproduction of Hypoaspis larvicolus (Acari: Laelapidae) feeding on astigmatid mites - Ibrahim Cakmak; Fernando Rodrigues da Silva (Experimental and Applied Acarology, 2018)

Biomonitoring birds: the use of a micronuclei test as a tool to assess environmental pollutants on coffee farms in southeast Brazil - Henrique Nazareth Souto; Edimar Olegário de Campos Júnior; Carlos Fernando Campos; Tamiris Sabrina Rodrigues; Boscolli Barbosa Pereira; Sandra Morelli (Environmental Science and Pollution Research, 2018)

Short-time analysis of shoreline based on RapidEye satellite images in the terminal area of Pecém Port, Ceará, Brazil - Cynthia Romariz Duarte; Fernando Pellon de Miranda; Luiz Landau; Michael Vandesteen Silva Souto; José Antonio Beltrão Sabadia; Claudio Ângelo da Silva Neto; Linara Ivina de Castro Rodrigues; Aline Moreira Damasceno (International Journal of Remote Sensing, 2018)

BioTIME: A database of biodiversity time series for the Anthropocene - Maria Dornelas; Laura H. Antão; Faye Moyes; Amanda E. Bates; Anne E. Magurran; Dušan Adam; Asem A. Akhmetzhanova; Ward Appeltans; José Manuel Arcos; Haley Arnold; Narayanan Ayyappan; Gal Badihi; et al. (Global Ecology and Biogeography, 2018)
Motivation The BioTIME database contains raw data on species identities and abundances in ecological assemblages through time. These data enable users to calculate temporal trends in biodiversity within and amongst assemblages using a broad range of metrics. BioTIME is being developed as a community‐led open‐source database of biodiversity time series. Our goal is to accelerate and facilitate quantitative analysis of temporal patterns of biodiversity in the Anthropocene. Main types of variables included The database contains 8,777,413 species abundance records, from assemblages consistently sampled for a minimum of 2 years, which need not necessarily be consecutive. In addition, the database contains metadata relating to sampling methodology and contextual information about each record. Spatial location and grain BioTIME is a global database of 547,161 unique sampling locations spanning the marine, freshwater and terrestrial realms. Grain size varies across datasets from 0.0000000158 km 2 (158 cm 2 ) to 100 km 2 (1,000,000,000,000 cm 2 ). Time period and grain BioTIME records span from 1874 to 2016. The minimal temporal grain across all datasets in BioTIME is a year. Major taxa and level of measurement BioTIME includes data from 44,440 species across the plant and animal kingdoms, ranging from plants, plankton and terrestrial invertebrates to small and large vertebrates. Software format .csv and .SQL.

Correction to: Can in vivo surface dental enamel microbiopsies be used to measure remote lead exposure? - Kelly Polido Kaneshiro Olympio; Manuel Fernando Gonzalez Huila; Cristiane de Almeida Baldini Cardoso; Ana Paula Sacone da Silva Ferreira; Adrielly Garcia Ortiz; Henrique Eisi Toma; Ricardo Henrique Alves da Silva; Maciel Santos Luz; Maria Regina Alves Cardoso; Gislayne Aparecida Rodrigues Kelmer; Pedro Vitoriano de Oliveira; Etelvino José Henriques Bechara; et al. (Environmental Science and Pollution Research, 2018)

Can in vivo surface dental enamelmicrobiopsies be used to measure remote lead exposure? - Kelly Polido Kaneshiro Olympio; Manuel Fernando Gonzalez Huila; Cristiane de Almeida Baldini Cardoso; Ana Paula Sacone da Silva Ferreira; Adrielly Garcia Ortiz; Henrique Eisi Toma; Ricardo Henrique Alves da Silva; Maciel Santos Luz; Maria Regina Alves Cardoso; Gislayne Aparecida Rodrigues Kelmer; Pedro Vitoriano de Oliveira; Etelvino José Henriques Bechara; et al. (Environmental Science and Pollution Research, 2018)

Sodium trimetaphosphate and hexametaphosphate impregnated with silver nanoparticles: characteristics and antimicrobial efficacy - Carla Corrêa Mendes-Gouvêa; Jackeline Gallo do Amaral; Renan Aparecido Fernandes; Gabriela Lopes Fernandes; Luiz Fernando Gorup; Emerson Rodrigues Camargo; Alberto Carlos Botazzo Delbem; Debora Barros Barbosa (Biofouling, 2018)

The role of topography, river size and riverbed grain size on the preservation of riverine mollusk shells - Alcemar Rodrigues Martello; Carla Bender Kotzian; Fernando Erthal (Journal of Paleolimnology, 2018)

First Report on vanA-Enterococcus faecalis Recovered from Soils Subjected to Long-Term Livestock Agricultural Practices in Azores Archipelago - Vanessa Silva; Fernando Peixoto; Gilberto Igrejas; Carolina Parelho; Patrícia Garcia; Isabel Carvalho; Margarida Sousa; José Eduardo Pereira; Armindo Rodrigues; Patrícia Alexandra Curado Quintas D Poeta (International Journal of Environmental Research, 2018)

Diversity of teiid lizards from Gran Chaco and Western Cerrado (Squamata: Teiidae) - Federico José Arias; Renato Recoder; Blanca Beatriz Álvarez; Eduardo Ethcepare; Matias Quipildor; Fernando Lobo; Miguel Trefaut Rodrigues (Zoologica Scripta, 2018)
The Gran Chaco dry forest ecoregion corresponds to the southern portion of the South America diagonal belt of open formations, being one of the most threatened subtropical woodland savannas in the world. The area is still poorly known biologically and has been suffering with impressively high forest cover loss in the last 10 years. Integrating morphological and molecular data, we detected and describe a cryptic new species of lizard genus Ameivula endemic from the eastern part of this ecoregion, the called Humid Chaco. Ameivula apipensis sp nov. is characterised by a whitish brown vertebral stripe in adults and juveniles, a lateral field without ocelli and with overlapping spot, presence of an interfrontoparietal scale in 46.2% of the specimens, 12–17 femoral pores, an hemipenis without lateral sac, five xiphisternal ribs, and by a combination of meristic features as confirmed by discriminant analysis. The new species was recovered sister to a clade from Western Cerrado in our analysis, the first phylogenetic hypothesis for the Ameivula and Glaucomastix genera based on 1977 base pairs of three mitochondrial (12S, 16S and cyt‐ b ) and one nuclear (c‐mos) genes, including all the recognised species at the moment. Maximum parsimony and Bayesian inference recovered the monophyly of Ameivula and Glaucomastix with strong support. Reinforcing previous studies, our results suggest the presence of additional cryptic species in Ameivula from the Western Cerrado.

Larval aggregation in a Neotropical butterfly: risky behaviors, per capita risk, and larval responses in Ascia monuste orseis - Alessandra F. K. Santana; Daniela Rodrigues; Fernando S. Zucoloto (Behavioral Ecology and Sociobiology, 2017)

Biogeography of mutualistic fungi cultivated by leafcutter ants - Ulrich G. Mueller; Heather D. Ishak; Sofia M. Bruschi; Chad C. Smith; Jacob J. Herman; Scott E. Solomon; Alexander S. Mikheyev; Christian Rabeling; Jarrod J. Scott; Michael Cooper; Andre Rodrigues; Adriana Ortiz; et al. (Molecular Ecology, 2017)
Leafcutter ants propagate co‐evolving fungi for food. The nearly 50 species of leafcutter ants ( Atta , Acromyrmex ) range from Argentina to the United States, with the greatest species diversity in southern South America. We elucidate the biogeography of fungi cultivated by leafcutter ants using DNA sequence and microsatellite‐marker analyses of 474 cultivars collected across the leafcutter range. Fungal cultivars belong to two clades (Clade‐A and Clade‐B). The dominant and widespread Clade‐A cultivars form three genotype clusters, with their relative prevalence corresponding to southern South America, northern South America, Central and North America. Admixture between Clade‐A populations supports genetic exchange within a single species, Leucocoprinus gongylophorus . Some leafcutter species that cut grass as fungicultural substrate are specialized to cultivate Clade‐B fungi, whereas leafcutters preferring dicot plants appear specialized on Clade‐A fungi. Cultivar sharing between sympatric leafcutter species occurs frequently such that cultivars of Atta are not distinct from those of Acromyrmex . Leafcutters specialized on Clade‐B fungi occur only in South America. Diversity of Clade‐A fungi is greatest in South America, but minimal in Central and North America. Maximum cultivar diversity in South America is predicted by the Kusnezov–Fowler hypothesis that leafcutter ants originated in subtropical South America and only dicot‐specialized leafcutter ants migrated out of South America, but the cultivar diversity becomes also compatible with a recently proposed hypothesis of a Central American origin by postulating that leafcutter ants acquired novel cultivars many times from other nonleafcutter fungus‐growing ants during their migrations from Central America across South America. We evaluate these biogeographic hypotheses in the light of estimated dates for the origins of leafcutter ants and their cultivars.

ATLANTIC ‐ CAMTRAPS : a dataset of medium and large terrestrial mammal communities in the Atlantic Forest of South America - Fernando Lima; Gabrielle Beca; Renata L. Muylaert; Clinton N. Jenkins; Miriam L. L. Perilli; Ana Maria O. Paschoal; Rodrigo L. Massara; Adriano P. Paglia; Adriano G. Chiarello; Maurício E. Graipel; Jorge J. Cherem; André L. Regolin; et al. (Ecology, 2017)
Our understanding of mammal ecology has always been hindered by the difficulties of observing species in closed tropical forests. Camera trapping has become a major advance for monitoring terrestrial mammals in biodiversity rich ecosystems. Here we compiled one of the largest datasets of inventories of terrestrial mammal communities for the Neotropical region based on camera trapping studies. The dataset comprises 170 surveys of medium to large terrestrial mammals using camera traps conducted in 144 areas by 74 studies, covering six vegetation types of tropical and subtropical Atlantic Forest of South America (Brazil and Argentina), and present data on species composition and richness. The complete dataset comprises 53,438 independent records of 83 species of mammals, includes 10 species of marsupials, 15 rodents, 20 carnivores, eight ungulates and six armadillos. Species richness averaged 13 species (±6.07 SD ) per site. Only six species occurred in more than 50% of the sites: the domestic dog Canis familiaris , crab‐eating fox Cerdocyon thous , tayra Eira barbara , south American coati Nasua nasua , crab‐eating raccoon Procyon cancrivorus and the nine‐banded armadillo Dasypus novemcinctus . The information contained in this dataset can be used to understand macroecological patterns of biodiversity, community, and population structure, but also to evaluate the ecological consequences of fragmentation, defaunation, and trophic interactions.

Global patterns of interaction specialization in bird–flower networks - Thais B. Zanata; Bo Dalsgaard; Fernando C. Passos; Peter A. Cotton; James J. Roper; Pietro K. Maruyama; Erich Fischer; Matthias Schleuning; Ana M. Martín González; Jeferson Vizentin‐Bugoni; Donald C. Franklin; Stefan Abrahamczyk; et al. (Journal of Biogeography, 2017)
Aim Among the world's three major nectar‐feeding bird taxa, hummingbirds are the most phenotypically specialized for nectarivory, followed by sunbirds, while the honeyeaters are the least phenotypically specialized taxa. We tested whether this phenotypic specialization gradient is also found in the interaction patterns with their floral resources. Location Americas, Africa, Asia and Oceania/Australia. Methods We compiled interaction networks between birds and floral resources for 79 hummingbird, nine sunbird and 33 honeyeater communities. Interaction specialization was quantified through connectance ( C ), complementary specialization ( H 2 ′), binary ( Q B ) and weighted modularity ( Q ), with both observed and null‐model corrected values. We compared interaction specialization among the three types of bird–flower communities, both independently and while controlling for potential confounding variables, such as plant species richness, asymmetry, latitude, insularity, topography, sampling methods and intensity. Results Hummingbird–flower networks were more specialized than honeyeater–flower networks. Specifically, hummingbird–flower networks had a lower proportion of realized interactions (lower C ), decreased niche overlap (greater H 2 ′) and greater modularity (greater Q B ). However, we found no significant differences between hummingbird– and sunbird–flower networks, nor between sunbird– and honeyeater–flower networks. Main conclusions As expected, hummingbirds and their floral resources have greater interaction specialization than honeyeaters, possibly because of greater phenotypic specialization and greater floral resource richness in the New World. Interaction specialization in sunbird–flower communities was similar to both hummingbird–flower and honeyeater–flower communities. This may either be due to the relatively small number of sunbird–flower networks available, or because sunbird–flower communities share features of both hummingbird–flower communities (specialized floral shapes) and honeyeater–flower communities (fewer floral resources). These results suggest a link between interaction specialization and both phenotypic specialization and floral resource richness within bird–flower communities at a global scale.

Life cycle thinking in Brazil: challenges and advances towards a more comprehensive practice - Danielle Maia de Souza; Tiago Braga; Maria Cléa Brito de Figueirêdo; Marília I. S. Folegatti Matsuura; Fernando Rodrigues Teixeira Dias; Cássia Maria Lie Ugaya (The International Journal of Life Cycle Assessment, 2017)

Chronic enalapril treatment increases transient outward potassium current in cardiomyocytes isolated from right ventricle of spontaneously hypertensive rats - Luiz Fernando Rodrigues Junior; Ana Carolina de Azevedo Carvalho; Enildo Broetto Pimentel; José Geraldo Mill; José Hamilton Matheus Nascimento (Naunyn-Schmiedeberg's Archives of Pharmacology, 2017)

Space-time modeling for post-fire vegetation recovery - Lucia Paci; Alan E. Gelfand; María Asunción Beamonte; Marcos Rodrigues; Fernando Pérez-Cabello (Stochastic Environmental Research and Risk Assessment, 2017)

Phylogenetic analysis of rabies virus isolated from canids in North and Northeast Brazil - Débora Nunes de Souza; Pedro Carnieli; Carla Isabel Macedo; Rafael de Novaes Oliveira; Helena Beatriz de Carvalho Ruthner Batista; Adriana Candido Rodrigues; Patricia Mariano Cruz Pereira; Samira Maria Achkar; Luiz Fernando Pereira Vieira; Juliana Galera Castilho Kawai (Archives of Virology, 2017)

Filamentous Fungi Isolates of Contaminated Sediment in the Amazon Region with the Potential for Benzo(a)pyrene Degradation - Hilton Marcelo de Lima Souza; Lara Durães Sette; Adolfo José da Mota; Joaquim Ferreira do Nascimento Neto; André Rodrigues; Tássio Brito de Oliveira; Fernando Mendes de Oliveira; Luiz Antônio de Oliveira; Hileia dos Santos Barroso; Sandra Patricia Zanotto (Water, Air, & Soil Pollution, 2016)

Adsorption of arsenic from water and its recovery as a highly active photocatalyst - Rodrigo C. Hott; Thaina G. Andrade; Mayra S. Santos; Anne C. F. Lima; Márcia C. S. Faria; Cleide A. Bomfeti; Fernando Barbosa; Luiz F. O. Maia; Luiz C. A. Oliveira; Márcio C. Pereira; Jairo L. Rodrigues (Environmental Science and Pollution Research, 2016)

Behavioral profile assessment in offspring of Swiss mice treated during pregnancy and lactation with caffeine - Roberto Laureano-Melo; Anderson Luiz Bezerra da Silveira; Fernando de Azevedo Cruz Seara; Rodrigo Rodrigues da Conceição; Cláudio da Silva-Almeida; Bruno Guimarães Marinho; Fábio Fagundes da Rocha; Luís Carlos Reis; Wellington da Silva Côrtes (Metabolic Brain Disease, 2016)

Use of sugarcane filter cake and nitrogen, phosphorus and potassium fertilization in the process of bioremediation of soil contaminated with diesel - Fernando Reynel Fundora Tellechea; Marco Antônio Martins; Alexsandro Araujo da Silva; Emanuela Forestieri da Gama-Rodrigues; Meire Lelis Leal Martins (Environmental Science and Pollution Research, 2016)

Does retention or exportation occur in the larvae of the mud shrimp Upogebia vasquezi (Decapoda, Gebiidea)? Implications for the reproductive strategy of the species on the Amazon coast - Danielly Brito de Oliveira; Jussara Moretto Martinelli-Lemos; Adelson Silva de Souza; Jossianne Rodrigues da Costa; Fernando Araújo Abrunhosa (Hydrobiologia, 2016)

“Watching the Detectives” report of the general assembly of the EU project DETECTIVE Brussels, 24–25 November 2015 - Ruani N. Fernando; Umesh Chaudhari; Sylvia E. Escher; Jan G. Hengstler; Jürgen Hescheler; Paul Jennings; Hector C. Keun; Jos C. S. Kleinjans; Raivo Kolde; Laxmikanth Kollipara; Annette Kopp-Schneider; Alice Limonciel; et al. (Archives of Toxicology, 2016)

Recurrent connections between Amazon and Atlantic forests shaped diversity in Caatinga four‐eyed frogs - Maria Tereza C. Thomé; Fernando Sequeira; Francisco Brusquetti; Bryan Carstens; Célio F. B. Haddad; Miguel Trefaut Rodrigues; João Alexandrino (Journal of Biogeography, 2016)
Aim The Caatinga is a widespread but poorly known biome in South America. Its historical stability is controversial and different types of evidence provide support to contrasting hypotheses. We investigate how past biome dynamics may have caused diversification in the endemic four‐eyed frog genus Pleurodema . Location Caatinga biome. Methods We sampled 353 individuals of Pleurodema alium and Pleurodema diplolister from 60 localities and genotyped them at 12 ( P. alium ) or 20 ( P. diplolister ) microsatellite loci. We sequenced a mitochondrial fragment for a subset (199) of the samples. After exploratory analyses to infer genetic structure between and within species, we designed seven biogeographical scenarios based on the literature on species distributions, palaeomodels and geological palaeoindicators. We tested these hypotheses by calculating the posterior probability of models using multilocus approximate Bayesian computation ( ABC ). Results Both markers recovered well‐defined interspecific limits with restricted introgression, but population structure within P. diplolister is subtle and affected by isolation by distance. Model selection using ABC supported two scenarios of diversification that included recent demographic growth. Genetic breaks at intra‐ and interspecific levels were geographically coincident, and correlated with past forest invasions reported in the literature. Main conclusions Our data support the idea that past expansions of the Amazon and Atlantic forests over the current Caatinga distribution shaped the genetic structure in endemic four‐eyed frogs at more than one level by promoting intermittent vicariance. Additional support comes from the distribution patterns of forest and C aatinga taxa. Variation among groups suggests differential organismal responses to past habitat shifts, probably mediated by specific natural‐history traits. This paper provides the first direct evidence that taxa endemic to the C aatinga were affected by past forest interactions.

A comparative evaluation of biological activities and bioactive compounds of the seagrasses Zostera marina and Zostera noltei from southern Portugal - Luísa Custódio; Simona Laukaityte; Aschwin H. Engelen; Maria João Rodrigues; Hugo Pereira; Catarina Vizetto-Duarte; Luísa Barreira; Hortensia Rodríguez; Fernando Alberício; João Varela (Natural Product Research, 2016)

Myelin Lipids Inhibit Axon Regeneration Following Spinal Cord Injury: a Novel Perspective for Therapy - Fernando M. Mar; Tiago F. da Silva; Marlene M. Morgado; Lorena G. Rodrigues; Daniel Rodrigues; Marta I. L. Pereira; Ana Marques; Vera F. Sousa; João Coentro; Clara Sá-Miranda; Mónica M. Sousa; Pedro Brites (Molecular Neurobiology, 2016)

Long‐term elevated air [ CO 2 ] strengthens photosynthetic functioning and mitigates the impact of supra‐optimal temperatures in tropical Coffea arabica and C. canephora species - Weverton P. Rodrigues; Madlles Q. Martins; Ana S. Fortunato; Ana P. Rodrigues; José N. Semedo; Maria C. Simões‐Costa; Isabel P. Pais; António E. Leitão; Filipe Colwell; Luis Goulao; Cristina Máguas; Rodrigo Maia; et al. (Global Change Biology, 2016)
The tropical coffee crop has been predicted to be threatened by future climate changes and global warming. However, the real biological effects of such changes remain unknown. Therefore, this work aims to link the physiological and biochemical responses of photosynthesis to elevated air [ CO 2 ] and temperature in cultivated genotypes of C offea arabica L. (cv. Icatu and IPR 108) and Coffea canephora cv. Conilon CL 153. Plants were grown for ca. 10 months at 25/20 °C (day/night) and 380 or 700 μl CO 2 l −1 and then subjected to temperature increase (0.5 °C day −1 ) to 42/34 °C. Leaf impacts related to stomatal traits, gas exchanges, C isotope composition, fluorescence parameters, thylakoid electron transport and enzyme activities were assessed at 25/20, 31/25, 37/30 and 42/34 °C. The results showed that (1) both species were remarkably heat tolerant up to 37/30 °C, but at 42/34 °C a threshold for irreversible nonstomatal deleterious effects was reached. Impairments were greater in C. arabica (especially in Icatu) and under normal [ CO 2 ]. Photosystems and thylakoid electron transport were shown to be quite heat tolerant, contrasting to the enzymes related to energy metabolism, including RuBis CO , which were the most sensitive components. (2) Significant stomatal trait modifications were promoted almost exclusively by temperature and were species dependent. Elevated [ CO 2 ], (3) strongly mitigated the impact of temperature on both species, particularly at 42/34 °C, modifying the response to supra‐optimal temperatures, (4) promoted higher water‐use efficiency under moderately higher temperature (31/25 °C) and (5) did not provoke photosynthetic downregulation. Instead, enhancements in [ CO 2 ] strengthened photosynthetic photochemical efficiency, energy use and biochemical functioning at all temperatures. Our novel findings demonstrate a relevant heat resilience of coffee species and that elevated [ CO 2 ] remarkably mitigated the impact of heat on coffee physiology, therefore playing a key role in this crop sustainability under future climate change scenarios.

Reproductive and productive performances of Santa Inês ewes submitted to breeding in different periods of the Amazonian humid tropical climate - Felipe Nogueira Soares; Maria Emilia Franco Oliveira; Luciana Cristina Padilha-Nakaghi; Luís Guilherme de Oliveira; Marcus Antônio Rossi Feliciano; Felipe Brener Bezerra de Oliveira; Pedro Paulo Maia Teixeira; Wilter Ricardo Russiano Vicente; Cristian Faturi; Luiz Fernando de Souza Rodrigues (Tropical Animal Health and Production, 2015)

Prevalence of Mycobacterium avium subsp. paratuberculosis and Escherichia coli in blood samples from patients with inflammatory bowel disease - Nair Nazareth; Fernando Magro; Elisabete Machado; Teresa Gonçalves Ribeiro; António Martinho; Pedro Rodrigues; Rita Alves; Gonçalo Nuno Macedo; Daniela Gracio; Rosa Coelho; Candida Abreu; Rui Appelberg; et al. (Medical Microbiology and Immunology, 2015)

Activation of the aryl hydrocarbon receptor by carcinogenic aromatic amines and modulatory effects of their N-acetylated metabolites - Ludmila Juricek; Linh-Chi Bui; Florent Busi; Stéphane Pierre; Erwan Guyot; Aazdine Lamouri; Jean-Marie Dupret; Robert Barouki; Xavier Coumoul; Fernando Rodrigues-Lima (Archives of Toxicology, 2015)

Human adenovirus spread, rainfalls, and the occurrence of gastroenteritis cases in a Brazilian basin - Manoela Tressoldi Rodrigues; Andréia Henzel; Rodrigo Staggemeier; Daniela Muller de Quevedo; Caroline Rigotto; Larissa Heinzelmann; Carlos Augusto do Nascimento; Fernando Rosado Spilki (Environmental Monitoring and Assessment, 2015)

Inhibition of cyclin-dependent kinase CDK1 by oxindolimine ligands and corresponding copper and zinc complexes - Rodrigo Bernardi Miguel; Philippe Alexandre Divina Petersen; Fernando A. Gonzales-Zubiate; Carla Columbano Oliveira; Naresh Kumar; Rafael Rodrigues do Nascimento; Helena Maria Petrilli; Ana Maria da Costa Ferreira (JBIC Journal of Biological Inorganic Chemistry, 2015)

Resistance to Cowpea aphid-borne mosaic virus in species and hybrids of Passiflora: advances for the control of the passion fruit woodiness disease in Brazil - Eileen Azevedo Santos; Alexandre Pio Viana; Josie Cloviane de Oliveira Freitas; Fernando Higino de Lima e Silva; Rosana Rodrigues; Marcelo Eiras (European Journal of Plant Pathology, 2015)

Toxicological effects of metal-EDTA/NTA complex formation in a synthetic medium on the macroalga Gracilaria domingensis - Luiz Fernando Mendes; Leonardo Zambotti-Villela; Cintia Simas-Rodrigues; Pio Colepicolo (Journal of Applied Phycology, 2015)

Nellore cows and their calves during the lactation period: performance, intake, milk composition, and total apparent digestibility - Luiz Fernando Costa e Silva; Terry Eugene Engle; Sebastião de Valadares Filho; Polyana Pizzi Rotta; Faider Alberto Castaño Villadiego; Flávia Adriane Sales Silva; Edilane Costa Martins; Luis Henrique Rodrigues Silva; Mário Fonseca Paulino (Tropical Animal Health and Production, 2015)

A Kinetic Characterization of (Na+, K+)-ATPase Activity in the Gills of the Pelagic Seabob Shrimp Xiphopenaeus kroyeri (Decapoda, Penaeidae) - Francisco Assis Leone; Malson Neilson Lucena; Luciana Augusto Rezende; Daniela Pereira Garçon; Marcelo Rodrigues Pinto; Fernando Luis Mantelatto; John Campbell McNamara (The Journal of Membrane Biology, 2015)

Botryococcus braunii and Nannochloropsis oculata extracts inhibit cholinesterases and protect human dopaminergic SH-SY5Y cells from H2O2-induced cytotoxicity - Luísa Custódio; Fernando Soares; Hugo Pereira; Maria João Rodrigues; Luísa Barreira; Amélia Pilar Rauter; Fernando Alberício; João Varela (Journal of Applied Phycology, 2015)

Escovopsis trichodermoides sp. nov., isolated from a nest of the lower attine ant Mycocepurus goeldii - Virginia E. Masiulionis; Marta N. Cabello; Keith A. Seifert; Andre Rodrigues; Fernando C. Pagnocca (Antonie van Leeuwenhoek, 2015)

OCT4 mutations in human erythroleukemic cells: implications for multiple drug resistance (MDR) phenotype - Bruno Rodrigues Oliveira; Marcio Azevedo Figueiredo; Gilma Santos Trindade; Luis Fernando Marins (Molecular and Cellular Biochemistry, 2015)

Modelling the risk of invasion by the red-swamp crayfish (Procambarus clarkii): incorporating local variables to better inform management decisions - Francisco D. Moreira; Fernando Ascensão; César Capinha; Diana Rodrigues; Pedro Segurado; Margarida Santos-Reis; Rui Rebelo (Biological Invasions, 2015)

Subcellular localization of p29, a putative movement protein of pepper ringspot virus - Kelly B. Rodrigues; Anelise F. Orílio; Rosana Blawid; Fernando L. Melo; Tatsuya Nagata (Archives of Virology, 2015)

Neuroprotective Effect of Diphenyl Diselenide in a Experimental Stroke Model: Maintenance of Redox System in Mitochondria of Brain Regions - Fernando Dobrachinski; Michele Hinerasky da Silva; Cíntia Letícia Cardias Tassi; Nélson Rodrigues de Carvalho; Glaecir Roseni Mundstock Dias; Ronaldo Medeiros Golombieski; Élgion Lúcio da Silva Loreto; João Batista Teixeira da Rocha; Michele Rechia Fighera; Félix Alexandre Antunes Soares (Neurotoxicity Research, 2014)

The Impact of Uranium Mine Contamination of Soils on Plant Litter Decomposition - Ana C. Freitas; Dina Rodrigues; Teresa A. P. Rocha-Santos; Fernando Gonçalves; Armando C. Duarte; Ruth Pereira (Archives of Environmental Contamination and Toxicology, 2014)

Yeasts found on an ephemeral reproductive caste of the leaf-cutting ant Atta sexdens rubropilosa - Silvio Lovato Arcuri; Fernando Carlos Pagnocca; Weilan Gomes da Paixão Melo; Nilson Satoru Nagamoto; Dirce Leimi Komura; Andre Rodrigues (Antonie van Leeuwenhoek, 2014)

Unique RNA 2 sequences of two Brazilian isolates of Pepper ringspot virus, a tobravirus - Adriana Ribeiro Silva Batista; Cícero Nicolini; Kelly Barreto Rodrigues; Fernando Lucas Melo; Raquel Medeiros Vasques; Mônica Alves de Macêdo; Alice Kazuko Inoue-Nagata; Tatsuya Nagata (Virus Genes, 2014)

Effects of environmentally relevant concentrations of metallic compounds on the flatfish Scophthalmus maximus: biomarkers of neurotoxicity, oxidative stress and metabolism - Bruno Nunes; Fátima Brandão; Tânia Sérgio; Sara Rodrigues; Fernando Gonçalves; Alberto Teodorico Correia (Environmental Science and Pollution Research, 2014)

HOE-140, an antagonist of B2 receptor, protects against memory deficits and brain damage induced by moderate lateral fluid percussion injury in mice - Ana Paula Oliveira Ferreira; Fernanda Silva Rodrigues; Iuri Domingues Della-Pace; Bibiana Castagna Mota; Sara Marchesan Oliveira; Camila de Campos Velho Gewehr; Franciane Bobinski; Clarissa Vasconcelos de Oliveira; Juliana Sperotto Brum; Mauro Schneider Oliveira; Ana Flavia Furian; Claudio Severo Lombardo de Barros; et al. (Psychopharmacology, 2014)

Are seed germination and ecological breadth associated? Testing the regeneration niche hypothesis with bromeliads in a heterogeneous neotropical montane vegetation - Andréa Rodrigues Marques; Allbens P. F. Atman; Fernando A. O. Silveira; José Pires de Lemos-Filho (Plant Ecology, 2014)

Species delimitation, patterns of diversification and historical biogeography of the N eotropical frog genus A denomera ( A nura, L eptodactylidae) - Antoine Fouquet; Carla Santana Cassini; Célio Fernando Baptista Haddad; Nicolas Pech; Miguel Trefaut Rodrigues (Journal of Biogeography, 2014)
Aim For many taxa, inaccuracy of species boundaries and distributions hampers inferences about diversity and evolution. This is particularly true in the Neotropics where prevalence of cryptic species has often been demonstrated. The frog genus Adenomera is suspected to harbour many more species than the 16 currently recognized. These small terrestrial species occur in Amazonia, Atlantic Forest ( AF ), and in the open formations of the Dry Diagonal ( DD : Chaco, Cerrado and Caatinga). This widespread and taxonomically complex taxon provides a good opportunity to (1) test species boundaries, and (2) investigate historical connectivity between Amazonia and the AF and associated patterns of diversification. Location Tropical South America east of the Andes. Methods We used molecular data (four loci) to estimate phylogenetic relationships among 320 Adenomera samples. These results were integrated with other lines of evidence to propose a conservative species delineation. We subsequently used an extended dataset (seven loci) and investigated ancestral area distributions, dispersal–vicariance events, and the temporal pattern of diversification within Adenomera . Results Our conservative delineation identified 31 Confirmed Candidate Species (four remaining unconfirmed) representing a 94% increase in species richness. The biogeographical analysis suggested an Amazonian origin of Adenomera with as many as three dispersals to the DD and one to the AF during the Miocene. These dispersals were associated with habitat shifts from forest towards open habitats. Main conclusions The DD played a major role in the history of Adenomera in limiting dispersal and favouring diversification of open‐habitat lineages. Moreover, a forest bridge during the Miocene Climatic Optimum may have permitted dispersal from Amazonia towards the AF and subsequent diversification. Uncovering species boundaries and distributions might drastically change inferences based on currently perceived distribution patterns.

Fatty acid composition and biological activities of Isochrysis galbana T-ISO, Tetraselmis sp. and Scenedesmus sp.: possible application in the pharmaceutical and functional food industries - Luísa Custódio; Fernando Soares; Hugo Pereira; Luísa Barreira; Catarina Vizetto-Duarte; Maria João Rodrigues; Amélia Pilar Rauter; Fernando Alberício; João Varela (Journal of Applied Phycology, 2014)

Kelps across the portuguese coast: evidence of top-down and bottom-up influences - Franco Joao; Wernberg Thomas; Bertocci Iacopo; Arenas Francisco; Martínez Brezo; Duarte Pedro; Jacinto David; Vasco-Rodrigues Nuno; Sousa-Pinto Isabel; Tuya Fernando (Frontiers in Marine Science, 2014)

Increasing the density of markers around a major QTL controlling resistance to angular leaf spot in common bean - Paula Rodrigues Oblessuc; Juliana Morini Kupper Cardoso Perseguini; Renata Moro Baroni; Alisson Fernando Chiorato; Sérgio Augusto Morais Carbonell; Jorge Mauricio Costa Mondego; Ramon Oliveira Vidal; Luis Eduardo Aranha Camargo; Luciana Lasry Benchimol-Reis (Theoretical and Applied Genetics, 2013)

Mercury Toxicity to Freshwater Organisms: Extrapolation Using Species Sensitivity Distribution - Andreia C. M. Rodrigues; Fátima T. Jesus; Marco A. F. Fernandes; Fernando Morgado; Amadeu M. V. M. Soares; Sizenando N. Abreu (Bulletin of Environmental Contamination and Toxicology, 2013)

Mango tree pruning hay in substitution of elephant grass in cattle diet - Rafael Torres de Souza Rodrigues; Mario Luiz Chizzotti; Daniel Ribeiro Menezes; Fernando Santos Costa; Carlos Wagner de Souza Wanderley; Álvaro Santos Lisboa Neto (Tropical Animal Health and Production, 2013)

Risk assessment of Cry toxins of Bacillus thuringiensis on the predatory mites Euseius concordis and Neoseiulus californicus (Acari: Phytoseiidae) - Thiago Rodrigues de Castro; John Jairo Saldarriaga Ausique; Daiane Heloisa Nunes; Fernando Henrique Ibanhes; Italo Delalibera Júnior (Experimental and Applied Acarology, 2013)

Presence of Torque Teno Virus (TTV) in Tap Water in Public Schools from Southern Brazil - Andréia Dalla Vecchia; Mariana Kluge; Joseane V. dos Santos da Silva; Juliana Comerlato; Manoela T. Rodrigues; Juliane D. Fleck; Roger B. da Luz; Thais F. Teixeira; Paulo M. Roehe; Roberta Capalonga; Ana Beatriz Oliveira; Fernando R. Spilki (Food and Environmental Virology, 2013)

Adolescents with chronic migraine commonly exhibit depressive symptoms - Juliana Harumi Arita; Jaime Lin; Ricardo Silva Pinho; Thais Soares Cianciarullo Minett; Maria Sylvia de Souza Vitalle; Mauro Fisberg; Mario Fernando Prieto Peres; Luiz Celso Pereira Vilanova; Marcelo Rodrigues Masruha (Acta Neurologica Belgica, 2013)

Intraspecific variation and emendation of Hannaella kunmingensis - Ifeloju Dayo-Owoyemi; Andre Rodrigues; Melissa F. Landell; Patricia Valente; Ulrich G. Mueller; Jesus Pais Ramos; Fernando C. Pagnocca (Mycological Progress, 2013)

Catabolism of amino acids in livers from cafeteria-fed rats - Cristiane Vizioli de Castro Ghizoni; Fabiana Rodrigues Silva Gasparin; Antonio Sueiti Maeda Júnior; Fernando Olinto Carreño; Rodrigo Polimeni Constantin; Adelar Bracht; Emy Luiza Ishii Iwamoto; Jorgete Constantin (Molecular and Cellular Biochemistry, 2013)

Long-Term Power Transmission Failures in Southeastern Brazil and the Geophysical Environment - Magda A. S. Duro; Pierre Kaufmann; Fernando C. P. Bertoni; Emilio C. N. Rodrigues; José Pissolato Filho (Surveys in Geophysics, 2012)

Humidity levels drive reproductive modes and phylogenetic diversity of amphibians in the Brazilian Atlantic Forest - Fernando Rodrigues da Silva; Mário Almeida‐Neto; Vitor Hugo Mendonça do Prado; Célio Fernando Baptista Haddad; Denise de Cerqueira Rossa‐Feres (Journal of Biogeography, 2012)
Aim The diversity of reproductive modes among amphibians constitutes a striking example of how differences in the biology of species provide important explanations for species distribution patterns on a broad scale. We hypothesize that sites with a higher humidity level will support more modes of reproduction than drier sites and will consequently exhibit a higher phylogenetic diversity. Furthermore, if there is a gradient in the tolerance of reproductive modes to desiccation, there will be a nested pattern in the composition of reproductive modes among sites. Location Twenty‐seven forest sites in the Brazilian Atlantic Forest. Methods Through a path analysis approach, we evaluated the direct and indirect effects of the humidity level on the number of reproductive modes, as well as the relative importance of both variables on amphibian phylogenetic diversity. A nestedness analysis was used to quantify the extent to which the compositions of both species and reproductive modes in drier sites correspond to subsets of those in sites with higher annual precipitation. Results We found that the reproductive modes present in drier sites are non‐random subsets of those present in sites with higher humidity levels. Because reproductive modes are phylogenetically conserved among amphibians, sites with a greater number of reproductive modes supported greater phylogenetic diversity. Sites with high precipitation throughout the year provided suitable environmental conditions for a larger number of reproductive modes, whereas sites with low precipitation and typical seasonal climates supported only those reproductive modes specialized to resist desiccation. Main conclusions Our results show that humidity‐related variables are key environmental factors related to both the richness of reproductive modes and phylogenetic diversity. Our results support the hypothesis that the higher phylogenetic diversity found in moister sites reflects differences in the tolerance to desiccation among different reproductive modes. Given that reproductive modes are associated with susceptibility to desiccation, their incorporation into explanatory models may trigger a significant advance in the understanding of the mechanisms regulating the species richness and composition of amphibian communities.

Isolation and characterization of polymorphic microsatellite loci for the spiny-rat Clyomys bishopi (Rodentia: Echimyidae) - Ana Carolina Ramos Arantes; Roberto Guilherme Trovati; Andréa Cristina Peripato; Fernando Pacheco Rodrigues (Conservation Genetics Resources, 2012)

Dependence of anuran diversity on environmental descriptors in farmland ponds - Fernando Rodrigues da Silva; Carolina Panin Candeira; Denise de Cerqueira Rossa-Feres (Biodiversity and Conservation, 2012)

Acute Brain Damage Induced by Acetaminophen in Mice: Effect of Diphenyl Diselenide on Oxidative Stress and Mitochondrial Dysfunction - Michele Hinerasky da Silva; Edovando José Flores da Rosa; Nélson Rodrigues de Carvalho; Fernando Dobrachinski; João Batista Teixeira da Rocha; Jose L. Mauriz; Javier González-Gallego; Félix Alexandre Antunes Soares (Neurotoxicity Research, 2012)

An integrated GIS for sedimentological and geomorphological analysis of a lagoon environment. Barra de Cananéia inlet region, (Southeastern Brazil) - Luis Américo Conti; Carlos Alberto S. Araujo; Fernando S. Paolo; Roberto L. Barcellos; Marcelo Rodrigues; Michel M. Mahiques; Valdenir V. Furtado (Journal of Coastal Conservation, 2012)

Breeding Habitat and Landscape Correlates of Frog Diversity and Abundance in a Tropical Agricultural Landscape - Fernando Rodrigues da Silva; James P. Gibbs; Denise de Cerqueira Rossa-Feres (Wetlands, 2011)

Nanoparticles: molecular targets and cell signalling - Francelyne Marano; Salik Hussain; Fernando Rodrigues-Lima; Armelle Baeza-Squiban; Sonja Boland (Archives of Toxicology, 2011)

Identification and distribution of mercury species in rat tissues following administration of thimerosal or methylmercury - Jairo L. Rodrigues; Juliana M. Serpeloni; Bruno L. Batista; Samuel S. Souza; Fernando Barbosa (Archives of Toxicology, 2010)

Insights into the Phylogeny or Arylamine N-Acetyltransferases in Fungi - Marta Martins; Julien Dairou; Fernando Rodrigues-Lima; Jean-Marie Dupret; Philippe Silar (Journal of Molecular Evolution, 2010)

The nodC, nodG, and glgX genes of Rhizobium tropici strain PRF 81 - Luciana Ruano Oliveira; Francismar Corrêa Marcelino; Fernando Gomes Barcellos; Elisete Pains Rodrigues; Manuel Megías; Mariangela Hungria (Functional & Integrative Genomics, 2010)

Erratum to: Local and remote tissue injury upon intestinal ischemia and reperfusion depends on the TLR/MyD88 signaling pathway - Tatiana Victoni; Fernando Rodrigues Coelho; Alexandre Learth Soares; Andressa de Freitas; Thomas Secher; Rodrigo Guabiraba; François Erard; Ricardo Martins de Oliveira-Filho; B. Boris Vargaftig; Gregoire Lauvaux; Mamdouh A. Kamal; Bernhard Ryffel; et al. (Medical Microbiology and Immunology, 2010)

Local and remote tissue injury upon intestinal ischemia and reperfusion depends on the TLR/MyD88 signaling pathway - Tatiana Victoni; Fernando Rodrigues Coelho; Alexandre Learth Soares; Andressa de Freitas; Thomas Secher; Rodrigo Guabiraba; François Erard; Ricardo Martins de Oliveira-Filho; B. Boris Vargaftig; Gregoire Lauvaux; Mamdouh A. Kamal; Bernhard Ryffel; et al. (Medical Microbiology and Immunology, 2010)

Potential effects of the herbicide Diuron on mammary and urinary bladder two-stage carcinogenesis in a female Swiss mouse model - Nelci Antunes de Moura; Tony Fernando Grassi; Maria Aparecida Marchesan Rodrigues; Luís Fernando Barbisan (Archives of Toxicology, 2010)

Benthic invertebrate assemblage in Samborombón River (Argentina, S. America), a brackish plain river - Fernando Spaccesi; Alberto Rodrigues Capítulo (Aquatic Ecology, 2009)

Antagonistic interactions between garden yeasts and microfungal garden pathogens of leaf-cutting ants - Andre Rodrigues; Rachel N. Cable; Ulrich G. Mueller; Maurício Bacci; Fernando C. Pagnocca (Antonie van Leeuwenhoek, 2009)

Haplotype and quantitative transcript analyses of Portuguese breast/ovarian cancer families with the BRCA1 R71G founder mutation of Galician origin - Catarina Santos; Ana Peixoto; Patrícia Rocha; Ana Vega; Maria José Soares; Nuno Cerveira; Susana Bizarro; Manuela Pinheiro; Deolinda Pereira; Helena Rodrigues; Fernando Castro; Rui Henrique; et al. (Familial Cancer, 2009)

Metalloproteinases 2 and -9 activity during promotion and progression stages of rat liver carcinogenesis - Kelly Silva Furtado; Paulo Wagner Pires; Luis Antonio Justulin; Maria Aparecida Marchesan Rodrigues; Sergio Luis Felisbino; Luis Fernando Barbisan (Journal of Molecular Histology, 2009)

Yeasts and filamentous fungi carried by the gynes of leaf-cutting ants - Fernando C. Pagnocca; André Rodrigues; Nilson S. Nagamoto; Maurício Bacci (Antonie van Leeuwenhoek, 2008)

High frequency of BF mosaic genomes among HIV-1-infected children from Sao Paulo, Brazil - Cristina Mendes de Oliveira; Flávia Jacqueline Almeida; Rosangela Rodrigues; Marcia Crozatti; Carla Maria Pasquareli Vazquez; Maria do Socorro Carneiro Ferrão; Alexandre Ely Campeas; Silvia Regina Marques; Eitan Naaman Berezin; Luis Fernando de Macedo Brígido (Archives of Virology, 2008)

Loss of heterozygosity at 19p13.2 and 2q21 in tumours from familial clusters of non-medullary thyroid carcinoma - Hugo João Prazeres; Fernando Rodrigues; Paula Soares; Plamen Naidenov; Paulo Figueiredo; Beatriz Campos; Manuela Lacerda; Teresa C. Martins (Familial Cancer, 2008)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

BRCA1 and BRCA2 germline mutational spectrum and evidence for genetic anticipation in Portuguese breast/ovarian cancer families - Ana Peixoto; Natália Salgueiro; Catarina Santos; Graça Varzim; Patrícia Rocha; Maria José Soares; Deolinda Pereira; Helena Rodrigues; Maria José Bento; António Fráguas; Graça Moura; Fernando Regateiro; et al. (Familial Cancer, 2006)

Acute heat exposure increases high-intensity performance during sprint cycle exercise - Ana Cristina R. Lacerda; Fernando Gripp; Luiz Oswaldo C. Rodrigues; Emerson Silami-Garcia; Cândido C. Coimbra; Luciano S. Prado (European Journal of Applied Physiology, 2006)

Evaluation of the use of salivary lead levels as a surrogate of blood lead or plasma lead levels in lead exposed subjects - Fernando Barbosa; Maria Heloísa Corrêa Rodrigues; Maria R. Buzalaf; Francisco J. Krug; Raquel F. Gerlach; José Eduardo Tanus-Santos (Archives of Toxicology, 2006)

Antimicrobial and antiviral activities of an actinomycete (Streptomyces sp.) isolated from a Brazilian tropical forest soil - Doralice Rodrigues Sacramento; Rosalie Reed Rodrigues Coelho; Márcia Dutra Wigg; Luiz Fernando de Toledo Luna Linhares; Marta Gonçalves Matos dos Santos; Luzia Teixeira de Azevedo Soares Semêdo; Antonio Jorge Ribeiro da Silva (World Journal of Microbiology and Biotechnology, 2004)

Changes in ectonucleotidase activities in rat Sertoli cells during sexual maturation - Emerson André Casali; Luiz Fernando de Souza; Daniel Pens Gelain; Glória Regina Rodrigues de Freitas Kaiser; Ana Maria Oliveira Battastini; João José Freitas Sarkis (Molecular and Cellular Biochemistry, 2003)

Characterization of the Ecdysteroid UDP-Glucosyltransferase (egt) Gene of Anticarsia gemmatalis Nucleopolyhedrovirus - Júlio Carlyle Macedo Rodrigues; Marlinda Lobo De Souza; David O'reilly; Lucas Malard Velloso; Francisco José Rivera Pinedo; Fernando Barcellos Razuck; Berghem Ribeiro; Bergmann Morais Ribeiro (Virus Genes, 2001)

Analysis of the allelic diversity of a (CA)n repeat polymorphism among α1-antitrypsin gene products from northern Portugal - J. Rocha; Dalila Pinto; M. Teresa Santos; António Amorim; Jorge Amil-Dias; Fernando Cardoso-Rodrigues; Álvaro Aguiar (Human Genetics, 1997)